Transparent article having high superficial layer hardness and display device having same

By arranging an optical film structure with a scratch-resistant layer and alternating high and low refractive index layers on a glass ceramic substrate, the problem of difficulty in achieving transparent products with high hardness and low reflectivity in the existing technology is solved, and efficient optical and mechanical properties are achieved. combine.

CN119343615APending Publication Date: 2025-01-21CORNING INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202380045697.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-04-28
Filing Date
2023-05-01
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The prior art is difficult to achieve high shallow hardness, low reflectivity, low glare, high visible and infrared transmittance, low reflectance color and color uniformity, and in some cases damage resistance while protecting optical products and equipment. Transparent products with high modulus and high fracture toughness.

Method used

An optical film structure including a scratch-resistant layer and a plurality of alternating high-refractive-index and low-refractive-index layers is provided on the outer surface of the glass ceramic substrate. The outer structure of the optical film structure includes at least one medium refractive index layer, and the sum of the physical thicknesses of all low refractive index layers is less than about 200 nm.

Benefits of technology

Achieve high shallow layer hardness, low reflectivity, low glare, high visible and infrared transmission, low reflective color and color uniformity while maintaining the strength grade of the substrate and in some cases providing damage resistance, high modulus strength and high fracture toughness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119343615A_ABST
    Figure CN119343615A_ABST
Patent Text Reader

Abstract

Described herein is a transparent article comprising: a substrate comprising opposing first and second major surfaces; and an optical film structure disposed on the first main surface. The optical film structure includes a scratch resistant layer, a plurality of alternating high refractive index (RI) and low RI layers, and an outer structure and an inner structure, the scratch resistant layer disposed between the outer structure and the inner structure. The outer structure may include at least one medium RI layer in contact with one of the high RI layer and the scratch resistant layer. The medium RI layer comprises RI of 1.55 to 1.80, and each of the high RI layers comprises gt; 1.80, and each of the low RI layers includes lt; the RI is greater than 1.55. The sum of physical thicknesses of all the low RI layers in the outer structure may be lt; the particle size is 200 nm.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of priority under patent law to U.S. Provisional Application No. 63 / 337,846 filed on May 3, 2022, U.S. Provisional Application No. 63 / 441,293 filed on January 26, 2023, and U.S. Provisional Application No. 63 / 462,661 filed on April 28, 2023, the contents of which are incorporated herein by reference in their entirety. Technical Field

[0003] The present disclosure relates to transparent articles for protecting optical articles and display devices, and more particularly to transparent articles having a substrate with an optical film structure disposed thereon, which transparent articles exhibit various optical and mechanical performance attributes, including but not limited to high shallow layer hardness, low reflectivity, low glare, high visible and infrared transmittance, low reflective color, color uniformity, minimized overall thickness, retained strength, and minimized deposition warpage. Background Art

[0004] Covered articles with glass substrates are often used to protect key devices and components in electronic products and systems (e.g., mobile devices, smart phones, tablet computers, handheld devices, car displays, and other electronic devices with displays, cameras, light sources, and / or sensors). These covered articles can also be used in architectural products, transportation products (e.g., products for automotive applications, trains, aircraft, marine vehicles, etc.), home appliance products, or any products that require a certain degree of transparency, scratch resistance, abrasion resistance, or a combination thereof.

[0005] These applications using cover glass articles generally require a combination of mechanical and environmental durability, vandalism resistance, damage resistance, scratch resistance, and strong optical performance characteristics. For example, the cover article may need to exhibit high light transmittance, low reflectivity, and / or low transmittance color in the visible spectrum. In some applications, the cover article needs to cover and protect display devices, cameras, sensors, and / or light sources. In addition, recent data indicate that high hardness of the outer surface of the optical structure near the cover article can significantly improve scratch and abrasion resistance, more specifically against scratches from sliding motions with low normal forces.

[0006] Furthermore, conventional covered articles using glass or glass-ceramic substrates with optical film structures may suffer from reduced mechanical properties at the article level. More specifically, including optical film structures on these substrates provides advantages in optical performance and certain mechanical properties (e.g., scratch resistance); however, conventional combinations of these substrates with optical film structures (e.g., optimizations utilizing high modulus and / or hardness to improve scratch resistance) result in poor strength levels for the resulting articles. It should be noted that the presence of an optical film structure on a substrate may disadvantageously reduce the strength level of the article below that of the substrate in bare form without the optical film structure.

[0007] Therefore, there is a need for improved cover articles for protecting optical articles and devices, more particularly transparent articles that exhibit high shallow hardness (or more generally high hardness), low reflectivity, low glare, high visible and infrared transmittance, low reflective color and color uniformity, and in some cases damage resistance, high modulus, and / or high fracture toughness. There is also a need for the above transparent articles that employ optical film structures with minimized total thickness and deposited warpage levels and retained hardness and strength. In addition, there is a need for the aforementioned transparent articles that maintain or substantially maintain bare substrate strength levels (e.g., at or above the application drive threshold) after including the optical film structure. The present disclosure addresses these needs and other needs. Summary of the invention

[0008] According to aspects of the present disclosure, a transparent article is provided, comprising: a substrate comprising a first major surface and a second major surface, the major surfaces being opposite to each other; and an optical film structure defining an outer surface, the optical film structure being disposed on the first major surface. The optical film structure comprises a scratch-resistant layer and a plurality of alternating high refractive index (RI) and low RI layers. In addition, the optical film structure comprises an outer structure and an inner structure, the scratch-resistant layer being disposed between the outer structure and the inner structure. In addition, one or both of the following: (i) the outer structure comprises at least one medium RI layer, the at least one medium RI layer being in contact with one or both of the following: (a) the scratch-resistant layer, and (b) one of the high RI layers; and (ii) the sum of the physical thicknesses of all the low RI layers in the outer structure is less than about 200 nm. In addition, at least one medium RI layer comprises a refractive index of 1.55 to 1.80, each of the high RI layers comprises a refractive index greater than 1.80, and each of the low RI layers comprises a refractive index less than 1.55.

[0009] According to aspects of the present disclosure, a transparent article is provided, comprising: a substrate comprising a first major surface and a second major surface, the major surfaces being opposite to each other; and an optical film structure defining an outer surface, the optical film structure being disposed on the first major surface. The optical film structure comprises a scratch-resistant layer and a plurality of alternating high refractive index (RI) and low RI layers. In addition, the optical film structure comprises an outer structure and an inner structure, the scratch-resistant layer being disposed between the outer structure and the inner structure. The outer structure comprises at least one medium RI layer, the at least one medium RI layer being in contact with one or both of the following: (a) the scratch-resistant layer, and (b) one of the high RI layers. In addition, the medium RI layer comprises a refractive index of 1.55 to 1.80, each of the high RI layers comprises a refractive index greater than 1.80, and each of the low RI layers comprises a refractive index less than 1.55.

[0010] According to another aspect of the present disclosure, a transparent article is provided, comprising: a substrate comprising a first major surface and a second major surface, the major surfaces being opposite to each other; and an optical film structure defining an outer surface, the optical film structure being disposed on the first major surface. The optical film structure comprises a scratch-resistant layer and a plurality of alternating high refractive index (RI) and low RI layers. In addition, the optical film structure comprises an outer structure and an inner structure, the scratch-resistant layer being disposed between the outer structure and the inner structure. In addition, the sum of the physical thicknesses of all the low RI layers in the outer structure is less than about 75 nm.

[0011] According to a further aspect of the present disclosure, a transparent article is provided, comprising: a substrate comprising a first major surface and a second major surface, the major surfaces being opposite to each other; and an optical film structure defining an outer surface, the optical film structure being disposed on the first major surface. The optical film structure comprises a scratch-resistant layer and a plurality of alternating high refractive index (RI) and low RI layers. In addition, the optical film structure comprises an outer structure and an inner structure, the scratch-resistant layer being disposed between the outer structure and the inner structure. The outer structure comprises at least one medium RI layer in contact with one of the high RI layers and the scratch-resistant layer. In addition, the medium RI layer comprises a refractive index of 1.55 to 1.80, each of the high RI layers comprises a refractive index greater than 1.80, and each of the low RI layers comprises a refractive index less than 1.55. In addition, the sum of the physical thicknesses of all low RI layers in the outer structure is less than about 75 nm.

[0012] According to aspects of the present disclosure, a transparent article is provided, comprising: a substrate comprising a first major surface and a second major surface, the major surfaces being opposite to each other; and an optical film structure defining an outer surface, the optical film structure being disposed on the first major surface. The optical film structure comprises a scratch-resistant layer and a plurality of alternating high refractive index (RI) and low RI layers. In addition, the optical film structure comprises an outer structure and an inner structure, the scratch-resistant layer being disposed between the outer structure and the inner structure. In addition, the sum of the physical thicknesses of all low RI layers in the outer structure is less than about 75 nm. In addition, the article exhibits an average first surface photopic reflectance of less than 7% and a first surface reflectance at a wavelength of 940 nm of less than 8%, each measured at a near normal incidence angle.

[0013] According to another aspect of the present disclosure, a transparent article is provided, comprising: a substrate comprising a first major surface and a second major surface, the major surfaces being opposite to each other; and an optical film structure defining an outer surface, the optical film structure being disposed on the first major surface. The optical film structure comprises a scratch-resistant layer and a plurality of alternating high refractive index (RI) and low RI layers. In addition, the optical film structure comprises an outer structure and an inner structure, the scratch-resistant layer being disposed between the outer structure and the inner structure. In addition, the sum of the physical thicknesses of all low RI layers in the outer structure is less than about 200 nm. In addition, the article exhibits an average first surface photopic reflectance of less than 3% and a first surface reflectance at a wavelength of 940 nm of less than 5%, each measured at a near normal incidence angle.

[0014] According to aspects of the present disclosure, a transparent article is provided, comprising: a glass-ceramic substrate comprising a first major surface and a second major surface, the major surfaces being opposite to each other; and an optical film structure defining an outer surface, the optical film structure being disposed on the first major surface. The optical film structure comprises a scratch-resistant layer and a plurality of alternating high refractive index (RI) and low RI layers. In addition, the optical film structure comprises an outer structure and an inner structure, the scratch-resistant layer being disposed between the outer structure and the inner structure. The outer structure comprises at least one medium RI layer in contact with one of the high RI layers and the scratch-resistant layer. In addition, the medium RI layer comprises a refractive index of 1.55 to 1.80, each of the high RI layers comprises a refractive index greater than 1.80, and each of the low RI layers comprises a refractive index less than 1.55. In addition, the glass-ceramic substrate comprises an elastic modulus greater than 85 GPa and a fracture toughness greater than 0.8 MPa·√m.

[0015] According to aspects of the present disclosure, a transparent article is provided, comprising: a substrate comprising a first major surface and a second major surface, the major surfaces being opposite to each other; and an optical film structure defining an outer surface, the optical film structure being disposed on the first major surface. The optical film structure comprises a scratch-resistant layer and a plurality of alternating high refractive index (RI) and low RI layers. In addition, the optical film structure comprises an outer structure and an inner structure, the scratch-resistant layer being disposed between the outer structure and the inner structure. The outer structure comprises at least one medium RI layer, the at least one medium RI layer being in contact with one or both of the following: (a) the scratch-resistant layer, and (b) one of the high RI layers. In addition, at least one medium RI layer comprises a refractive index of 1.55 to 1.80, each of the high RI layers comprises a refractive index greater than 1.80, and each of the low RI layers comprises a refractive index less than 1.55. The optical film structure has a physical thickness of about 200 nm to 5000 nm. In addition, the article exhibits a first surface average photopic reflectance of less than 6%. In addition, the article exhibits one or more of the following: (i) a hardness greater than 11 GPa at an indentation depth of approximately 20 nm or 40 nm, as measured by the Berkovich hardness test at the outer surface of the optical film structure; (ii) a hardness greater than 15 GPa at an indentation depth of 100 nm; and (iii) a hardness greater than 16 GPa at an indentation depth of 125 nm.

[0016] According to aspects of the present disclosure, a transparent article is provided, comprising: a substrate comprising a first major surface and a second major surface, the major surfaces being opposite to each other; and an optical film structure defining an outer surface, the optical film structure being disposed on the first major surface. The optical film structure comprises a scratch-resistant layer and a plurality of alternating high refractive index (RI) and low RI layers. In addition, the optical film structure comprises an outer structure and an inner structure, the scratch-resistant layer being disposed between the outer structure and the inner structure. The outer structure comprises at least one medium RI layer, the at least one medium RI layer being in contact with one or both of: (a) the scratch-resistant layer, and (b) one of the high RI layers. In addition, at least one medium RI layer comprises a refractive index of 1.55 to 1.80, each of the high RI layers comprises a refractive index greater than 1.80, and each of the low RI layers comprises a refractive index less than 1.55. The optical film structure has a physical thickness of about 200 nm to 800 nm. In addition, the article exhibits a first surface average photopic reflectance of less than 6%. In addition, the article exhibits one or more of the following: (i) a hardness greater than 9 GPa at an indentation depth of 20 nm; (ii) a hardness greater than 10 GPa at an indentation depth of 40 nm; (iii) a hardness greater than 12 GPa at an indentation depth of 100 nm; (iv) a hardness greater than 12 GPa at an indentation depth of 125 nm (measured on the outer surface of the optical film structure by the Berkovich hardness test).

[0017] According to aspects of the present disclosure, a transparent article is provided, comprising: a substrate comprising a first major surface and a second major surface, the major surfaces being opposite to each other; and an optical film structure defining an outer surface, the optical film structure being disposed on the first major surface. The optical film structure comprises a scratch-resistant layer and a plurality of alternating high refractive index (RI) and low RI layers. In addition, the optical film structure comprises an outer structure and an inner structure, the scratch-resistant layer being disposed between the outer structure and the inner structure. The outer structure comprises at least one medium RI layer, the at least one medium RI layer being in contact with one or both of the following: (a) the scratch-resistant layer, and (b) one of the high RI layers. In addition, at least one medium RI layer comprises a refractive index of 1.55 to 1.80, each of the high RI layers comprises a refractive index greater than 1.80, and each of the low RI layers comprises a refractive index less than 1.55. In addition, the scratch-resistant layer has a physical thickness of about 100 nm to less than 2000 nm.

[0018] According to other aspects of the present disclosure, a display device is provided, comprising one or more of the aforementioned transparent articles, wherein each article serves as a protective cover for the display device.

[0019] Additional features and advantages will be set forth in the detailed description which follows, and may be understood in part by those skilled in the art from that description, or may be learned by practicing the embodiments described herein, including the detailed description which follows, the claims, and the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] It should be understood that both the foregoing general description and the following detailed description are exemplary only and are intended to provide an overview or framework for understanding the nature and character of the claims. The accompanying drawings are included to provide a further understanding and are incorporated into and constitute a part of this specification. The drawings illustrate one or more embodiments and together with the description explain the principles and operation of the various embodiments, wherein:

[0021] Figure 1A , Figure 1B , Figure 1C , Figure 1D , Figure 1E , Figure 1F and Figure 1G is a cross-sectional side view of a transparent article (e.g., for use in a display device) according to one or more embodiments of the present disclosure;

[0022] Figure 2A is a plan view of an exemplary electronic device incorporating any of the transparent articles disclosed herein;

[0023] Figure 2B yes Figure 2AA perspective view of an exemplary electronic device;

[0024] Figure 3A , Figure 4A and Figure 5A are graphs of first surface reflectance and wavelength measured at a near normal incidence angle of 8° for three comparative products, respectively;

[0025] Figure 3B , Figure 4B and Figure 5B Is has Figure 3A , Figure 4A and Figure 5A A graph of the single-side reflection color measured at incident angles of 0° to 90° using various optical film structure thickness scaling factors for three comparative products of the optical properties in FIG.

[0026] Fig. 6A , Fig. 7A and Fig. 8A are graphs of first surface reflectance versus wavelength measured at a near normal incidence angle of 8° for three transparent articles of the present disclosure, respectively;

[0027] Figure 6B , Figure 7B and Figure 8B Is has Fig. 6A , Fig. 7A and Fig. 8A Graphs of the single-side reflected color measured at incident angles of 0° to 90° using various optical film structure thickness scaling factors for three transparent articles of the present disclosure of the optical properties in FIG.

[0028] Fig. 9A Is has FIG. 6A to FIG. 8B The transparent products of the present disclosure having the optical properties of Figure 4A and Figure 4B Box plot of average product failure stress measured in ring-to-ring testing for comparative products of optical properties in FIG.

[0029] Fig. 9B and Fig. 9C is to have FIG. 6A to FIG. 8B Graphs of hardness and elastic modulus versus displacement as measured in a Berkovich hardness test of an optical film structure of a transparent article of the present disclosure of optical properties;

[0030] Fig. 10A , Fig.11A , Fig. 12A , Fig.13A , Fig.14A , Fig.15A , Fig.16A , Fig.17A and Fig. 20Aare graphs of first surface reflectance versus wavelength measured at a near normal incidence angle of 8° for nine transparent articles of the present disclosure, respectively;

[0031] Fig. 10B , Fig. 11B , Fig. 12B , Fig. 13B , Fig. 14B , Fig. 15B , Fig. 16B , Fig. 17B and Fig. 20B Is has Fig. 10A , Fig.11A , Fig. 12A , Fig.13A , Fig.14A , Fig.15A , Fig.16A , Fig.17A and Fig. 20A Graphs of single-side reflected color measured at incident angles of 0° to 90° using various optical film structure thickness scaling factors for nine transparent articles of the present disclosure of optical properties in FIG.

[0032] Fig.18A and Fig.19A are graphs of first surface reflectance versus wavelength measured at a near normal incidence angle of 6° for two transparent articles of the present disclosure, respectively;

[0033] Fig.18B and Fig.19B Is has Fig.18A and Fig.19A A graph of the single-side reflected color of two transparent articles of the present disclosure of optical properties measured at incident angles of 0° to 90°;

[0034] Fig.21 is a table summarizing the optical and mechanical properties of comparative and inventive examples of the present disclosure;

[0035] Fig. 22 is a graph of average article failure stress versus optical film structure residual stress modeled for transparent articles having an optical film structure of the present disclosure exhibiting different elastic modulus values;

[0036] Fig.23A is a box plot of average article edge failure stresses measured in a 4-point bend test for transparent articles of the present disclosure and comparative articles without an optical film structure;

[0037] Fig. 23B yes Fig.23A A graph of single-side reflectivity versus wavelength for a transparent product of measured at a near-normal incident angle of 8°;

[0038] Fig.23C yes Fig.23A A graph of the single-side reflected color of a transparent product measured at incident angles of 0° to 90° using various optical film structure thickness scaling factors;

[0039] Fig.24 is a graph of hardness (GPa) versus indentation depth (0 to 50 nm) measured in a Berkovich hardness test for optical film structures of transparent articles of the present disclosure and comparative articles;

[0040] Fig.25A is a graph of first surface reflectance versus wavelength for a comparative article measured at a near normal angle of incidence of 8°;

[0041] Fig.25B Is has Fig.25A A graph of the single-side reflected color of a comparative product of the optical properties measured at an incident angle of 0° to 90°;

[0042] Fig.26A , Fig.27A , Fig.28A , Fig.29A , Fig. 30A , Fig.31A , Fig.32A , Fig.33A , Fig.34A , Fig.35A and Fig.36A are graphs of first surface reflectance versus wavelength measured at a near normal incidence angle of 8° for eleven transparent articles of the present disclosure, respectively;

[0043] Fig.26B , Fig.27B , Fig.28B , Fig.29B , Fig. 30B , Fig.31B , Fig.32B , Fig.33B , Fig.34B , Fig.35B and Fig.36B Is has Fig.26A , Fig.27A , Fig.28A , Fig.29A , Fig. 30A , Fig.31A , Fig.32A , Fig.33A , Fig.34A , Fig.35A and Fig.36A A graph of the single-side reflected color of a transparent article of the present disclosure measured at an incident angle of 0° to 90°;

[0044] Fig.29C is to have Fig.29A and Fig.29BA graph of hardness (GPa) versus indentation depth as measured in a Berkovich hardness test of an optical film structure of a transparent article of the present disclosure of optical properties;

[0045] Fig.37A is a schematic diagram of a comparative article having an optical film structure with a scratch-resistant layer having different thickness levels;

[0046] Fig.37B is modeled to indicate the Fig.37A A schematic diagram of the hardness (GPa) and the indentation depth of the Berkovich hardness test results of the optical film structure of the comparative product;

[0047] Fig.38 is a schematic diagram of the basic fracture mechanics principle of the transparent article of the present disclosure;

[0048] Fig.39A and Fig.39B is a schematic diagram of a transparent article of the present disclosure subjected to pure bending with equal moments to evaluate warpage as a function of thickness of the optical film structure;

[0049] Fig.40A is a graphical representation of hardness (GPa) versus indentation depth modeled to indicate results from Berkovich hardness testing of optical film structures of transparent articles of the present disclosure having different levels of scratch resistant layer thickness;

[0050] Fig.40B is modeled to indicate the Fig.40A A schematic diagram of the Berkovich hardness test results of the optical film structure of the transparent product and the hardness (GPa) and the thickness of the scratch-resistant layer;

[0051] Fig.41A and Fig.41B Modeled to indicate different levels of scratch resistant layer thickness Fig.40A Schematic diagram of the retention strength (MPa) and substrate defect size of a ring-to-ring (ROR) test of a transparent product and a control sample without an optical film structure;

[0052] Fig.41C is modeled to indicate Fig.40A Schematic diagram of surface retention strength and the strength at a depth of 63 μm in the ROR test of a transparent product and the thickness of the scratch-resistant layer;

[0053] Fig.42A Available in different scratch resistant layer thickness grades Fig.40A Schematic diagram of net deflection and one-sided material removal of a transparent article; and

[0054] Fig.42B The one-sided material removal and Fig.40A Schematic diagram of the function of the thickness of the scratch-resistant layer of a transparent article. DETAILED DESCRIPTION

[0055] In the following embodiments, for the purpose of explanation rather than limitation, the exemplary embodiments of the disclosure details are described to provide a thorough understanding of the various principles of the present disclosure. However, those skilled in the art who benefit from the present disclosure should understand that the present disclosure can be practiced in other embodiments different from the specific details shown herein. In addition, the description of conventional equipment, methods and materials can be omitted to avoid blurring the description of the various principles of the present disclosure. Finally, similar component symbols represent similar components in any applicable place.

[0056] Ranges expressed herein may be from "about" one particular value and / or to "about" another particular value. When such a range is expressed, another embodiment includes from the one particular value and / or to the other particular value. Likewise, when values ​​are expressed in an approximate manner using the preposition "about," it will be understood that the particular value will form another embodiment. It will be further understood that each endpoint of a range is clearly related to, and independent of, the other endpoint.

[0057] Directional terms used herein (eg, "upper," "lower," "right," "left," "front," "back," "top," "bottom") apply only with reference to the drawings depicted and are not intended to imply an absolute orientation.

[0058] Unless otherwise expressly stated, any method described herein is not to be construed as requiring that its steps be performed in a specific order. Therefore, in the event that a method claim does not actually recite the order of its steps or does not specifically state in the claim or narrative that the steps are limited to a specific order, the order is not to be inferred in any way in any respect. This applies to any possible non-expressive basis for description, including logical subject matter for arrangement or operational flow; general meaning derived from grammatical organization or punctuation; the number or type of embodiments described in the specification.

[0059] As used herein, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, reference to a "component" includes aspects having two or more components unless the context clearly dictates otherwise.

[0060] As used herein, the term "disposed" includes coating, depositing, and / or forming a material on a surface using any method known or developed in the art. The disposed material may constitute a layer as defined herein. As used herein, the phrase "disposed on" includes steps of forming a material onto a surface so that the material is in direct contact with the surface, as well as embodiments in which the material is formed on a surface using one or more intervening materials disposed between the material and the surface. The one or more intervening materials may constitute a layer as defined herein.

[0061] As used herein, the terms "low RI layer", "medium RI layer" and "high RI layer" refer to the relative values ​​of the refractive index ("RI") of the layers of the optical film structure of the transparent article according to the present disclosure. Therefore, the refractive index of the low RI layer < the refractive index of the medium RI layer < the refractive index of the high RI layer, unless otherwise explicitly stated in the present disclosure. Therefore, the refractive index value of the low RI layer is less than the refractive index values ​​of the medium RI layer and the high RI layer. Further, as used herein, "low RI layer" and "low refractive index layer" can be interchanged and have the same meaning. Similarly, "medium RI layer" and "medium refractive index layer" can be interchanged and have the same meaning. Similarly, "high RI layer" and "high refractive index layer" can be interchanged and have the same meaning.

[0062] As used herein, the term "glass ceramic substrate" is not limited to a glass ceramic substrate. Rather, the term "glass ceramic substrate" refers to a group of substrates including a glass ceramic substrate, a ceramic substrate, a glass substrate, a sapphire substrate, a strengthened glass substrate, and a strengthened glass ceramic substrate.

[0063] As used herein, the term "strengthened substrate" refers to a substrate used in the transparent article of the present disclosure that has been chemically strengthened, for example, a substrate strengthened by ion exchange of smaller ions in the surface of the substrate for larger ions. However, other strengthening methods known in the art (e.g., thermal tempering or utilizing the mismatch in the coefficient of thermal expansion between portions of the substrate to produce compressive stress and a central tension region) may be used to form a strengthened substrate.

[0064] As used herein, "Berkovich indenter hardness test" and "Berkovich hardness test" may be used interchangeably to refer to a test that measures the hardness of a material on its surface by indenting the surface with a diamond Berkovich indenter. The Berkovich indenter hardness test includes using a diamond Berkovich indenter to indent a single optical film structure or the outermost surface (e.g., exposed surface) of the transparent article of the present disclosure to form an indentation with an indentation depth in the range of about 50 nm to about 1000 nm (or the entire thickness of the outer or inner optical film structure, whichever is smaller), and measuring the maximum hardness of the indentation along the entire indentation depth range or a portion of the indentation depth (e.g., in the range of about 100 nm to about 600 nm), typically using Oliver, WC and Pharr, GM, "An improved technique for determining hardness and elastic modulus using load and displacement sensing indentation experiments", J. Mater. Res., Vol. 7, No. 6, 1992, 1564-1583, and Oliver, WC and Pharr, GM, "Measurement of Hardness and Elasticity", J. Mater. Res., Vol. 19, No. 1, 2004, 3-20. As used herein, each of “hardness” and “maximum hardness” interchangeably refers to the maximum hardness measured along the range of indentation depth, rather than the average hardness.

[0065] As used herein, the term "ring-to-ring test", "Ring-on-Ring test" or "ROR test" refers to a test used to determine the breaking strength or stress (in MPa) of transparent articles of the present disclosure and comparative articles. Each ROR test was performed using a test apparatus that used loading and support rings made of high-strength steel with diameters of 12.7 mm and 25.4 mm, respectively. In addition, the load-bearing surfaces of the loading and support rings were machined to a radius of approximately 0.0625 inches to minimize stress concentration in the contact area between the rings and the transparent article. In addition, the loading ring was placed on the outermost major surface of the transparent article (e.g., on the outer surface of its optical film structure), while the support ring was placed on the innermost major surface of the transparent article (e.g., on the second major surface of its substrate). The loading ring includes a mechanism that enables the loading ring to be articulated and ensures proper alignment and uniform loading of the test sample. In addition, each ROR test was performed by pressing the loading ring against the transparent article using a loading rate of 1.2 mm / min. The term "average" in the ROR test is a mathematical average based on the breaking stress measurements made for five (5) samples. In addition, unless otherwise specified in the specific examples of the present disclosure, all the breaking stress values ​​and measurements described herein refer to the measurements from the ROR test in which the outer surface of the article is placed in tension, as described in International Publication No. WO2018 / 125676 entitled "Coated Articles with Optical Coatings Having Residual Compressive Stress" published on July 5, 2018, and incorporated herein by reference in its entirety. The failure in each ROR test usually occurs on the side of the sample opposite to the loading ring in tension, and finite element modeling is used to provide an appropriate conversion from the breaking load to the breaking stress at the location of the failure. It should also be understood that other breaking strength tests can be used to determine the breaking strength of the transparent articles of the present disclosure, wherein the appropriate correlation of the ROR values ​​and results reported in the present disclosure is established based on differences in test conditions, test sample geometry, and other technical considerations understood by those skilled in the art. However, unless otherwise specified, all average breaking strength values ​​reported for the transparent articles of the present disclosure and the comparative articles are measured according to the ROR test.

[0066] As used herein, the terms "four-point bend test," "4-point bend test," "4-pt bend test," or the like refer to mechanical property tests performed on transparent articles of the present disclosure in accordance with ASTM C158, Standard Test Method for Flexural Strength of Glass, which is incorporated herein by reference in its entirety. In the context of the present disclosure, unless otherwise noted, all transparent articles subjected to such tests are tested with the side of the article having the optical film structure in compression (i.e., facing up) or in tension (i.e., facing down). Comparative control articles without optical film structures but with an easy-to-clean (ETC) coating are tested with the ETC-coated side in compression (i.e., facing up) or in tension (i.e., facing down). In all other respects, all tests referred to as four-point bend tests in the present disclosure are performed in accordance with the ASTM C158 protocol.

[0067] As used herein, the term "transmittance" is defined as the percentage of incident optical power within a given wavelength range that is transmitted through a material (e.g., an article, a substrate, or an optical film or portion thereof). The term "reflectivity" is similarly defined as the percentage of incident optical power within a given wavelength range that is reflected from a material (e.g., an article, a substrate, or an optical film or portion thereof). Transmittance and reflectance can be measured using a specific line width. As used herein, "average transmittance" refers to the average amount of incident optical power transmitted through a material within a defined wavelength range. As used herein, "average reflectivity" refers to the average amount of incident optical power reflected by a material.

[0068] As used herein, "photopic reflectance" simulates the response of the human eye by weighting the reflectance or transmittance and the wavelength spectrum, respectively, according to the sensitivity of the human eye. According to known conventions (e.g., CIE color space conventions), photopic reflectance can also be defined as the illuminance of the reflected light or the Y value of the tristimulus. As used herein, the "average photopic reflectance" for the wavelength range of 380nm to 720nm is defined in the following equation as the spectral reflectance R(λ) related to the spectral response of the eye multiplied by the illuminant spectrum I(λ) and the CIE color matching function

[0069]

[0070] In addition, "average reflectivity" can be determined in the visible spectrum or other wavelength ranges (e.g., in the infrared spectrum from 840 nm to 950 nm, etc.) according to measurement principles understood by those skilled in the art. Unless otherwise stated, all reflectivity values ​​reported or otherwise cited in this disclosure are associated with testing through both the major surface of the substrate and the optical film structure of the transparent article of the present disclosure (e.g., "dual-surface" average photopic reflectivity). Where "one surface" or "first surface" reflectivity is specified, the reflectivity from the rear surface of the article is eliminated through optical bonding with a light absorber, allowing the reflectivity of only the first surface to be measured.

[0071] The usability of a transparent article in an electronic device (e.g., as a protective cover) can be related to the total amount of reflectivity in the article. Photopic reflectivity is particularly important for display devices that use visible light. Lower reflectivity in a cover transparent article over a lens and / or display associated with a device can reduce multiple reflections in the device that can produce "ghost images." Therefore, reflectivity has an important relationship with the image quality associated with the device, more specifically its display and any other optical components (e.g., a lens of a camera). Displays with lower reflectivity can also achieve better display readability, reduced eye fatigue, and faster user response times (e.g., in automotive displays, display readability is also related to driver safety). Displays with lower reflectivity can also allow for reduced display energy consumption and increased device battery life, because the display brightness of a display with lower reflectivity can be reduced compared to a standard display, while still maintaining a target level of display readability in bright ambient environments.

[0072] As used herein, "photopic transmittance" is defined as the spectral transmittance T(λ) related to the spectral response of the eye multiplied by the illuminant spectrum I(λ) and the CIE color matching function in the following equation:

[0073]

[0074] In addition, "average transmittance" or "average photopic transmittance" can be determined in the visible spectrum or other wavelength ranges (e.g., in the infrared spectrum from 840 nm to 950 nm, etc.) according to measurement principles understood by those skilled in the art. Unless otherwise specified, all transmittance values ​​reported or otherwise referenced in the present disclosure and claims are related to the transmission through the major surface of the substrate and the optical film structure of the transparent article (e.g., Figures 1A to 1D The substrate 110, major surfaces 112, 114, and optical film structure 120 shown and described below both (eg, "dual-surface" average photopic transmittance).

[0075] As used herein, "transmittance color" and "reflection color" refer to the transmission or reflection color of a transparent article of the present disclosure in the CIEL*, a*, b* colorimetric system under D65 illuminant. More specifically, because the transmission color of a transparent article through a D65 illuminant in an incident angle range of, for example, from 0 degrees to 10 degrees (e.g., Figures 1A to 1D These color coordinates are measured in transmission or reflection from a major surface of the substrate (substrate 110, major surfaces 112, 114, and optical film structure 120) as shown and described below, so the "transmitted color" and "reflected color" are given by √(a* 2 +b* 2 ) given.

[0076] As also used herein, "optical film structure thickness scaling factor" is interchangeable with "thickness scaling factor" and generally refers to the expected differences in the thickness of the optical film structures of the present disclosure that may result from the vapor deposition of the optical film structures on a non-planar substrate or a non-planar portion of a substrate. These optical film structure thickness differences as a function of the method used to deposit these structures on a substrate are described in detail in U.S. Provisional Patent Application No. 63 / 314,041 filed on February 25, 2022, wherein the major portions related to thickness scaling factors and similar concepts are incorporated herein by reference. Therefore, these variations in the thickness of the optical film structure may result in non-uniformity in the transmission and / or reflection color exhibited by the transparent articles of the present disclosure having such optical film structures. Therefore, the transmittance and reflectance color values ​​of various thickness scale factors are recorded in the present disclosure such that "100%" corresponds to a color measurement on the optical film structure on a flat surface of a substrate or at the maximum thickness of the optical film structure on the surface of a substrate, "90%" corresponds to a color measurement of the optical film structure on a non-flat surface having 90% of the thickness of a portion of the optical film structure on an adjacent flat surface or a portion of the optical film structure on the surface of a substrate having a maximum thickness, and so on.

[0077] In general, the present disclosure relates to transparent articles using optical film structures on substrates (including reinforced substrates). In addition, these transparent articles can include optically transparent high toughness and high modulus glass-ceramic substrates with high hardness optical coatings with controlled transmittance and color. In view of this combination of substrate and optical film structure, the transparent article can exhibit high shallow hardness, while also exhibiting transparency, low reflectivity, high visible and infrared transmittance and low chroma. In addition, the transparent articles of the present disclosure can advantageously exhibit a destructive strength grade that is the same as or substantially close to that of a bare glass-ceramic substrate.

[0078] In aspects of these transparent articles, the optical film structure is configured such that the employed article exhibits a hardness of at least about 12 GPa, at least about 15 GPa, or even at least about 17 GPa at a Barkovich indentation depth of about 125 nm from the outer surface of the optical film structure. x 、SiO x N y 、SiN y , and / or Si3N4 layers, including a scratch-resistant layer (e.g., embedded in the structure). According to some implementations, the outer structure of the optical film structure above the scratch-resistant layer can be configured to have a high RI layer and a scratch-resistant layer (e.g., SiO x N y or SiN y ) in contact with at least one medium RI layer (e.g., SiO x N y ) and / or all low RI layers (e.g., SiO2 or SiO x N y ) is limited to about 75 nm or less. Some or all of these structural features may enable or otherwise significantly affect the achievement of these shallow high hardness levels.

[0079] The transparent articles of the present disclosure can be used for the protection of displays, camera lenses, sensors, and / or light source components in electronic devices or other parts of electronic devices and / or the protection of outer covers and other components (e.g., buttons, speakers, microphones, etc.). These transparent articles with protective functions adopt optical film structures set on substrates, so that the articles show a combination of high shallow hardness and desired optical properties. Advantageously, the transparent articles of the present disclosure show these shallow high hardness levels without significant loss of optical properties (e.g., low reflectivity and low reflective color in the visible and IR spectra).

[0080] As also described in the present disclosure, the aforementioned advantageous article-grade high shallow hardness levels can be achieved through control of the composition and / or arrangement of the optical film structures employed in the transparent articles. It should be noted that the articles of the present disclosure can achieve these hardness levels while maintaining the desired optical properties. With respect to optical properties, the average first surface reflectivity of the transparent articles of the present disclosure can be less than 6%, 5%, or even 4%; the first surface reflectivity at a wavelength of 940nm is less than 7%, 6%, or even 5%; the average first surface reflectivity at IR wavelengths is less than 10%, 9%, or even 8%, all of which are measured at near vertical angles of incidence.

[0081] Transparent products with protective functions can also use optical film structures disposed on glass ceramic substrates, so that the products exhibit high hardness, high damage resistance and a combination of desired optical properties (including high photopic transmittance and low transmittance color). The optical film structure can include a scratch-resistant layer at any different position within the structure. In addition, the optical film structure of these products can include a plurality of alternating high and low refractive index layers, wherein each high refractive index layer and scratch-resistant layer includes a nitride or oxynitride, and each low refractive index layer includes an oxide.

[0082] With respect to mechanical properties, the maximum hardness exhibited by embodiments of the transparent articles of the present disclosure as measured by the Berkovich hardness test over an indentation depth in the range of 100 nm to about 500 nm in the optical film structure may be 10 GPa or greater, or 12 GPa or greater (or even greater than 14 GPa in some cases). The elastic modulus of the glass-ceramic substrates employed in these articles may be greater than 85 GPa, or greater than 95 GPa in some cases. The fracture toughness exhibited by these glass-ceramic substrates may also be greater than 0.8 MPa·√m, or greater than 1 MPa·√m in some cases.

[0083] According to some embodiments of transparent articles of the present disclosure, favorable article-level failure stress levels can be achieved through control of the composition, arrangement, and / or treatment of the optical film structures employed in the transparent articles. It should be noted that the composition, arrangement, and / or treatment of the optical film structures can be adjusted to achieve a residual compressive stress level of at least 700 MPa (e.g., 700 to 1100 MPa) and an elastic modulus of at least 140 GPa (e.g., 140 to 170 GPa, 140 to 180 GPa, 140 to 190 GPa, or 140 to 200 GPa). These optical film structure mechanical properties unexpectedly correlate with average failure stress levels of 500 MPa or greater, 600 MPa or greater, or even 700 MPa or greater measured in ROR testing of the outer surface of the optical film structure of the article placed under tension in transparent articles employing these optical film structures.

[0084] Reference Figures 1A to 1D According to one or more embodiments, the transparent article 100 may include a substrate 110, and an optical film structure 120 defining an outer surface 120a and an inner surface 120b disposed on the substrate 110. The substrate 110 includes opposing major surfaces 112, 114 and opposing minor surfaces 116, 118. The optical film structure 120 is shown in FIG. Figures 1A to 1D, its inner surface 120b is disposed on the first relative major surface 112, and is shown as having no optical film structure disposed on the second relative major surface 114. However, in some embodiments, one or more of the optical film structures 120 may be disposed on the second relative major surface 114 and / or on one or both of the relative minor surfaces 116, 118.

[0085] The optical film structure 120 includes at least one material layer. As used herein, the term "layer" may include a single layer, or may include one or more sub-layers. Such sub-layers may be in direct contact with each other. The sub-layers may be formed of the same material or two or more different materials. In one or more alternative embodiments, such sub-layers may have an intermediate layer of different materials disposed therebetween. In one or more embodiments, the layer may include one or more connected and uninterrupted layers, and / or one or more discontinuous and discontinuous layers (i.e., layers with different materials formed adjacent to each other). The layers or sub-layers may be formed by any known method in the art, including discrete deposition or continuous deposition processes. In one or more embodiments, the layers may be formed using only a continuous deposition process, or alternatively, only a discrete deposition process may be used to form the layers.

[0086] In one or more embodiments, a single-layer or multi-layer optical film structure 120 can be deposited onto the glass ceramic substrate 110 by vacuum deposition techniques such as chemical vapor deposition (e.g., plasma enhanced chemical vapor deposition (PECVD), low pressure chemical vapor deposition, atmospheric pressure chemical vapor deposition, and plasma enhanced atmospheric pressure chemical vapor deposition), physical vapor deposition (e.g., reactive or non-reactive sputtering or laser ablation), thermal or electron beam evaporation, and / or atomic layer deposition. Liquid methods such as spray coating, dip coating, spin coating, or slot coating (e.g., using sol-gel materials) can also be used. In general, vapor deposition techniques can include various vacuum deposition methods that can be used to produce thin films. For example, physical vapor deposition uses a physical process (e.g., heating or sputtering) to generate a vapor of a material that is then deposited on the object being coated. Preferred methods for manufacturing the optical film structure 120 can include reactive sputtering, metal mode reactive sputtering, and PECVD processing.

[0087] The physical thickness of the optical film structure 120 can be about 100 nm to about 10 microns. For example, the thickness of the optical film structure 120 can be greater than or equal to about 200 nm, 300 nm, 325 nm, 350 nm, 375 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1 micron, 2 microns, 3 microns, 4 microns, 5 microns, 6 microns, 7 microns, or even 8 microns, and less than or equal to about 10 microns. Figures 1A to 1DIn some implementations of the illustrated transparent article 100 , the physical thickness of the optical film structure 120 is 2 microns to 4 microns, 2.25 microns to 3.75 microns, or 2.5 microns to 3.5 microns.

[0088] In some embodiments, Figures 1A to 1D As shown, the optical film structure 120 is divided into an outer structure 130a and an inner structure 130b, wherein a scratch-resistant layer 150 (as further described below) is disposed between the structures 130a and 130b. In these embodiments, the outer and inner optical film structures 130a and 130b can have the same thickness or different thicknesses, and each includes one or more layers.

[0089] Refer again Figures 1A to 1D In the transparent article 100 shown, the optical film structure 120 includes one or more scratch-resistant layers 150. For example, Figures 1A to 1D The transparent article 100 shown includes an optical film structure 120 having a scratch-resistant layer 150 disposed over a major surface 112 of a substrate 110. According to one embodiment, the scratch-resistant layer 150 may include a selected from Si u Al v O x N y 、Ta2O5、Nb2O5、AlN、AlN x 、SiAl x N y 、AlN x / SiAl x N y 、Si3N4、AlO x N y 、SiO x N y 、SiN y 、SiN x :H y , HfO2, TiO2, ZrO2, Y2O3, Al2O3, MoO3, diamond-like carbon, or a combination thereof. Exemplary materials for the scratch resistant layer 150 may include inorganic carbides, nitrides, oxides, diamond-like materials, or a combination thereof. Examples of suitable materials for the scratch resistant layer 150 include metal oxides, metal nitrides, metal oxynitrides, metal carbides, metal oxycarbides, and / or a combination thereof. Exemplary metals include B, Al, Si, Ti, V, Cr, Y, Zr, Nb, Mo, Sn, Hf, Ta, and W. Specific examples of materials that can be used for the scratch resistant layer 150 may include Al2O3, AlN, AlO x N y 、Si3N4、SiO x N y 、Si u Alv O x N y , Diamond, Diamond-like Carbon, Si x C y 、Si x O y C z 、ZrO2、TiO x N y In some implementations, the scratch resistant layer 150 may include Si3N4, SiN y 、SiO x N y In some embodiments, each of the scratch-resistant layers 150 employed in the transparent article 100 can exhibit an effective fracture toughness value greater than about 1 MPa√m and simultaneously exhibit a hardness value greater than about 10 GPa as measured by the Berkovich Hardness Test.

[0090] like Figures 1A to 1D As shown in the exemplary form of the transparent article 100 shown, each of the scratch-resistant layers 150 can be composed of any of the aforementioned materials and exhibit a refractive index (RI) greater than 1.80. In some implementations, the RI of the scratch-resistant layer 150 is greater than 1.80, greater than 1.85, or greater than 1.90. For example, the RI of the scratch-resistant layer 150 can be 1.80, 1.85, 1.9, 1.95, 2.0, 2.05, 2.10, 2.15, 2.20, 2.25, 2.3, 2.35, 2.4, 2.45, 2.5, and all RI values ​​are between the aforementioned values.

[0091] like Figures 1A to 1DAs shown in the exemplary form of the transparent article 100 shown, each of the scratch resistant layers 150 can be relatively thick (e.g., greater than or equal to about 50 nm, 75 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 325 nm, 350 nm, 375 nm, 400 nm, 425 nm, 450 nm, 475 nm, 500 nm, 525 nm, 550 nm, 575 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1 micron, 2 microns, 3 microns, 4 microns, 5 microns, 6 microns, 7 microns, or even 8 microns) compared to other layers (e.g., low RI layer 130A, high RI layer 130B, medium RI layer 130C, capping layer 131, etc.). For example, the thickness of the scratch resistant layer 150 can be about 50 nm to about 10 microns, about 100 nm to about 10 microns, about 150 nm to about 10 microns, about 500 nm to 7500 nm, about 500 nm to about 6000 nm, about 500 nm to about 5000 nm, and all thickness levels and ranges between the foregoing ranges. In other implementations, the thickness of the scratch resistant layer 150 can be about 100 nm to about 10000 nm, about 1000 nm to about 3000 nm, or about 1500 nm to about 2500 nm.

[0092] like Figures 1A to 1D As shown and as summarized above, the transparent article 100 of the present disclosure includes an optical film structure 120 having one or more of an outer structure 130a and an inner structure 130b. The optical film structure 120 includes a plurality of alternating low RI layers and high RI layers, 130A and 130B, respectively. In an embodiment, each or one of the outer structure 130a and the inner structure 130b includes a plurality of alternating low RI layers and high RI layers, 130A and 130B, respectively. In an embodiment, each or one of the outer structure 130a and the inner structure 130b includes a plurality of alternating medium RI layers and high RI layers, 130C and 130B, respectively. In some preferred implementations, the outer structure 130a includes at least one medium RI layer 130C in contact with one of the high RI layer 130B and the scratch-resistant layer 150. In some preferred implementations, as Figures 1A to 1D As shown in the exemplary form in FIG. 1 , the outer structure 130 a includes at least one outermost capping layer 131 .

[0093] According to an embodiment, each of the outer structure 130a and the inner structure 130b includes a period 132 of two or more layers (e.g., a low RI layer 130A and a high RI layer 130B; or a low RI layer 130A, a high RI layer 130B, and a low RI layer 130A; or a high RI layer 130B and a medium RI layer 130C). In addition, each of the outer and inner structures 130a, 130b of the optical film structure 120 may include a plurality of periods 132 (e.g., 1 to 30 periods, 1 to 25 periods, 1 to 20 periods, and all periods within the foregoing ranges). In addition, the number of periods 132, the number of layers of the outer and inner structures 130a, 130b, and / or the number of layers within a given period 132 may be different, or may be the same. Furthermore, in some implementations, the total amount of the plurality of alternating low RI layers 130A and high RI layers 130B and the scratch resistant layer 150 can range from 6 to 50 layers, 6 to 40 layers, 6 to 30 layers, 6 to 28 layers, 6 to 26 layers, 6 to 24 layers, 6 to 22 layers, 6 to 20 layers, 6 to 18 layers, 6 to 16 layers, 6 to 14 layers, and all ranges of layers and layer amounts between the foregoing values.

[0094] As an example, in Figures 1A to 1D In the embodiment, the period 132 of the outer structure 130a or the inner structure 130b includes a low RI layer 130A and a high RI layer 130B or a medium RI layer 130C and a high RI layer 130B. When multiple periods are included in one or both of the outer structure 130a and the inner structure 130b, the low RI layer 130A (designated as "L"), the medium RI layer 130C (designated as "M"), and the high RI layer 130B (designated as "H") can be alternated using the following order of layers: L / H / L / H..., H / L / H / L..., M / H / M / H..., H / M / H / M..., so that the low RI layer 130A and the high RI layer 130B or the medium RI layer 130C and the high RI layer 130B are alternated along the physical thickness of the outer structure 130a and the inner structure 130b of the optical film structure 120. In a preferred implementation, as Figures 1A to 1D As shown, the period 132 in the outer structure 130a is configured as H / M / H / M... above the scratch resistant layer 150; the period 132 in the inner structure 130b is configured as L / H / L / H... above the substrate 110 and below the scratch resistant layer 150.

[0095] In the implementation of the transparent product 100, as Figure 1AAs shown, the number of periods 132 of the outer structure 130a and the inner structure 130b can be configured such that the outer structure 130a includes a total of six (6) alternating layers (e.g., alternating medium RI layers 130C and high RI layers 130B); and the inner structure 130b includes at least fifteen (15) layers (e.g., alternating low RI layers 130A and high RI layers 130B, respectively). In addition, in this implementation, the outer structure 130a of the optical film structure 120 includes: a capping layer 131 (similar in structure and thickness to the low RI layer 130A) above the outer structure 130a; and a scratch-resistant layer 150 between the outer structure 130a and the inner structure 130b.

[0096] In the implementation of the transparent product 100, as Figure 1B As shown, the number of periods 132 of the outer structure 130a and the inner structure 130b can be configured such that the outer structure 130a includes a total of ten (10) alternating layers (e.g., alternating medium RI layers 130C and high RI layers 130B); and the inner structure 130b includes at least fifteen (15) layers (e.g., alternating low RI layers 130A and high RI layers 130B, respectively). In addition, in this implementation, the outer structure 130a of the optical film structure 120 includes: a capping layer 131 (similar in structure and thickness to the low RI layer 130A) above the outer structure 130a; and a scratch-resistant layer 150 between the outer structure 130a and the inner structure 130b.

[0097] In the implementation of the transparent product 100, as Figure 1C As shown, the number of periods 132 of the outer structure 130a and the inner structure 130b can be configured such that the outer structure 130a includes six (6) alternating layers (e.g., alternating medium RI layers 130C and high RI layers 130B) and additional repeated medium RI layers 130C adjacent to another medium RI layer 130C; and the inner structure 130b includes at least fifteen (15) layers (e.g., alternating low RI layers 130A and high RI layers 130B, respectively). In addition, in this implementation, the outer structure 130a of the optical film structure 120 includes: a capping layer 131 (similar in structure and thickness to the low RI layer 130A) above the outer structure 130a; and a scratch-resistant layer 150 between the outer structure 130a and the inner structure 130b.

[0098] In the implementation of the transparent product 100, as Figure 1DAs shown, the number of periods 132 of the outer structure 130a and the inner structure 130b can be configured such that the outer structure 130a includes a total of four (4) alternating layers (e.g., alternating medium RI layers 130C and high RI layers 130B); and the inner structure 130b includes at least eleven (11) layers (e.g., alternating low RI layers 130A and high RI layers 130B, respectively). In addition, in this implementation, the outer structure 130a of the optical film structure 120 includes: a capping layer 131 (similar in structure and thickness to the low RI layer 130A) above the outer structure 130a; and a scratch-resistant layer 150 between the outer structure 130a and the inner structure 130b.

[0099] According to another implementation of the transparent article 100 of the present disclosure (not shown), the number of periods 132 of the outer structure 130a and the inner structure 130b can be configured such that the outer structure 130a includes at least two (2) layers (e.g., alternating low RI layers 130A and high RI layers 130B), while the inner structure 130b includes at least five (5) layers (e.g., two periods 132 of alternating low RI layers 130A and high RI layers 130B, and an additional period 132 of three (3) layers of alternating low RI / high RI / low RI layers 130A, 130B). In addition, in this implementation, the optical film structure 120 includes: a capping layer 131 (similar in structure and thickness to the low RI layer 130A) above the outer structure 130a; and a scratch-resistant layer 150 between the outer and inner structures 130a and 130b. In an embodiment of this implementation, the transparent article 100 does not include any medium RI layer 130C.

[0100] according to Figures 1A to 1D In some embodiments of the transparent article 100 shown, the outermost capping layer 131 and the outer structure 130a of the optical film structure 120 may not be exposed, but have a top coating 140 disposed thereon. In some implementations of the transparent article 100, the scratch-resistant layer 150 and each high RI layer 130B of the optical film structure 120, as well as the outer structure 130a and the inner structure 130b include nitrides, silicon-containing nitrides (e.g., SiN y , Si3N4), oxynitride, or silicon-containing oxynitride (e.g., SiAl x O y N z or SiO x N y In addition, according to some embodiments, each low RI layer 130A of the optical film structure 120, as well as the outer structure 130a and the inner structure 130b, includes an oxide, a silicon-containing oxide (eg, SiO2, SiO x , or SiO2 doped with Al, N or F), or silicon-containing oxynitride (e.g., SiO x Ny In addition, according to some embodiments, each medium RI layer 130C of the optical film structure 120 and the outer structure 130a and the inner structure 130b include oxynitride or silicon-containing oxynitride (eg, SiAl x O y N z or SiO x N y ).

[0101] exist Figures 1A to 1D In one or more embodiments of the transparent article 100 shown, when used with the low RI layer 130A and / or the capping layer 131, the refractive index range included by the term "low RI" is less than 1.55, about 1.3 to about 1.55, and all refractive indices within these ranges. In one or more embodiments, when used with the medium RI layer 130C, the refractive index range included by the term "medium RI" is 1.55 to 1.80, 1.56 to 1.80, 1.6 to 1.75, and all refractive indices within these ranges. In one or more embodiments, when used with the high RI layer 130B and / or the scratch-resistant layer 150, the refractive index range included by the term "high RI" is greater than 1.80, greater than 1.90, about 1.8 to about 2.5, about 1.8 to about 2.3, or about 1.90 to about 2.5, and all refractive indices between these ranges. In addition, in a specific implementation, the medium RI layer of the transparent article 100 of the present disclosure (see, e.g. Figures 1A to 1D ) may include a refractive index of 1.55 to 1.90, or 1.55 to 1.85, and values ​​between all such ranges, which may overlap with the refractive index of the high RI layer 130B (e.g., having a refractive index greater than 1.80) of the optical film structure 120, or may not overlap with the refractive index of the high RI layer 130B (e.g., having a refractive index greater than 1.90). In one or more embodiments, the difference in refractive index of each of the low RI layer 130A (and / or capping layer 131), the medium RI layer 130C, and / or the high RI layer 130B (and / or the scratch resistant layer 150) may be about 0.01 or greater, about 0.05 or greater, about 0.1 or greater, or even about 0.2 or greater.

[0102] Applies to Figures 1A to 1D Exemplary materials for the outer and inner structures 130a and 130b of the optical film structure 120 of the transparent article 100 shown include, but are not limited to, SiO2, SiO x 、Al2O3、SiAl x O y 、GeO2、SiO、AlO x N y 、AlN、AlN x、SiAl x N y 、SiN x 、SiO x N y 、SiAl x O y N z , Ta2O5, Nb2O5, TiO2, ZrO2, TiN, MgO, MgF2, BaF2, CaF2, SnO2, HfO2, Y2O3, MoO3, DyF3, YbF3, YF3, CeF3, diamond-like carbon, and combinations thereof. Some examples of suitable materials for the low RI layer 130A and the outermost capping layer 131 include, but are not limited to, SiO2, SiO x 、Al2O3、SiAl x O y 、GeO2、SiO、AlO x N y 、SiO x N y 、SiAl x O y N z 、MgO、MgAl x O y , MgF2, BaF2, CaF2, DyF3, YbF3, YF3 and CeF3. In some implementations of the transparent article 100, each of the low RI layers 130A thereof includes a silicon-containing oxide (e.g., SiO2 or SiO x ) or silicon-containing oxynitride (e.g., SiO x N y The nitrogen content of the material used for the low RI layer 130A may be minimized (e.g., in a SiO x N y , Al2O3 and MgAl x O y Some examples of suitable materials for the high RI layer 130B include, but are not limited to, SiAl x O y N z 、Ta2O5、Nb2O5、AlN、AlN x 、SiAl x N y 、AlN x / SiAl x N y 、Si3N4、AlO x N y 、SiO x N y 、SiN y 、SiN x :Hy , HfO2, TiO2, ZrO2, Y2O3, Al2O3, MoO3 and diamond-like carbon. Some examples of suitable materials for the medium RI layer 130C include, but are not limited to, SiAl x O y N z 、AlO x N y 、SiO x N y , HfO2, Y2O3 and Al2O3. According to some implementations, each high RI layer 130B of the outer structure 130a and the inner structure 130b includes a silicon-containing nitride or a silicon-containing oxynitride (e.g., Si3N4, SiN y , or SiO x N y ). In one or more embodiments, each of the high RI layers 130B may have a high hardness (eg, a hardness greater than 8 GPa), and the high RI materials listed above may include high hardness and / or scratch resistance.

[0103] The oxygen content of the material used for the high RI layer 130B can be minimized (especially in SiN y In addition, the exemplary SiO x N y The high RI material may include about 0 atomic % to about 20 atomic % oxygen or about 5 atomic % to about 15 atomic % oxygen, and 30 atomic % to about 50 atomic % nitrogen. The foregoing materials may be hydrogenated up to about 30 weight %. In the case where a material having a medium refractive index is desired as the medium RI layer 130C, some embodiments may utilize SiO x N y (eg, having relatively low levels of nitrogen (eg, less than 3%).) It should be understood that the scratch resistant layer 150 can include any of the materials disclosed as suitable for use in the high RI layer 130B.

[0104] In one or more embodiments of the transparent article 100, the optical film structure 120 includes a scratch-resistant layer 150 that can be integrated as a high RI layer 130B, and one or more low RI layers 130A, high RI layers 130B, and / or capping layers 131 can be positioned above the scratch-resistant layer 150. In addition, with respect to the scratch-resistant layer 150, as Figures 1A to 1D As shown, an optional top coating 140 may also be positioned over layer 150. The scratch resistant layer 150 may alternatively be defined as the thickest high RI layer 130B in the entire optical film structure 120 and / or the outer and inner structures 130a, 130b.

[0105] Without being bound by theory, it is believed that when one or more medium RI layers 130C (e.g., comprising SiOx N y ) is placed in direct contact with one or more high RI layers 130B (e.g., SiO x N y 、SiN y )hour, Figures 1A to 1D The transparent article 100 shown can exhibit increased hardness at low indentation depths (e.g., 100-125 nm); the sum of the physical thicknesses of the low RI layer 130A and / or the capping layer 131 in the outer structure 130a is minimized; and the total thickness of the layers in the outer structure 130A is minimized. In some implementations, such as Figure 1C As shown in the illustrated article 100, additional repeating medium RI layers 130C can be deployed in the outer structure 130a in contact with another medium RI layer 130C, and further increase the hardness at a shallow depth within the optical film structure 120. According to some implementations, the sum of the physical thicknesses of the low RI layers 130A and / or the capping layer 131 in the outer structure 130a is configured to be less than about 275 nm, less than about 250 nm, less than about 225 nm, less than about 200 nm, less than about 175 nm, less than about 150 nm, less than about 125 nm, less than 110 nm, less than 100 nm, less than 90 nm, less than 75 nm, less than 65 nm, less than 50 nm, or even less than 25 nm, and further increase the hardness at a shallow depth within the optical film structure 120. For example, the sum of the physical thicknesses of the low RI layer 130A and / or the capping layer 131 in the outer structure 130a can be 250nm, 225nm, 200nm, 175nm, 150nm, 125nm, 120nm, 110nm, 100nm, 90nm, 80nm, 70nm, 60nm, 50nm, 40nm, 30nm, 20nm, 10nm, and all total thickness values ​​between the aforementioned values. In addition, in some implementations, Figures 1A to 1D The total physical thickness of the layers in the outer structure 130a of the illustrated transparent article 100 can be configured to be less than 500nm, less than 450nm, less than 400nm, less than 350nm, less than 300nm, less than 250nm, less than 200nm, or even less than 150nm, as well as all total thickness values ​​within the foregoing ranges.

[0106] Refer again Figures 1A to 1D 100, these articles can also show a correlation between the achievable reflectivity level in the outer structure 130a of the optical film structure 120 and the amount of low RI material (e.g., the volume of the low RI layer 130A). Thus, for an optical film structure 120 having a photopic average first surface reflectivity value of about 3.5-7%, all low RI layers 130A (e.g., SiO2 or SiOx N y , where the sum of the physical thicknesses of the outer structure 130a (e.g., SiO2 or SiO2) < 1.55) can be limited to about 75 nm or less, and in the best case, less than 20 nm, resulting in particularly high hardness at a shallow indentation depth of about 125 nm. For those embodiments of the article 100 that achieve a lower photopic average first surface reflectance value of 1-2.5%, a first surface reflectance at a wavelength of 940 nm of less than 4%, and an average reflectance of 1000-1700 nm of less than 10.5% (including some practical examples below), all low RI layers 130A (e.g., SiO2 or SiO2) in the outer structure 130a are preferably less than 10% of the first surface reflectance. x N y , where n<1.55) can be limited to about 200 nm or less, and in the best case, less than 65 nm.

[0107] Refer again Figures 1A to 1D As shown in the transparent article 100, as measured by the Berkovich Hardness Test, according to some embodiments, each of the low RI layers 130A of the optical film structure 120 can have a hardness greater than 5 GPa, each of the medium RI layers 130C can have a hardness greater than 10 GPa, and each of the high RI layer 130B and the scratch resistant layer 150 can have a hardness greater than 12 GPa. Without being bound by theory, the use of the medium RI layer 130C helps to establish high hardness at shallow depths through two mechanisms: 1) reducing the amount of low RI and low hardness material in the outer structure 130a of the optical film structure 120 (e.g., minimizing the volume of the low RI layer 130A; and 2) including the relatively higher hardness of the medium RI material employed by the medium RI layer 130C (compared to the low RI material of the low RI layer 130A replaced by the medium RI material in the optical film structure 120).

[0108] According to some embodiments of the transparent article 100, increased hardness may be exhibited at the indentation depth when a relatively small amount of material is deposited over the scratch resistant layer 150. However, including low RI and high RI layers 130A, 130B over the scratch resistant layer 150 may enhance the optical properties of the transparent article 100. In some embodiments, relatively few layers (e.g., only 1, 2, 3, 4, or 5 layers) may be positioned over the scratch resistant layer 150, and each of these layers may be relatively thin (e.g., less than 100 nm, less than 75 nm, less than 50 nm, or even less than 25 nm).

[0109] In one or more embodiments, Figures 1A to 1DThe transparent article 100 shown may include one or more additional top coatings 140 disposed on the outer structure 130a of the optical film structure 120. In one or more embodiments, the additional top coating 140 may include an easy-to-clean coating. U.S. Patent Application Publication No. 2014 / 0113083, entitled "Process for Making of Glass Articles with Optical and Easy-to-Clean Coatings" published on April 24, 2014, describes an example of a suitable easy-to-clean coating, which is incorporated herein by reference in its entirety. The easy-to-clean coating may have a thickness ranging from about 5 nm to about 50 nm and may include known materials (e.g., fluorinated silanes). The easy-to-clean coating may alternatively or additionally include a low-friction coating or surface processing. Exemplary low-friction coating materials may include diamond-like carbon, silanes (e.g., fluorinated silanes), phosphonates, olefins, and alkynes. In some embodiments, the thickness of the easy-to-clean coating of the top coating 140 can range from about 1 nm to about 40 nm, about 1 nm to about 30 nm, about 1 nm to about 25 nm, about 1 nm to about 20 nm, about 1 nm to about 15 nm, about 1 nm to about 10 nm, about 5 nm to about 50 nm, about 10 nm to about 50 nm, about 15 nm to about 50 nm, about 7 nm to about 20 nm, about 7 nm to about 15 nm, about 7 nm to about 12 nm, about 7 nm to about 10 nm, about 1 nm to about 90 nm, about 5 nm to about 90 nm, about 10 nm to about 90 nm, or about 5 nm to about 100 nm, and all ranges and sub-ranges therebetween.

[0110] The top coating 140 may include one or more scratch-resistant layers, the one or more scratch-resistant layers including any material disclosed as suitable for the scratch-resistant layer 150. In some embodiments, the additional top coating 140 includes a combination of an easy-to-clean material and a scratch-resistant material. In one example, the combination includes an easy-to-clean material and diamond-like carbon. The thickness of such an additional top coating 140 may range from about 5 nm to about 20 nm. The components of the additional coating 140 may be provided in separate layers. For example, diamond-like carbon may be provided as a first layer, and the easy-to-clean material may be provided as a second layer on the first layer of diamond-like carbon. The thickness of the first layer and the second layer may range from the range provided above for the additional coating. For example, the thickness of the first layer of diamond-like carbon may be about 1 nm to about 20 nm or about 4 nm to about 15 nm (or more specifically about 10 nm), and the thickness of the second layer of the easy-to-clean material may be about 1 nm to about 10 nm (or more specifically about 6 nm). The diamond-like coating may include tetrahedral amorphous carbon (Ta-C), Ta-C:H, and / or aCH.

[0111] according to Figures 1A to 1D In the embodiment of the transparent article 100 shown, the physical thickness of each of the high RI layers 130B of the outer structure 130a and the inner structure 130b of the optical film structure 120 can range from about 5 nm to 5000 nm, 5 nm to 2000 nm, about 5 nm to 1500 nm, about 5 nm to 1000 nm, and all thicknesses and thickness ranges between these values. For example, the physical thickness of these high RI layers 130B can be 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 250 nm, 500 nm, 750 nm, 1000 nm, 1250 nm, 1500 nm, 1750 nm, 2000 nm, 2500 nm, 3000 nm, 4000 nm, 5000 nm, and all thickness values ​​between these levels. In addition, the physical thickness of each of the high RI layers 130B of the inner structure 130b can range from about 5 nm to 500 nm, about 5 nm to 400 nm, about 5 nm to 300 nm, and all thicknesses and thickness ranges between these values. As an example, the physical thickness of each of these high RI layers 130B can be 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, and all thickness values ​​between these levels.

[0112] In addition, according to Figures 1A to 1D In some embodiments of the transparent article 100 shown, the physical thickness of each of the low RI layer 130A and the medium RI layer 130C of the outer structure 130a and the inner structure 130b can be about 5nm to 300nm, about 5nm to 250nm, about 5nm to 200nm, and all thicknesses and thickness ranges between these values. For example, the physical thickness of each of these low RI layers 130A can be 5nm, 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 150nm, 200nm, 250nm, 300nm, and all thickness values ​​between these levels.

[0113] In one or more embodiments, at least one of the layers (e.g., low RI layer 130A, high RI layer 130B, and / or medium RI layer 130C) of the outer structure 130a and the inner structure 130b of the optical film structure 120 may include a specific optical thickness (or optical thickness range). As used herein, the term "optical thickness" refers to the product of the physical thickness of the layer and the refractive index. In one or more embodiments, the optical thickness of at least one of the layers of the outer and inner structures 130a, 130b may range from about 2nm to about 200nm, from about 10nm to about 100nm, from about 15nm to about 100nm, from about 15nm to about 500nm, or from about 15nm to about 5000nm. In some embodiments, the optical thickness of each of all the layers of the outer and inner structures 130a, 130b may range from about 2nm to about 200nm, from about 10nm to about 100nm, from about 15nm to about 100nm, from about 15nm to about 500nm, or from about 15nm to about 5000nm. In some embodiments, at least one layer of one or both of the outer and inner structures 130a, 130b has an optical thickness of about 50 nm or greater. In some embodiments, the optical thickness of each of the low RI layer 130A and / or the medium RI layer 130C ranges from about 2 nm to about 200 nm, from about 10 nm to about 100 nm, from about 15 nm to about 100 nm, from about 15 nm to about 500 nm, or from about 15 nm to about 5000 nm. In some embodiments, the optical thickness of each of the high RI layers 130B ranges from about 2 nm to about 200 nm, from about 10 nm to about 100 nm, from about 15 nm to about 100 nm, from about 15 nm to about 500 nm, or from about 15 nm to about 5000 nm. In some embodiments, the scratch resistant layer 150 is the thickest layer in the optical film structure 120 and / or has a higher RI than any other layer in the film structure.

[0114] Figures 1A to 1DThe substrate 110 of the transparent article 100 shown may include an inorganic material having an amorphous and a crystalline portion. The substrate 110 may be formed of an artificial material and / or a naturally occurring material (e.g., quartz). In some specific embodiments, the substrate 110 may specifically exclude polymers, plastics, and / or metal substrates. The feature of the substrate 110 may be a substrate including an alkali (i.e., the substrate includes one or more alkalis). In one or more embodiments, the refractive index exhibited by the substrate 110 ranges from about 1.5 to about 1.6. In a specific embodiment, the average failure strain of the substrate 110 (e.g., a glass-ceramic substrate) exhibited at the surface on one or more opposing major surfaces 112, 114 measured using the ROR test using at least 5, at least 10, at least 15, or at least 20 samples to determine the average failure strain value can be 0.5% or more, 0.6% or more, 0.7% or more, 0.8% or more, 0.9% or more, 1% or more, 1.1% or more, 1.2% or more, 1.3% or more, 1.4% or more, 1.5% or more, or even 2% or more. In a specific embodiment, the average failure strain of the substrate 110 exhibited at the surface on one or more opposing major surfaces 112, 114 is about 1.2%, about 1.4%, about 1.6%, about 1.8%, about 2.2%, about 2.4%, about 2.6%, about 2.8%, or about 3% or more.

[0115] The term "failure strain" refers to the strain at which cracks propagate in the outer structure 130a or inner structure 130b, substrate 110, or both of the optical film structure 120 without applying an additional load, which typically causes catastrophic damage in a given material, layer, or film as defined herein, and even bridges to another material, layer, or film. In other words, in the absence of a rupture of substrate 110, the rupture of the optical film structure 120 (i.e., including the outer structure 130a and / or the inner structure 130b) constitutes a failure, and the rupture of substrate 110 also constitutes a failure. When used in conjunction with the average failure strain or any other property, the term "average" is based on the mathematical average of the measurement of such properties for 5 samples. Typically, crack initiation strain measurements are repeatable under normal laboratory conditions, and the standard deviation of crack initiation strains measured in multiple samples may be as low as 0.01% of the observed strain. The average failure strain used herein is measured using the ROR test. However, unless otherwise noted, the failure strain measurements described herein refer to measurements from ring-to-ring testing, as described in International Publication No. WO 2018 / 125676, entitled “Coated Articles with Optical Coatings Having Residual Compressive Stress,” published on July 5, 2018, and incorporated herein by reference in its entirety.

[0116] The elastic modulus (or Young's modulus) exhibited by a suitable substrate 110 (e.g., a glass-ceramic substrate) may range from about 60 GPa to about 130 GPa. In some cases, the elastic modulus of the substrate 110 may range from about 70 GPa to about 120 GPa, from about 80 GPa to about 110 GPa, from about 80 GPa to about 100 GPa, from about 80 GPa to about 90 GPa, from about 85 GPa to about 110 GPa, from about 85 GPa to about 105 GPa, from about 85 GPa to about 100 GPa, from about 85 GPa to about 95 GPa, and all ranges and sub-ranges therebetween (e.g., about 103 GPa). In some implementations, the elastic modulus of the substrate 110 may be greater than 85 GPa, greater than 90 GPa, greater than 95 GPa, or even greater than 100 GPa. In some examples, the Young's modulus can be measured by acoustic resonance (ASTM E1875), resonant ultrasonic spectroscopy, or nanoindentation using a Berkovich indenter. In addition, the shear modulus exhibited by a suitable substrate 110 (e.g., a glass ceramic substrate) may range from about 20 GPa to about 60 GPa, from about 25 GPa to about 55 GPa, from about 30 GPa to about 50 GPa, from about 35 GPa to about 50 GPa, and shear modulus ranges and sub-ranges therebetween (e.g., about 43 GPa). In some implementations, the shear modulus of the substrate 110 may be greater than 35 GPa, or even greater than 40 GPa. In addition, in some cases, the fracture toughness exhibited by the substrate 110 may be greater than 0.8 MPa·√m, greater than 0.9 MPa·√m, greater than 1 MPa·√m, or even greater than 1.1 MPa·√m (e.g., about 1.15 MPa·√m).

[0117] In one or more embodiments, the amorphous substrate 110 may include glass, which may be strengthened or unstrengthened. Examples of suitable glass include soda-lime glass, alkali aluminosilicate glass, alkali-containing borosilicate glass, and alkali aluminoborosilicate glass. In some variations, the glass may be free of lithium. In one or more alternative embodiments, the substrate 110 may include a crystalline substrate (e.g., a glass-ceramic substrate (which may be strengthened or unstrengthened)), or may include a single crystal structure (e.g., sapphire). In one or more specific embodiments, the substrate 110 includes an amorphous base (e.g., glass) with a crystalline coating (e.g., a sapphire layer, a polycrystalline alumina layer, and / or a spinel (MgAl2O4) layer).

[0118] In one or more embodiments, the substrate 110 includes one or more glass-ceramic materials and may be strengthened or unstrengthened. In one or more embodiments, the substrate 110 as a glass-ceramic material may include one or more crystalline phases (e.g., lithium disilicate, lithium metasilicate, petalite, beta quartz, and / or beta spodumene that may be combined with residual glass in the structure). In an embodiment, the substrate 110 includes a disilicate phase. In another implementation, the substrate 110 includes a disilicate phase and a petalite phase. According to an embodiment, the substrate 110 has a crystallinity of at least 40% by weight. In some implementations, the crystallinity of the substrate 110 is at least about 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, or more (by weight), wherein the residue is a glass phase. In addition, according to some embodiments, each of the crystalline phases of the substrate 110 has an average crystal size of less than 100 nm, less than 75 nm, less than 50 nm, less than 40 nm, less than 30 nm, and all crystal sizes within or less than these levels. According to an exemplary embodiment, the substrate 110 includes lithium disilicate and petalite phases, with 40% by weight lithium disilicate, 45% by weight petalite, and the remainder is residual glass (i.e., about 85% crystalline, and about 15% residual amorphous / glass); each crystalline phase has a majority of crystals with an average crystal size in the range of 10 nm to 50 nm.

[0119] In the transparent article 100 of the present disclosure (see for example Figures 1A to 1D ) can exhibit a refractive index that is higher than the refractive index of a conventional glass substrate or a strengthened glass substrate. For example, the refractive index of the substrate 110 can range from about 1.52 to 1.65, about 1.52 to 1.64, about 1.52 to 1.62, or about 1.52 to 1.60, as well as all refractive indices within the foregoing ranges (e.g., measured at a visible wavelength of 589 nm). Therefore, conventional optical coatings that are typically optimized for glass substrates and their refractive index ranges are not necessarily applicable to the substrate 110 of the transparent article 100 of the present disclosure that includes a glass-ceramic material. More specifically, the layer of the optical film structure 120 between the substrate 110 and the scratch-resistant layer 150 can be modified to achieve low reflectivity and low color generated by the transition zone between the glass-ceramic substrate 110 and the scratch-resistant layer 150. This layer redesign requirement can also be described as optical impedance matching between the substrate 110 and the scratch-resistant layer 150.

[0120] Depending on the implementation, the substrate 110 is substantially optically clear, transparent, and free of light scattering. In such an embodiment, the average light transmittance exhibited by the substrate 110 over the optical wavelength interval may be about 80% or greater, about 81% or greater, about 82% or greater, about 83% or greater, about 84% or greater, about 85% or greater, about 86% or greater, about 87% or greater, about 88% or greater, about 89% or greater, about 90% or greater, about 91% or greater, about 92% or greater, about 93% or greater, or even about 94% or greater. In some embodiments, these light reflection values ​​and light transmission values ​​may be total reflectance or total transmittance (considering the reflectance or transmittance on both major surfaces 112, 114 of the substrate 110), or may be observed on a single side of the substrate 110 (not considering the opposite surface 114, but only measuring on the major surface 112). Unless otherwise noted, the average reflectivity or transmittance of substrate 110 alone is measured at an incident illumination angle of approximately 0 degrees relative to major surface 112 (however, such measurements may be provided at incident illumination angles of 45 degrees or 60 degrees).

[0121] Additionally or alternatively, the physical thickness of the substrate 110 may vary with one or more of its dimensions for aesthetic and / or functional reasons. For example, the edges of the substrate 110 may be thicker than the more central regions of the substrate 110. In other implementations, the edges of the substrate 110 may be thinner than the more central regions of the substrate 110. Furthermore, in some embodiments, portions of the substrate 110 (e.g., edge portions) may be non-planar (e.g., tilted, chamfered, curved, etc.). The length, width, and physical thickness dimensions of the substrate 110 may also vary depending on the application or use of the article 100.

[0122] Various different processes may be used to provide the substrate 110. For example, where the substrate 110 includes an amorphous portion or phase (eg, glass), various formation methods may include a float glass process and down-draw processes (eg, fusion draw and slot draw).

[0123] Once formed, substrate 110 may be strengthened to form a strengthened substrate (eg, chemical strengthening via an ion exchange process, thermal tempering, and / or exploiting mismatches in coefficients of thermal expansion between portions of the substrate to create compressive stress and a central tension region).

[0124] In the case of chemically strengthening the substrate 110 by an ion exchange process, the ions in the surface layer of the substrate 110 are replaced or exchanged by larger ions having the same valence or oxidation state. The ion exchange process is generally performed by immersing the substrate in a molten salt bath containing larger ions to exchange with smaller ions in the substrate. It should be understood by those skilled in the art that the parameters for the ion exchange process include, but are not limited to, the composition and temperature of the bath, the immersion time, the number of times the substrate 110 is immersed in the salt bath (or baths), the use of multiple salt baths, additional steps (e.g., annealing, cleaning, and the like), and are generally determined by the composition of the substrate 110 and the desired compressive stress (CS) depth (or depth of layer) of the compressive stress layer of the substrate 110 caused by the strengthening operation. For example, ion exchange of an alkali metal-containing substrate can be achieved by immersing in at least one molten bath containing a salt (e.g., but not limited to, nitrates, sulfates, chlorides of larger alkali metal ions). The temperature of the molten salt bath is generally in the range of about 380° C. to about 530° C., and the immersion time is in the range of about 15 minutes to about 40 hours. However, temperatures and immersion times different from those described above may also be used.

[0125] The degree of chemical strengthening achieved by ion exchange can be quantified based on the parameters of central tension (CT), surface CS, depth of compression (DOC) (i.e., the point at which the stress state in the substrate changes from compression to tension) and depth of potassium ion layer (DOL). Compressive stress (including surface CS) is measured by a surface stress meter (FSM) using a commercially available instrument (such as FSM-6000 manufactured by Orihara Industrial Co., Ltd (Japan)). Surface stress measurement depends on the accurate measurement of the stress optical coefficient (SOC) related to the birefringence of glass-ceramic materials. Then, SOC is measured according to the procedure C (glass dish method) described in ASTM standard C770-16 entitled "Standard Test Method for Measurement of Glass Stress-Optical Coefficient", the contents of which are incorporated herein by reference as a whole. Refractive near field (RNF) method or scattered light polarizer (SCALP) technology can be used to measure stress distribution curves. When using the RNF method to measure the stress distribution curve, the maximum CT value provided by SCALP is used in the RNF method. More specifically, the stress profile measured by the RNF is force balanced and calibrated to the maximum CT value provided by the SCALP measurement. The RNF method is described in U.S. Patent No. 8,854,623 entitled "Systems and Methods for Measuring a Profile Characteristic of a Glass Sample," which is incorporated herein by reference in its entirety. More specifically, the RNF method includes placing a glass ceramic article adjacent to a reference block, generating a polarization-switched beam that switches between orthogonal polarizations at a rate between 1 Hz and 50 Hz, measuring the amount of power in the polarization-switched beam, and generating a polarization-switched reference signal, wherein the measured amount of power in each of the orthogonal polarizations is within 50% of each other. The method further includes transmitting the polarization-switched beam into the glass sample through the glass sample and the reference block at different depths, and then relaying the transmitted polarization-switched beam to a signal photodetector using a relay optical system, wherein the signal photodetector generates a polarization-switched detector signal. The method also includes dividing the detector signal by the reference signal to form a normalized detector signal, and determining a profile characteristic of the glass-ceramic sample from the normalized detector signal.The maximum CT value is measured using a scattered light polariscope (SCALP) technique known in the art.

[0126] In one embodiment of the transparent article 100 (see Figures 1A to 1D), the surface CS of the strengthening substrate 110 can be 200 MPa or greater, 250 MPa or greater, 300 MPa or greater, or 350 MPa or greater. In another implementation, the residual surface compressive stress (CS) exhibited by the strengthening substrate can be about 200 MPa to about 1200 MPa, about 200 MPa to about 1000 MPa, about 200 MPa to about 800 MPa, about 200 MPa to about 600 MPa, about 200 MPa to about 500 MPa, about 200 MPa to about 400 MPa, about 225 MPa to about 400 MPa, about 250 MPa to about 400 MPa, and all CS sub-ranges and values ​​within the foregoing ranges. The DOL of the strengthening substrate 110 can be 1 μm to 5 μm, 1 μm to 10 μm, or 1 μm to 15 μm, and / or the central tension (CT) can be 50 MPa or more, 75 MPa or more, 100 MPa or more, 125 MPa or more (e.g., 80 MPa, 90 MPa, or 100 MPa or more), but less than 250 MPa (e.g., 200 MPa or less, 175 MPa or less, 150 MPa or less, etc.). In such an implementation of the transparent article 100 having a substrate 110 (the CT of the substrate 110 is about 50 MPa to about 200 MPa, or 80 MPa to about 200 MPa), the thickness of the substrate 110 should be limited to about 0.6 mm or less to ensure that the substrate is not brittle. For implementations employing thicker substrates (e.g., having thicknesses of up to 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, or even up to 1.5 mm), the upper limit of CT should be kept below the 200 MPa level to ensure that the substrate does not become brittle (e.g., 150 MPa for a thickness of 0.8 mm).

[0127] The depth of compression (DOC) of the substrate 110 may be 0.1·t (the thickness of the substrate (t)) to about 0.25·t (e.g., about 0.15·t to about 0.25·t, or about 0.15·t to about 0.20·t, and all DOC values ​​between the foregoing ranges). For example, the DOC of the substrate 110 may be 20% of the thickness of the substrate, compared to 15% or less of the DOC of the ion-exchanged glass substrate. In some implementations, the DOC of the substrate 110 may be about 5 μm to about 150 μm, about 5 μm to about 125 μm, about 5 μm to about 100 μm, and all DOC values ​​between the foregoing ranges. In some embodiments, the depth of compression of the substrate material may be about 8% to about 20% of the thickness of the substrate 110. It should be noted that the foregoing DOC values ​​are measured from one of the major surfaces 112 or 114 of the substrate 110. Thus, for a 600 μm thick substrate 110, the DOC may be 20% of the thickness of the substrate, about 120 μm from each of the major surfaces 112, 114 of the substrate 110, or a total of 240 μm for the entire substrate. In one or more specific embodiments, the strengthened substrate 110 may exhibit one or more of the following mechanical properties: a surface CS of about 200 MPa to about 400 MPa, a DOL greater than 30 μm, a DOC of about 0.08·t to about 0.25·t, and a CT of about 80 MPa to about 200 MPa.

[0128] According to an embodiment of the present disclosure, the maximum hardness exhibited by the substrate 110 (on which the optical film structure 120 for measurement purposes is not disposed) measured by the Berkovich hardness test over an indentation depth in the range of 100 nm to about 500 nm in the substrate 110 may be 8.5 GPa or greater, 9 GPa or greater, or 9.5 GPa or greater (or even greater than 10 GPa in some cases). For example, the maximum hardness exhibited by the substrate 110 measured by the Berkovich hardness test over an indentation depth in the range of 100 nm to about 500 nm in the substrate 110 may be 8.5 GPa, 8.75 GPa, 9 GPa, 9.25 GPa, 9.5 GPa, 9.75 GPa, 10 GPa, and higher hardness levels. In addition, the Vickers hardness exhibited by the substrate 110 of the present disclosure measured using a 200 g load may be greater than 700, or even greater than 800. Furthermore, the substrate 110 of the present disclosure may exhibit a Mohs hardness greater than 6.5, or even greater than 7.

[0129] As previously described, the substrate 110 may be non-strengthened or strengthened and have a suitable composition to support strengthening. Examples of suitable glass-ceramics for the substrate 110 may include Li2O-Al2O3-SiO2 system (i.e., LAS system) glass-ceramics, MgO-Al2O3-SiO2 system (i.e., MAS system) glass-ceramics, and / or glass-ceramics including a main crystalline phase, the main crystalline phase including β-quartz solid solution, β-spodumene, cordierite, and lithium disilicate. Such a glass-ceramic substrate as the substrate 110 may be strengthened using the chemical strengthening process disclosed herein. In one or more embodiments, the MAS system glass-ceramic substrate may be strengthened in a Li2SO4 molten salt, and the 2Li + With Mg 2+ The exchange occurs.

[0130] According to some embodiments of the transparent product 100 of the present disclosure, the substrate 110 may be a glass-ceramic material of a LAS system having the following composition: 70-80% SiO2, 5-10% Al2O3, 10-15% Li2O, 0.01-1% Na2O, 0.01-1% K2O, 0.1-5% P2O5, and 0.1-7% ZrO2 (based on the weight % of the oxide). In some implementations of the transparent product 100 of the present disclosure, the substrate 110 may be a LAS system having the following composition: 70-80% SiO2, 5-10% Al2O3, 10-15% Li2O, 0.01-1% Na2O, 0.01-1% K2O, 0.1-5% P2O5, and 0.1-5% ZrO2 (based on the weight % of the oxide). According to another embodiment, the substrate 110 may be a LAS system having the following composition: 70-75% SiO2, 5-10% Al2O3, 10-15% Li2O, 0.05-1% Na2O, 0.1-1% K2O, 1-5% P2O5, 2-7% ZrO2, and 0.1-2% CaO (based on the weight % of the oxides). According to a further embodiment, the substrate 110 may have the following composition: 71-72% SiO2, 6-8% Al2O3, 10-13% Li2O, 0.05-0.5% Na2O, 0.1-0.5% K2O, 1.5-4% P2O5, 4-7% ZrO2, and 0.5-1.5% CaO (based on the weight % of the oxides). Generally speaking, these compositions of the substrate 110 are advantageous for the transparent article 100 of the present disclosure, because low haze levels, high transparency, high fracture toughness and high elastic modulus are exhibited, and ion exchangeability is possible.

[0131] According to an embodiment of the transparent article 100, a substrate 110 as a glass-ceramic material is selected using any of the compositions of the present disclosure, and further processed to a crystallinity level of the present disclosure to exhibit a combination of high fracture toughness (e.g., greater than 1 MPa·√m) and high elastic modulus (e.g., greater than 100 GPa). These mechanical properties can be derived from the presence of a crystalline phase (e.g., lithium disilicate phase) exhibiting a relatively high modulus; and the microstructure of the final substrate 110 including some residual glass phase. It should be noted that the residual glass phase (and its alkali-containing composition) ensures that the substrate 110 can be ion-exchanged to a high level of central tension (CT) (e.g., greater than 80 MPa) and compressive stress (CS) (e.g., greater than 200 MPa). In addition, ceramicization (i.e., post-melt treatment, thermal processing conditions) can be selected to minimize the grain size of the substrate 110, so that the grain size is smaller than the wavelength of visible light, thereby ensuring that the substrate 110 and the article 100 are transparent or substantially transparent. Finally, the composition and processing of the substrate 110 comprising the glass-ceramic material is advantageously selected to achieve a balance of high fracture toughness, high elastic modulus, and optical clarity to ensure that the transparent article 100 exhibits this balance of mechanical and optical properties, as well as a surprising level of damage resistance, as a result of employing these substrates 110 and optical film structures 120.

[0132] The substrate 110 according to one or more embodiments may have a physical thickness of about 100 μm to about 5 mm in various portions of the substrate 110. For example, the physical thickness of the exemplary substrate 110 ranges from about 100 μm to about 500 μm (e.g., 100, 200, 300, 400, or 500 μm), from about 500 μm to about 1000 μm (e.g., 500, 600, 700, 800, 900, or 1000 μm), and from about 500 μm to about 1500 μm (e.g., 500, 750, 1000, 1250, or 1500 μm). In some implementations, the physical thickness of the substrate 110 may be greater than about 1 mm (e.g., about 2, 3, 4, or 5 mm). In one or more specific embodiments, the physical thickness of the substrate 110 may be 2 mm or less, or 1 mm or less. The substrate 110 may be acid polished or otherwise processed to remove or reduce the effects of surface defects.

[0133] about Figures 1A to 1DThe hardness of the transparent article 100 shown, typically in a nanoindentation measurement method where the coating is harder than the underlying substrate (e.g., by using a Berkovich indenter), the measured hardness may initially appear to increase due to the development of a plastic zone at a shallow indentation depth (e.g., less than 25 nm or less than 50 nm), and then increase and reach a maximum or plateau at a deeper indentation depth (e.g., 50 nm to about 500 nm or 1000 nm). Thereafter, the hardness begins to decrease at yet deeper indentation depths due to the influence of the underlying substrate. The same effect can be seen in the case of using a substrate 110 having a greater hardness than the optical film structure 120; however, the hardness at deeper indentation depths will increase due to the influence of the underlying substrate.

[0134] More about Figures 1A to 1D The transparent article 100 shown, can select the indentation depth range and the hardness value within certain indentation depth ranges to identify the specific hardness response of the optical film structure 120 described herein and its outer and inner structures 130a, 130b layers, without being affected by the underlying substrate 110. When the Berkovich indenter is used to measure the hardness of the optical film structure 120 (when set on the substrate 110), the permanent deformation area (plastic zone) of the material is associated with the hardness of the material. During indentation, the elastic stress field far exceeds the permanent deformation area. As the indentation depth increases, the apparent hardness and modulus are affected by the interaction of the stress field with the underlying substrate 110. The influence of the substrate 110 on the hardness occurs at a deeper indentation depth (i.e., typically at a depth greater than about 10% of the total thickness of the optical film structure 120). In addition, a further complexity is that the hardness response requires a certain minimum load to produce complete plasticity during the indentation process. Before a certain minimum load, the hardness generally shows an increasing trend.

[0135] At smaller indentation depths (which can also be characterized as smaller loads) in the optical film structure 120 (e.g., up to about 50 nm), the apparent hardness of the material exhibits a sharp increase relative to the indentation depth. This smaller indentation depth range does not represent a true measure of hardness, but rather reflects the development of the plastic zone described above, which is related to the finite radius of curvature of the indenter. At moderate indentation depths, the apparent hardness approaches the maximum level. At deeper indentation depths, the effect of the substrate 110 becomes more pronounced as the indentation depth increases. Once the indentation depth exceeds about 30% of the optical coating thickness, the hardness may begin to drop sharply.

[0136] In one or more embodiments, Figures 1A to 1DAs shown, as measured from the outer surface 120a of the optical film structure 120 by the Berkovich indenter hardness test, the hardness exhibited by the transparent article 100 at an indentation depth of 100-125nm or at a depth of 125nm can be greater than about 15GPa, 16GPa, 17GPa, 18GPa, or 19GPa, indicating a higher shallow hardness.

[0137] In one or more embodiments, the maximum hardness exhibited by the transparent article 100 as measured from the outer surface 120a of the optical film structure 120 by the Berkovich hardness test over an indentation depth of 100 nm to about 500 nm or over an indentation depth of 100 nm to about 900 nm can be about 10 GPa or greater, about 11 GPa or greater, about 12 GPa or greater, about 13 GPa or greater, or about 14 GPa or greater. For example, the maximum hardness exhibited by the transparent article 100 as measured from the outer surface 120a of the optical film structure 120 by the Berkovich hardness test over an indentation depth of 100 nm to about 500 nm can be 10 GPa, 11 GPa, 12 GPa, 13 GPa, 14 GPa, 15 GPa, 16 GPa, 17 GPa, 18 GPa, 19 GPa, 20 GPa, or greater. In some implementations, the maximum hardness of the transparent article 100 at an indentation depth of 100 nm is greater than 8 GPa, 10 GPa, 11 GPa, 12 GPa, 13 GPa, 14 GPa, 15 GPa, 16 GPa, 17 GPa, 18 GPa, or 19 GPa. In some implementations, the maximum hardness of the transparent article 100 at an indentation depth of 500 nm is greater than 8 GPa, 10 GPa, 12 GPa, 14 GPa, 16 GPa, 17 GPa, 18 GPa, or 19 GPa. In addition, according to some embodiments, the maximum hardness exhibited by the transparent article 100 measured from the outer surface 120a of the optical film structure 120 by the Berkovich hardness test over an indentation depth in the range of 100 nm to about 500 nm, about 100 nm to about 900 nm, or about 200 nm to about 900 nm can be about 8 GPa or greater, about 10 GPa or greater, about 12 GPa or greater, about 14 GPa or greater, 15 GPa or greater, 16 GPa or greater, 17 GPa or greater, or even 18 GPa or greater.

[0138] In one or more embodiments of the present disclosure, Figures 1A to 1DAs shown, the average failure stress level exhibited by the transparent articles 100 having the substrate 110 including the glass-ceramic material measured in the ROR test of the outer surface 120a of the optical film structure 120 of these articles placed under tension can be 500 MPa or greater, 600 MPa or greater, 700 MPa or greater, 750 MPa or greater, 800 MPa or greater, or even 850 MPa or greater. In essence, these article-level average failure stress levels unexpectedly indicate that the transparent articles 100 having the optical film structure 120 have not experienced any loss or have not experienced any substantial loss in the failure strength relative to their bare glass-ceramic substrates. In some embodiments, the average breaking stress level exhibited by the transparent article 100 measured in the ROR test of the outer surface 120a of the optical film structure 120 of the article placed under tension is 500MPa, 550MPa, 600MPa, 650MPa, 700MPa, 725MPa, 750MPa, 775MPa, 800MPa, 825MPa, 850MPa, 875MPa, 900MPa, 925MPa, 950MPa, 975MPa, 1000MPa, 1025MPa, 1050MPa, 1075MPa, 1100MPa, and all average breaking stress levels between the foregoing values.

[0139] Referring again to the transparent article 100 having an average ROR failure stress level of 700 MPa or greater (see Figures 1A to 1D ), it should be understood that these failure stress levels can be achieved through the control of the composition, arrangement, and / or treatment of the optical film structure 120 used in the transparent article 100. It should be noted that the composition, arrangement, and / or treatment of the optical film structure 120 can be adjusted to obtain a residual compressive stress level of at least 700 MPa (e.g., 700 to 1100 MPa) and a maximum elastic modulus of at least 120 GPa (e.g., 120 to 200 GPa, 140 to 200 GPa, 140 to 170 GPa, or 140 to 180 GPa). In some cases, it is useful to quantify the elastic modulus of the optical film structure 120 at a depth equal to 15% of the total thickness of the optical film structure 120 to more accurately compare the moduli of optical film structures 120 of different thicknesses. Using this metric, the preferred range of elastic modulus at a depth equal to 15% of the total thickness of the optical film structure 120 can be adjusted to a range of 120 to 180 GPa or 120 to 160 GPa. The mechanical properties of these optical film structures 120 unexpectedly correlate to average stress levels of 500 MPa or greater, 600 MPa or greater, or 700 MPa or greater measured in ROR testing of the outer surface 120a of the optical film structure of the article placed under tension in the transparent articles 100 employing these optical film structures (see Fig. 9A , and the corresponding description that follows below).

[0140] Further with respect to the residual compressive stress and elastic modulus level (and hardness level) of the optical film structure 120, these properties can be controlled by adjusting the stoichiometry and / or thickness of the low RI layer 130A, the high RI layer 130B, the medium RI layer 130C, the capping layer 131, and the scratch-resistant layer 150. In embodiments, the residual compressive stress and elastic modulus level (and hardness level) exhibited by the optical film structure 120 can be controlled by adjusting the processing conditions used to sputter the layers of the optical film structure 120, specifically the high RI layer 130B and the scratch-resistant layer 150 thereof. In some implementations, for example, a reactive sputtering process can be used to deposit the high RI layer 130B comprising a silicon-containing nitride or a silicon-containing oxynitride. Furthermore, these high RI layers 130B can be deposited by applying power to a silicon sputtering target in a reactive gas environment including argon (e.g., at a flow rate of 50 to 150 sccm), nitrogen (e.g., at a flow rate of 200 to 250 sccm), and oxygen, wherein the residual compressive stress and elastic modulus levels depend greatly on the selected oxygen flow rate. For example, a relatively low oxygen flow rate (e.g., 45 sccm) can be used according to the aforementioned argon and nitrogen flow conditions to produce a SiO2-rich silicon layer 130B. x N y The stoichiometric high RI layer 130B is formed such that the optical film structure 120 exhibits a residual compressive stress of about 942 MPa, a hardness of 17.8 GPa, and an elastic modulus of 162.6 GPa. As another example, a relatively high oxygen flow rate (e.g., 65 sccm) can be used according to the aforementioned argon and nitrogen flow conditions to produce a SiO x N y The stoichiometric high RI layer 130B causes the optical film structure 120 to exhibit a residual compressive stress of about 913 MPa, a hardness of 16.4 GPa, and an elastic modulus of 148.4 GPa. Thus, the stoichiometry of the optical film structure 120 (specifically, its high RI layer 130B and the scratch-resistant layer 150) can be controlled to achieve target residual compressive stress and elastic modulus levels, which are unexpectedly associated with advantageously high average failure stress levels in the transparent article 100 (e.g., greater than or equal to 700 MPa).

[0141] According to an embodiment, in the optical wavelength range of 400 to 700 nm, at normal incidence, 0 to 10 degrees, 0 to 20 degrees, 0 to 30 degrees, 0 to 40 degrees, 0 to 50 degrees, or even 0 to 60 degrees, Figures 1A to 1DThe transparent article 100 shown may exhibit an average dual-sided or dual-surface photopic transmittance or average visible light transmittance (i.e., through both major surfaces 112, 114 of the substrate 110) of about 85% or greater, about 88% or greater, about 90% or greater, about 91% or greater, about 92% or greater, about 93% or greater, or even about 94% or greater. In some embodiments, in the infrared spectrum (e.g., 940 nm), at normal incidence, 0 to 10 degrees, 0 to 20 degrees, 0 to 30 degrees, 0 to 40 degrees, 0 to 50 degrees, or even 0 to 60 degrees, the transparent article 100 may exhibit an average dual-sided transmittance of about 85% or greater, about 88% or greater, about 90% or greater, about 91% or greater, about 92% or greater, about 93% or greater, or even about 94% or greater. In some embodiments, in the near infrared spectrum (e.g., average transmittance from 1000 nm to 1700 nm), at normal incidence, 0 to 10 degrees, 0 to 20 degrees, 0 to 30 degrees, 0 to 40 degrees, 0 to 50 degrees, or even 0 to 60 degrees, the transparent article 100 may exhibit an average double-sided transmittance of about 80% or greater, about 85% or greater, about 88% or greater, about 90% or greater, about 91% or greater, about 92% or greater, or even about 93% or greater.

[0142] According to some implementations, Figures 1A to 1D The illustrated transparent article 100 may exhibit a dual surface transmission color of -4 to +4, -3 to +3, -2.5 to +2.5, or -2 to +2 in a* and b* measured at all angles of incidence from 0 to 90 degrees using a D65 illuminant. For example, the transparent article 100 may exhibit a transmission color of -4, -3.5, 3.0, -2.5, -2.0, -1.5, -1.0, -0.5, 0, +0.5, +1.0, +1.5, +2.0, +2.5, +3.0, +3.5, +4.0 in a* and b*, and all values ​​therebetween.

[0143] According to some implementations, the measured at normal incidence, 0 to 10 degrees, or all incidence angles from 0 to 90 degrees. Figures 1A to 1D The transparent article 100 shown in FIG. 1 shows a D65 illuminant with a wavelength of √(a* 2 +b* 2 ) A given transmission color can be less than 4, less than 3.5, less than 3, less than 2.5, less than 2, less than 1.5, or even less than 1. For example, the transparent article 100 can exhibit a transmission color of less than 6, 5.5, 5.0, 4.5, 4, 3.75, 3.5, 3.25, 3, 2.75, 2.5, 2.25, 2, 1.5, 1.0, 0.5, or even less, measured at normal incidence, all angles of incidence from 0 to 10 degrees, or from 0 to 90 degrees.

[0144] According to an embodiment, at normal incidence, near normal incidence (about 8°), or 0 to 10 degrees, Figures 1A to 1D The illustrated transparent article 100 may exhibit an average single-side or first surface (i.e., through one of the major surfaces 112, 114 of the substrate 110) photopic reflectance or average reflectance in the optical wavelength range of 400 to 700 nm through one or both major surfaces of the substrate 110 (i.e., first surface or dual surface reflectance) that is less than about 10%, less than about 9%, less than about 8%, less than about 7%, less than about 6%, less than about 5%, less than about 4%, less than about 2%, or even less than 1%. For example, the first surface average photopic reflectance exhibited by the transparent article 100 may be less than 10%, less than 8%, less than 6%, less than 5%, less than 2%, or even less than 1%.

[0145] According to an embodiment, at normal incidence, near normal incidence (about 8°), or 0 to 10 degrees, Figures 1A to 1D The transparent article 100 shown may exhibit an average single-side or first surface reflectivity or average reflectivity through one or both major surfaces (i.e., first surface or dual surface reflectivity) of the substrate 110 (i.e., through one of the major surfaces 112, 114 of the substrate 110) at an infrared wavelength (e.g., 940 nm) or an infrared wavelength range (e.g., 900-950 nm) of less than about 8%, less than about 7%, less than about 6%, less than about 5%, less than 4.5%, less than 4.3%, less than about 4%, less than about 3%, or even less than 2%. For example, the first surface reflectivity of the transparent article 100 at an infrared wavelength (e.g., about 940 nm) may be less than 8%, less than 7%, less than 6%, less than 5%, less than 4%, or even less than 2%.

[0146] According to an embodiment, at normal incidence, near normal incidence (about 8°), or 0 to 10 degrees, Figures 1A to 1DThe transparent article 100 shown may exhibit an average single-side or first-surface reflectivity or average reflectivity through one or both major surfaces (i.e., first-surface or dual-surface reflectivity) of the substrate 110 at a near-infrared wavelength (e.g., 1500 nm) or a near-infrared wavelength range (e.g., 1000-1700 nm, 1500-1600 nm) of less than about 15%, less than about 12.5%, less than about 10%, less than about 9%, less than about 8%, less than about 7%, less than about 6%, less than about 5%, less than about 4%, less than about 3%, or even less than 2.5%. For example, the first surface reflectivity exhibited by the transparent article 100 at a near-infrared wavelength (e.g., about 1500 nm, about 1600 nm, etc.) can be less than 15%, less than 13%, less than 12%, less than 10%, less than 9%, less than 8%, less than 7%, less than 6%, less than 5%, less than 4%, less than 3%, or even less than 2.5%.

[0147] According to some implementations, Figures 1A to 1D The transparent article 100 shown exhibits a first surface reflected color measured at all incident angles from 0 to 90 degrees using a D65 illuminant that can be -5 to +5, -4 to +4, -3 to +3, or -2 to +2 in a*, and can be -12 to +4, -10 to +3, or -8 to +2 in b*. For example, the first surface reflected color exhibited by the transparent article 100 can be -5, -4.5, -4, -3.5, -3.0, -2.5, -2.0, -1.5, -1.0, -0.5, 0, +0.5, +1.0, +1.5, +2.0, +2.5, +3.0, +3.5, +4.0, +4.5 and +5.5, and all values ​​therebetween in a*, and can be -12, -11, -10, -9, -8, -7, -6, -5, -4, -3, -2, -1, 0, +1, +2, +3, +4, and all values ​​therebetween in b*.

[0148] According to some implementations, the measured at normal incidence, 0 to 10 degrees, or all incidence angles from 0 to 90 degrees. Figures 1A to 1D The transparent article 100 shown in FIG. 1 shows a D65 illuminant with a wavelength of √(a* 2 +b* 2) The reflected color of a given first surface (i.e., through one of the major surfaces 112, 114 of the substrate 110) can be less than 15, less than 12.5, less than 10, less than 8, less than 6, less than 4, less than 3, or even less than 2. For example, the transparent article 100 can exhibit a reflected color of less than 15, 14, 13, 12, 11, 10, 9, 8, 7, 6, 5, 4, 3.75, 3.5, 3.25, 3, 2.75, 2.5, 2.25, 2, 1.9, 1.8, 1.7, 1.75, 1.6, 1.5, 1.4, 1.3, 1.25, 1.2, 1.1, 1, or even less.

[0149] In some implementations, at normal incidence, near normal incidence (about 8°), or 0 to 10 degrees, Figures 1A to 1D The maximum to minimum oscillation of the average reflectivity exhibited by the transparent article 100 shown in the near infrared optical wavelength range of 1000 to 1700nm can be less than 6%, less than 5%, less than 4%, less than 3%, less than 2%, or even less than 1%. For example, at vertical incidence, near vertical incidence (about 8°), or 0 to 10 degrees, the oscillation exhibited by the reflectance spectrum of the transparent article 100 can be 6%, 5.5%, 5.0%, 4.5%, 4.0%, 3.5%, 3.0%, 2.5%, 2%, 1.5%, 1.0%, 0.75%, or even lower. It should be noted that these oscillating reflectivity values ​​are expressed in absolute reflectivity or transmittance units, where the scale of reflectivity is 0-100%. Therefore, an embodiment of a transparent article 100 having a 1% average reflectivity of 1000nm to 1700nm and less than 0.5% reflectivity oscillation will have a range of reflectivity values ​​between 0.5% and 1.5% within the specified wavelength range. In addition, at normal incidence, near normal incidence (about 8°), or 0 to 10 degrees, the maximum reflectivity exhibited by the transparent article 100 in the near infrared optical wavelength range of 1000 to 1700 nm can be less than 12%, less than 10%, or less than 6%.

[0150] According to some implementations, Figures 1A to 1D The illustrated transparent articles 100 can exhibit color and reflectivity uniformity associated with variations in the thickness of the optical film structure 120, where the variations in the thickness of the optical film structure 120 are caused by the sight layer, the film and optical structure deposition methods, and the non-planar portions of the substrate 110 (e.g., portions associated with the substrate 110 having flat, angled, or curved areas). More specifically, for ranges of optical film structure thickness scaling factors of 70% to 100%, 60% to 100%, 50% to 100%, 40% to 100%, or even 35% to 100%, these transparent articles 100 can exhibit a uniformity of color and reflectivity ...2 +b* 2 )A color shift of less than 4, less than 3, or even less than 2 for a given first surface reflectivity and / or dual surface transmittance.

[0151] exist Figures 1A to 1D In some implementations of the illustrated article 100, the substrate 110 is faceted or curved such that a normal angle to a first portion of the article is different than a normal angle to a second portion of the article (in Figures 1A to 1D ), and the physical thickness of the optical film structure 120 in the first part is different from the physical thickness of the optical film structure 120 in the second part. According to an embodiment, the physical thickness of the optical film structure 120 in the second part is 85-90% of the physical thickness of the optical film structure 120 in the first part, and the color shift exhibited by the product 100 in the first and second parts is less than 5, 4, 3, 2, or 1.5. In addition, the difference in the average reflectivity of the first surface exhibited by the first part and the second part of the optical film structure 120 is less than 2%, less than 1.5%, or even less than 1% of the absolute reflectivity value. According to another embodiment, the physical thickness of the optical film structure 120 in the second part is 85-90% of the physical thickness of the optical film structure 120 in the first part, and the color shift exhibited by the product 100 in the first and second parts is less than 10, 7.5, 5, 4, 3, or 2. In addition, the difference in the average reflectivity of the first surface exhibited by the first part and the second part of the optical film structure 120 is less than 3%, less than 2%, or even less than 1% of the absolute reflectivity value.

[0152] In some implementations, certain transparent articles 100 of the present disclosure (e.g., Figure 1E to Figure 1G The thinner optical film structures 120 (shown in Figure 1, as described below) exhibit high or higher shallow hardness levels compared to conventional transparent articles and other transparent articles of the present disclosure. In addition, recent testing supports the accuracy and reliability of hardness measurements at shallower depths (e.g., 20nm to 40nm). Advantageously, these transparent articles have lower manufacturing costs (e.g., less material in the layer, less deposition time per layer, etc.) and lower deposition warpage levels.

[0153] General Reference Figure 1E to Figure 1G The transparent articles 100 shown in the drawings have optical film structures 120 that exhibit high hardness at shallow depths. In addition, these optical film structures 120 employ one or more medium RI layers 130C (e.g., n=1.5 to 1.9, SiO x N y materials), sometimes incorporating one or more high RI layers 130B (e.g., n=1.9 or greater) in the outer structure 130a, SiN x). This strategy tends to minimize the use of lower refractive index materials (e.g., low RI layer 130A) in the optical film structure 120 and the outer structure 130a, which is an important factor in improving the hardness of the entire optical film structure 120, especially at shallow indentation depths (measured from the air-side surface 120a) (e.g., 20nm, 40nm, 100nm and 125nm).

[0154] Reference Figure 1E The transparent article 100 shown has an optical film structure 120 having an outer structure 130a and an inner structure 130b, wherein the outer structure 130a is disposed above the scratch-resistant layer 150, and the inner structure 130b is disposed between the scratch-resistant layer 150 and the substrate 110. In this configuration, the inner structure 130b may have four layers above the substrate 110 and below the scratch-resistant layer 150 in the following order: a low RI layer 130A (shown in contact with the substrate 110), a medium RI layer 130C, a high RI layer 130B, and a medium RI layer 130C. Other configurations of the inner structure 130b are also possible (e.g., three to nine layers in total). In addition, in Figure 1E In the particular embodiments of the transparent article 100 shown, the scratch resistant layer 150 is relatively thin (e.g., 100 nm to 300 nm, 125 nm to 250 nm, 150 nm to 250 nm, and all thicknesses between these ranges). In embodiments, the scratch resistant layer 150 is made of a high RI layer 130B material (e.g., SiN x ). In addition, the outer structure 130a can use two layers on the scratch resistant layer 150 in the following order: the medium RI layer 130C and the capping layer 131. However, other configurations of the outer structure 130a are also possible (for example, one to five layers). In general, Figure 1E The illustrated transparent article 100 advantageously minimizes the amount of low RI material (ie, a lower number of low RI layers 130A and the thickness of these layers in the capping layer 131 and / or the optical film structure 120 ), which tends to improve the shallow high hardness of the article 100 .

[0155] Now refer to Figure 1FThe transparent product 100 shown adopts an optical film structure 120 having an outer structure 130a and an inner structure 130b, wherein the outer structure 130a is disposed above the scratch-resistant layer 150, and the inner structure 130b is disposed between the scratch-resistant layer 150 and the substrate 110. In this configuration, the inner structure 130b can adopt two layers in the following order above the substrate 110 and below the scratch-resistant layer 150: a low RI layer 130A (shown as being in contact with the substrate 110) and a medium RI layer 130C. Other configurations of the inner structure 130b are also feasible (e.g., one to nine layers in total). In addition, the scratch-resistant layer 150 is relatively thin (e.g., 150nm to 300nm, 175nm to 275nm, 200nm to 275nm, 225nm to 275nm, and all thicknesses between these ranges). In an embodiment, the scratch-resistant layer 150 adopts a high RI layer 130B material (e.g., SiN x ). In addition, the outer structure 130a can use two layers on the scratch resistant layer 150 in the following order: the medium RI layer 130C and the capping layer 131. However, other configurations of the outer structure 130a are also possible (for example, one to five layers). In general, Figure 1F The illustrated transparent article 100 advantageously minimizes the amount of low RI material (i.e., a lower number of low RI layers 130A and the thickness of these layers in the capping layer 131 and / or the optical film structure 120) and employs a relatively thick scratch-resistant layer 150 (e.g., >200 nm), which tends to improve the shallow high hardness of the article 100 while the outer structure 130a is still able to achieve low reflectivity and desired color properties.

[0156] according to Figure 1E and Figure 1FIn the embodiment of the transparent article 100 shown, the total thickness of the optical film structure 120 is less than 800nm, 700nm, 600nm, 500nm, or even 450nm, and the photopic average first surface reflectance exhibited by the article is less than 6%, and the maximum hardness measured by the Berkovich hardness test at any indentation depth (e.g., 20 to 200 nanometers) is greater than 12GPa, 13GPa, 14GPa, 15GPa, or even 16GPa. For example, the total thickness of the optical film structure 120 can be 775nm, 750nm, 725nm, 700nm, 650nm, 600nm, 550nm, 500nm, 450nm, 425nm, 400nm, and all thicknesses between these thickness levels. In addition, the maximum hardness exhibited by the article 100 can be 12, 12.5, 13, 13.5, 14, 14.5, 15, 15.5, 16, 16.5, 17, 17.5, or even 18 GPa, and all hardness values ​​between these maximum hardness levels, and the photopic average first surface reflectivity can be 1, 1.25, 1.5, 1.75, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 5.75 and up to 6%, and all reflectivity values ​​between these levels. In some implementations, the photopic average first surface reflectance of these articles 100 can be less than 6%, 4%, 2%, 1.8%, or even less than 1.6%, while exhibiting any of the following hardness levels as measured by the Berkovich Hardness Test: a hardness greater than 9 GPa at an indentation depth of 20 nm, a hardness greater than 10 GPa at an indentation depth of 40 nm, a hardness greater than 12 GPa at an indentation depth of 100 nm, or a hardness greater than 12 GPa at an indentation depth of 125 nm.

[0157] Now refer to Figure 1G The transparent article 100 shown employs an optical film structure 120 having an outer structure 130a and an inner structure 130b, wherein the outer structure 130a is disposed above the scratch-resistant layer 150, and the inner structure 130b is disposed between the scratch-resistant layer 150 and the substrate 110. In this configuration, the inner structure 130b may employ seven layers above the substrate 110 and below the scratch-resistant layer 150 in the following order: a low RI layer 130A (shown in contact with the substrate 110), a medium RI layer 130C, a low RI layer 130A, a medium RI layer 130C, a low RI layer 130A, a medium RI layer 130C, and a low RI layer 130A. Figure 1G In some embodiments of the transparent article 100 shown, the inner structure 130b employs two (2) to twelve (12) periods 132 of alternating low RI layers 130A and medium RI layers 130C and additional low RI layers 130A. Figure 1GIn some embodiments of the transparent article 100 shown, the inner structure 130b may include any number of layers from five (5) to twenty-five (25) layers.

[0158] In addition, Figure 1G In some embodiments of the transparent article 100 shown, the internal structure 130b may include a refractive index gradient (in Figure 1G ), rather than, for example, multiple low RI layers 130A and high RI layers 130B. Therefore, in these embodiments, the transparent article 100 may include, in sequence: 1) a substrate 110; 2) a refractive index gradient structure as an inner structure 130b; 3) a scratch-resistant layer 150; and 4) an outer structure 130a that can achieve high shallow hardness. The refractive index gradient can be formed by a composition gradient. In such an embodiment, the composition at or adjacent to the substrate major surface 112 can be tuned to have a refractive index within about 0.05 refractive index units of the refractive index of the substrate 110 itself (e.g., about 1.45 to 1.55), and the composition at or adjacent to the scratch-resistant layer 150 can be tuned to have a refractive index within about 0.1 refractive index units of the refractive index of the scratch-resistant layer 150 (e.g., about 1.65 to 1.95). The thickness of the refractive index gradient region (ie, as the inner structure 130b) may preferably be in the range of about 100 nm to 500 nm.

[0159] exist Figure 1G In some embodiments of the transparent article 100 shown having an inner structure 130b including a refractive index gradient, the gradient is derived from a composition gradient formed by materials such as Si, Al, N, O, C, and / or a combination thereof. In one or more specific embodiments, the composition gradient is formed by Si, N, and / or O. In one example, the refractive index gradient may include an oxygen content gradient, wherein the oxygen content decreases or remains constant along the thickness of the refractive index gradient in the direction from the substrate surface to the scratch-resistant layer. In yet another example, the refractive index gradient may include a nitrogen content gradient, wherein the nitrogen content increases or remains constant along the thickness of the refractive index gradient in the direction from the substrate surface to the scratch-resistant layer. In one or more alternative embodiments, the optical film structure 120 may include a density gradient and / or an elastic modulus gradient to supplement or replace the refractive index gradient described elsewhere herein. In an embodiment, an elastic modulus gradient may be used to further improve certain mechanical properties of the transparent article 100 (e.g., maintaining or improving retention strength, reducing warping, or reducing delamination).

[0160] Refer again Figure 1GIn the transparent article 100 shown, the scratch resistant layer 150 can be relatively thick (e.g., 200 nm to 5000 nm, 400 nm to 5000 nm, 800 nm to 5000 nm, 1500 nm to 5000 nm, 1500 nm to 3000 nm, 1500 nm to 2500 nm, and all thicknesses between these ranges). In an embodiment, the scratch resistant layer 150 is made of a medium RI layer 130C material (e.g., SiO x N y ). In addition, Figure 1G As shown, the outer structure 130a can use six layers above the scratch resistant layer 150 in the following order: medium RI layer 130C, high RI layer 130B, medium RI layer 130C, high RI layer 130B, medium RI layer 130C and capping layer 131. In addition, the outer structure 130a can use a series of periods 132 (e.g., N=2 to 5) including alternating medium RI layers 130C and high RI layers 130B or alternating high RI layers 130B and medium RI layers 130C, additional medium RI layers 130C or high RI layers 130B and an outermost capping layer 131. In addition, other configurations of the outer structure 130a are also feasible (e.g., four to fourteen layers). In general, Figure 1G The illustrated transparent article 100 advantageously minimizes the amount of low RI material (i.e., a lower number of low RI layers 130A and thicknesses of these layers in the capping layer 131 and / or the optical film structure 120), and employs a relatively thick high RI layer 130B in the outer structure 130a as well as a relatively thick scratch-resistant layer 150, all of which tend to improve the shallow high hardness of the article 100.

[0161] according to Figure 1E to Figure 1G In the embodiment of the transparent article 100 shown, the optical film structure 120 can have a total thickness of 200nm to 5000nm, wherein the hardness at a 20nm indentation depth measured by the Berkovich hardness test is greater than 11GPa, the hardness at a 40nm indentation depth is greater than 11 or 12GPa, the hardness at a 100nm indentation depth is greater than 15GPa, or the hardness at a 125nm indentation depth is greater than 16GPa. In some of these embodiments, the article 100 exhibits a photopic average first surface reflectivity of less than 6%, 5%, 4.5%, 4%, 3%, 2%, 1.75%, or even 1.6%.

[0162] Generally refer to the above detailed description and Figures 1A to 1G100, embodiments of which employ an optical film structure 120 that, when deposited in a substrate 110, can have a significant amount of compressive stress that contributes to the overall retained strength of the article. On the other hand, residual compressive stress in the optical film structure 120 can also cause the article 100 to warp undesirably, requiring expensive additional processing (e.g., asymmetric polishing and material removal) of the substrate 110 prior to deposition of the layers that make up the optical film structure 120. That is, some embodiments of the optical film structure 120 require some asymmetric removal of material from the substrate 110 prior to deposition of the optical film structure 120 to effectively offset the residual compressive stress of the optical film structure to ensure that the resulting article 100 does not exhibit significant warping.

[0163] Without being bound by theory, it is generally understood that reducing the thickness of the optical film structure 120 can reduce the degree of warping caused by the optical film structure 120 when deposited on the substrate 110. Fig.37A , provides a schematic diagram of a comparative product having an optical film structure, the optical film structure having a scratch-resistant layer of different thickness levels. In addition, Fig.37B is modeled to indicate the Fig.37A Schematic diagram of the Berkovich hardness test results of the optical film structure of the comparative product (GPa) and the indentation depth. Although some conventional optical film structure designs (e.g., Fig.37A ) using a relatively thick scratch-resistant layer (e.g., 50-2000 nm SiO x N y or SiN x ), but reducing the thickness of these scratch-resistant layers to achieve the goal of reducing warpage may significantly and undesirably reduce the hardness of the article. Fig.37A and Fig.37B As shown, optical structure designs that use a large amount of low RI material (e.g., SiO2) in the outer structure 130a above the scratch-resistant layer tend to show a significant degree of hardness sensitivity as a function of the thickness of the scratch-resistant layer. That is, the warpage problem cannot be easily solved by reducing the thickness of the scratch-resistant layer of the optical film structure design in conventional products.

[0164] However, embodiments of the transparent article 100 of the present disclosure (see, e.g. Figures 1A to 1G ) uses an optical film structure 120, wherein the outer structure 130a has a plurality of high RI layers 130B (e.g., SiN x ) and the medium RI layer 130C (e.g., SiO x N y), wherein the outer structure 130a itself provides a significant hardness response. That is, without being bound by theory, these embodiments configure less low RI material in the outer structure 130a, and the end result is that the outer structure 130a itself has more influence on the hardness response of the transparent article 100. Therefore, the effect of the scratch-resistant layer 150 in these transparent articles 100 is less significant, and therefore, its thickness advantageously has less influence on the hardness response of the article. Therefore, as described in further detail in subsequent paragraphs, embodiments of these articles 100 can advantageously use thinner scratch-resistant layers to reduce warping without sacrificing hardness levels and maintaining strength.

[0165] Reference Fig.38 , provides a schematic diagram of the basic fracture mechanics principle of an embodiment of the transparent article 100 of the present disclosure. As shown in the figure, according to the basic fracture mechanics principle, the stress intensity factor K for a defect at the surface of the "combination" of the optical film structure 120 and the substrate 110 is I It can be written as Fig.38 As shown in the figure, it is obvious that when K I When K becomes equal to the fracture toughness of the glass substrate 110, IC , glass failure. It can be seen that the stress intensity factor is proportional to the total crack length "a" (i.e., the larger the crack, the higher the stress intensity factor and the lower the strength of the combined system). Therefore, thicker optical film structures (h c )(See Fig.38 ) is more likely to have a lower intensity.

[0166] Apart from Fig.38 In addition to the sensitivity of the optical film structure thickness to the retained strength shown, the warpage of the article is also affected by the thickness of the optical film structure. Fig.39A and Fig.39B , a schematic diagram of a transparent article 100 of the present disclosure is provided, which is subjected to pure bending with equal moments to evaluate the function of thickness and warpage of the optical film structure 120. More specifically, the warpage of the optical film structure 120 on the substrate 110 can be approximated as:

[0167]

[0168] Where D is the stiffness or flexural stiffness of the substrate 110 and is given by:

[0169]

[0170] In addition, the moment M is due to the stress in the optical film structure 120 and can be approximated as:

[0171]

[0172] Where σ is the average coating stress, h c is the thickness of the optical film structure 120, and t is the thickness of the substrate 110. According to these relationships and Fig.39A and Fig.39B It is obvious from the description that the warpage in the transparent article 100 is proportional to the thickness of the optical film structure 120 for a constant value of the average optical film structure stress. Therefore, in order to reduce the warpage, it is necessary to reduce the average stress in the optical film structure 120, or to reduce the thickness of the optical film structure 120, or both.

[0173] Therefore, embodiments of the transparent article 100 of the present disclosure (e.g., Figures 1A to 1G The optical film structure 120 may be configured to reduce warping by reducing the thickness of the scratch resistant layer 150 (e.g., a thickness of about 100 nm to less than 2000 nm, about 500 nm to less than 2000 nm, etc.) while retaining strength and hardness. That is, any of the transparent articles 100 of the present disclosure may benefit from these concepts of reducing the prescribed thickness of the scratch resistant layer 150.

[0174] One benefit of these embodiments is that a reduction in the thickness of the scratch-resistant layer 150 means that a smaller amount of material is used in the optical film structure 120, resulting in shorter sputtering times and associated cost savings and increased production. Another benefit is that reducing the thickness of the scratch-resistant layer 150 can maintain or even slightly improve the retention strength of the article 100. Another benefit is that reducing the thickness of the scratch-resistant layer 150 can significantly improve the degree of warping observed in the substrate 110 after deposition of the optical film structure 120; therefore, the lower degree of warping requires less processing (e.g., asymmetric polishing) prior to deposition of the optical film structure 120. Without being bound by theory, another potential benefit is that reducing the thickness of the scratch-resistant layer 150 can reduce the optical film structure force (F=σh c ), which should reduce the likelihood of delamination between the optical film structures 120 at the edges 116, 118 of the transparent article 100.

[0175] Embodiments of the transparent article 100 of the present disclosure (e.g., Figures 1A to 1G The substrate 110 may further include features at one or more major surfaces 112, 114 (in Figures 1A to 1G), which can combine anti-reflective (AR) and anti-glare (AG) optical properties with mechanical strength and wear resistance. Anti-reflective structures and functions are generally defined here as reflectivity reduction based on thin film interference, while anti-glare structures and functions are generally defined here as textured surfaces that impart a certain degree of light scattering and are generally used to reduce the specular reflectivity of the surface or interface of the product. Compared to products having only AR or AG properties and characteristics, these transparent products 100 advantageously have a lower first surface specular reflectivity level (e.g., less than 0.3%), which also contributes to higher display contrast, color gamut and neutral reflective color level. More specifically, these transparent products 100 can have an optical film structure 120 and one or more textured AG substrate surfaces (e.g., diffraction, roughness and other textured morphologies) with high hardness at shallow depths (e.g., at one or more of the main surfaces 112, 114) (a scratch-resistant layer 150 may be included). In addition, since the AG textured surface areas of these products 100 can scatter light in transmission and reflection, the appearance of hidden reflections in the display can also be reduced. In addition, these transparent articles 100 and their substrates 110 employ textured surface regions with optimized anti-glare optical properties (e.g., low pixel power deviation (PPD) 140 ) and low transmittance haze).

[0176] As used herein, the terms "pixel power deviation" and "PPD" refer to a quantitative measurement of flicker for a display. In addition, as used herein, the term "flicker" can be used interchangeably with "pixel power deviation" and "PPD". PPD is calculated by image analysis of display pixels according to the following procedure. Grid squares are drawn around each LCD pixel. Then, the total power within each grid square is calculated based on the CCD camera data and designated as the total power of each pixel. Therefore, the total power of each LCD pixel becomes an array of numbers, and its mean and standard deviation can be calculated. The PPD value is defined as the standard deviation of the total power per pixel divided by the average power per pixel (multiplied by 100). The total power collected from each LCD pixel by the eye simulator camera is measured, and the standard deviation of the total pixel power (PPD) of the entire measurement area (typically including approximately 30×30 LCD pixels) is calculated.

[0177] Details of the measurement system and image processing calculations for obtaining PPD values ​​are described in U.S. Patent 9,411,180, entitled "Apparatus and Method for Determining Sparkle," which is incorporated herein by reference in its entirety for important portions related to PPD measurements. In addition, unless otherwise noted, an SMS-1000 system (Display-Messtechnik & Systeme GmbH & Co. KG) was employed to generate and evaluate the PPD measurements of the present disclosure. The PPD measurement system includes: a pixelated source (e.g., a Lenovo Z50 140ppi laptop) including a plurality of pixels, wherein each of the plurality of pixels has a reference index i and j; and an imaging system optically arranged along an optical path originating from the pixelated source. The imaging system includes: an imaging device disposed along the optical path and having a pixelated sensitive area including a second plurality of pixels, wherein each of the second plurality of pixels is referenced using indices m and n; and an aperture disposed on the optical path between the pixelated source and the imaging device, wherein the aperture has an adjustable collection angle for an image originating from the pixelated source. The image processing calculations include: obtaining a pixelated image of a transparent sample, the pixelated image including a plurality of pixels; determining boundaries between adjacent pixels in the pixelated image; integrating within the boundaries to obtain an integrated energy for each source pixel in the pixelated image; and calculating a standard deviation of the integrated energy for each source pixel, wherein the standard deviation is the power per pixel dispersion. As used herein, all "PPD" and "flicker" values, properties, and limits utilize a pixel density of 140 pixels per inch (PPI) (also referred to herein as "PPD 140 ”) are calculated and evaluated using the test settings of a display device (e.g., transparent article 100) having a pixel density of 140 pixels per inch. In addition, unless otherwise specified herein, flicker is recorded in “%” to indicate the percentage of flicker observed on a display device having a pixel density of 140 pixels per inch.

[0178] As used herein, the terms "transmission haze" and "haze" refer to the percentage of transmitted light that is scattered outside an angular cone at about ±2.5° according to ASTM D1003 (entitled "Standard Test Method for Haze and Luminous Transmittance of Transparent Plastics," the contents of which are incorporated herein by reference in their entirety).

[0179] Also as used herein, “average texture height (R text)” is a characteristic of a structural feature of a textured surface region of a major surface (e.g., one or more major surfaces 112, 114) of a substrate (e.g., substrate 110) of the present disclosure, and is described in nanometers (nm). In addition, for a textured surface region including a roughened surface region (e.g., produced by etching and / or sandblasting processes), R text It is defined as the average surface roughness of the roughened surface area (R q ), and can be described in units of root mean square (RMS) nanometers (nm). As described in the present disclosure, for a textured surface region including a diffractive surface region, R text Defined as the average difference in height between two heights or depths of a structural feature (e.g., pillar, hole, etc.) associated with a diffractive surface area (or the average difference between the maximum and minimum feature heights).

[0180] In addition, as previously described in the present disclosure, these transparent articles 100 having one or more textured AG substrate surfaces also include an optical film structure 120 having multiple alternating high refractive index (e.g., high RI layer 130B), medium refractive index (e.g., medium RI layer 130C), and / or low refractive index layers (e.g., low RI layer 130A), and in some embodiments, the article can exhibit a hardness greater than 11 GPa at a depth of 20 nm, a hardness greater than 11 GPa at a depth of 40 nm, a hardness greater than 15 GPa at a depth of 100 nm, or a hardness greater than 16 GPa at a depth of 125 nm (measured by the Berkovich indenter hardness test or modeled according to the hardness model described herein).

[0181] Furthermore, the AG textured surface region on or at one or more of the major surfaces 112, 114 of the substrate 110 may enable the employed transparent article 100 to exhibit a PPD of less than 5%. 140 and a transmission haze of less than 50%. In addition, in embodiments, it is desirable to combine these light scattering AG textured surface regions with a relatively thin multilayer optical film structure 120 having a total thickness of 200 nm to 800 nm and having a hardness of greater than 9 GPa at a depth of 20 nm, a hardness of greater than 10 GPa at a depth of 40 nm, a hardness of greater than 12 GPa at a depth of 100 nm, or a hardness of greater than 12 GPa at a depth of 125 nm.

[0182] In some aspects, as understood by those skilled in the art, the textured surface region is a surface having randomly or semi-randomly formed structural features at one or more major surfaces 112, 114 of the substrate 110 formed by various chemical etching, combined chemical precipitation and etching, and / or sandblasting processes (in these embodiments, the surface texture is not considered to be a diffractive surface with a multi-peak distribution of surface heights). According to some embodiments, the lateral etch feature size (i.e., XY dimension) of a majority of the structural features of the roughened surface region ranges from 1 μm to 125 μm, 1 μm to 100 μm, 1 μm to 75 μm, 1 μm to 50 μm, 1 μm to 40 μm, 1 μm to 30 μm, 5 μm to 125 μm, 5 μm to 100 μm, 5 μm to 75 μm, 5 μm to 60 μm, 5 μm to 50 μm, 5 μm to 40 μm, 5 μm to 30 μm, 10 μm to 60 μm, 10 μm to 100 μm, and lateral dimensions within the aforementioned ranges.

[0183] In an embodiment of the transparent article 100, the textured surface region has an average surface roughness (R) ranging from 20 nm to 2000 nm in RMS. q According to a further implementation, the average surface roughness (R q ) is from 10nm to 2500nm, 10nm to 2000nm, 10nm to 1500nm, 20nm to 2500nm, 20nm to 2000nm, 20nm to 1500nm, 40nm to 2000nm, 40nm to 500nm, 40nm to 250nm, 50nm to 2500nm, 50nm to 2000nm, 50nm to 1500nm, 50nm to 1000nm, 50nm to 500nm, 50nm to 250nm, 100nm to 2500nm, 100nm to 2000nm, 100nm to 1500nm, 100nm to 1000nm, 100nm to 500nm, 100nm to 250nm, and all surface roughness values ​​between the foregoing ranges.

[0184] In some implementations of the transparent article 100, the textured surface region can be described as having a first average height and a second average height (e.g., a diffractive surface having a multi-peak distribution of surface heights). The first average height corresponds to the average height of the peaks of the textured surface region, and the second average height corresponds to the depth of the valleys between the peaks. In this configuration, the difference between the first and second average heights of the textured surface region or the difference between the highest average height and the lowest average height can range from 10nm to 500nm, 10nm to 250nm, 25nm to 500nm, 25nm to 250nm, 50nm to 500nm, 100 to 600nm, 100 to 800nm, 50nm to 250nm, 50nm to 150nm, 100nm to 200nm, 120nm to 200nm, and all height differences between the foregoing ranges.

[0185] In an embodiment of the transparent article 100, the textured surface region has an average texture height (R) of 20 nm to 2000 nm. text According to a further implementation, the average texture height (R text ) is 10 nm to 2500 nm, 10 nm to 2000 nm, 10 nm to 1500 nm, 20 nm to 2500 nm, 20 nm to 2000 nm, 20 nm to 1500 nm, 50 nm to 2500 nm, 50 nm to 2000 nm, 50 nm to 1500 nm, 50 nm to 1000 nm, 50 nm to 500 nm, 50 nm to 250 nm, 100 nm to 2500 nm, 100 nm to 2000 nm, 100 nm to 1500 nm, 100 nm to 1000 nm, 100 nm to 500 nm, 100 nm to 250 nm, and all texture height values ​​therebetween. In addition, for textured surface regions including roughened surface regions (e.g., produced by etching and / or sandblasting processes), R text It can be defined as the average surface roughness of the structural features of the roughened surface area (R q ), and is reported in root mean square (RMS) nanometers. As described in the present disclosure, for a textured surface region including a diffractive surface region (see below), R text Defined as the average difference in height between two heights or depths of a structural feature (e.g., pillars, holes, etc.) associated with a diffractive surface area (in the case of a bimodal surface height distribution) or the average difference in height between the highest height and the lowest depth (in the case of a multimodal surface height distribution with more than 2 height modes).

[0186] Referring again to the transparent article 100 of the present disclosure (e.g., Figures 1A to 1GAG properties (e.g., low distinctness of image (DOI), low pixel power deviation (PPD)). 140 ) and low transmission haze). According to aspects of the present disclosure, the diffractive surface regions have structural features (e.g., holes, pillars, ellipses, and / or interconnected spinodal features with controlled surface frequency content). In addition, these diffractive surface regions can enable the transparent article 100 to exhibit a first surface reflectivity DOI of less than 95%, a PPD of less than 5%, and a first surface reflectivity of less than 95%. 140 And a transmission haze of less than 50%. In addition, in some embodiments, the diffractive surface region can have a multimodal distribution (e.g., a bimodal distribution) of surface height (maximum height and / or depth is 120 to 200 nm or 100 to 600 nm), and specular reflection by diffraction interference can be reduced.

[0187] As used herein, "DOI" is equal to 100*(R s -R 0.3 °) / R s , where R s is the specular reflection flux measured from incident light (at 20° from normal) directed toward the diffractive surface area of ​​the transparent article 100 of the present disclosure, and R 0.3 ° is the specular flux at distance R s Reflected flux measured at 0.3° from the same incident light. Unless otherwise stated, the DOI values ​​and measurements described in this disclosure are obtained according to ASTM D5767-18 entitled "Standard Test Method for Instrumental Measurement of Distinctness-of-Image (DOI) Gloss of Coated Surfaces using a Rhopoint IQ Gloss Haze & DOI Meter" (Rhopoint Instruments Ltd.).

[0188] As used herein, a "multimodal distribution" can have multiple surface height modes (e.g., a distribution can be bimodal, trimodal, tetramodal, pentamodal, etc.). In an embodiment, the diffraction AG surface region is configured so that each of these modes is characterized by different peaks of surface height and the area fraction within the distribution of surface height. These peaks can be distinguished by at least 20%, at least 50%, or at least 80% reduction of the area fraction of the peak surface height value between different peaks associated with each of the modes. In addition, the peak of each of the modes can have a varying width, and the area fraction does not need to drop to zero between the peaks of the distribution. However, in some embodiments, the area fraction of the height between each of the peaks on the surface height and area chart can drop to zero or close to zero.

[0189] According to some embodiments of the transparent article 100, the diffractive surface region is configured so that each of the structural features has an aspect ratio greater than 10. Unless otherwise specified, the aspect ratio of each of the structural features is given by the average diameter divided by the corresponding average height. In some implementations, the aspect ratio of the structural features of the diffractive surface region is greater than 10, greater than 20, greater than 50, or greater than 100. For example, the average diameter of the first portion of the structural features is 20 μm, and the average height of 0.2 μm corresponds to an aspect ratio of 100. More generally, the diffractive surface region having features of these aspect ratios is substantially flat or planar, at least when viewed under ambient lighting without any magnification assistance.

[0190] According to some implementations of the transparent article 100, the structural features of the diffractive surface region can be configured according to an average lateral spatial period (related to an average lateral pitch or an average lateral feature size) to achieve anti-glare optical rotation properties. In some implementations of the transparent article 100, the structural features of the diffractive surface region are configured with a period ranging from 1 μm to 200 μm, 5 μm to 200 μm, 5 μm to 150 μm, 5 μm to 100 μm, 5 μm to 50 μm, 5 μm to 30 μm, 20 μm to 150 μm, 20 μm to 100 μm, 10 μm to 30 μm, 10 μm to 20 μm, and all period values ​​between the aforementioned ranges.

[0191] These implementations of the transparent article 100 of the present disclosure (for example, including diffraction AG surface area) provide several advantages over the conventional methods for realizing anti-reflection properties. For example, these transparent articles 100 can use diffraction light scattering to suppress specular reflectivity by a factor of 10x or more, while also realizing a combination of low haze, low glitter and high mechanical durability. High mechanical durability is associated with the relatively low aspect ratio of the structural features of the diffraction surface area. In addition, some transparent articles 100 according to the present disclosure adopt diffraction surface area and multilayer optical film structure 120 to realize a specular reduction greater than 20x, 50x or even 100x. According to some implementations, the spacing and / or size of the average lateral spatial period or feature shape are semi-randomized to minimize color and / or moiré. The level and type of feature randomization in the XY dimension are very important for realizing low PPD and minimizing other display artifacts (for example, moiré or color bands) at the same time. In other words, in the embodiments of the transparent articles 100 of the present disclosure, the conventional perfectly ordered grating-like structures are not preferred.

[0192] More generally, once the desired structure of the surface region is defined, a two-dimensional array of structural features of the diffractive surface region can be manufactured by a number of processes (e.g., optical lithography (photomask), inkjet printing, laser patterning, and / or screen printing). The choice of process depends on the resolution of the structural features (e.g., in terms of diameter, period, and / or pitch) and the technical capabilities of a given process. In some embodiments of the transparent article 100, once the structural parameters of the diffractive surface region are defined (e.g., pillars or holes, average height, pitch, diameter, period, etc.), the design can be converted into a computer-aided design (CAD) file and then used with any of the aforementioned processes to transfer the design to a substrate to create an "engineered" diffractive surface region.

[0193] Another advantage of these transparent articles 100 is that their planar stepped and semi-planar morphology and the controlled structural depth of less than 1 micron or less than 250 nm in the diffractive surface area make it easy to manufacture using much lower consumption of glass materials and etching chemicals (e.g., hydrofluoric acid) compared to conventional etched anti-glare glass substrates, thereby reducing environmental waste and bringing potential cost benefits. Various processes can be used to establish these structures (e.g., organic masks and etching, organic masks and vapor deposition, organic masks and liquid deposition oxides), which can help maintain low manufacturing costs. A further advantage of these transparent articles 100 is that they can exhibit a combination of anti-glare and optical properties that cannot be achieved by conventional anti-glare methods. For example, these transparent articles 100 of the present disclosure combined with the diffractive surface area achieve a DOI of less than 80%, a PPD of less than 2%, and a DOI of less than 10%. 140 and less than 5% haze.

[0194] In the embodiment of the transparent article 100, a photomask / optical lithography process can be used to form a diffractive surface area structure to form a texture depth R text In this case, a photosensitive polymer (i.e., photoresist) is exposed and developed to form a three-dimensional relief image on a substrate (e.g., substrate 110). In general, an ideal photoresist image has the exact shape of the designed or intended pattern on the plane of the substrate, with vertical walls extending through the thickness of the resist (<3μm for spin-coated resists, <20μm for dry film resists, and <15μm for screen-coatable photoresists). When exposed, the final resist pattern is binary, with portions of the substrate being covered by the resist and other portions being completely uncovered. The general sequence of process steps for a typical photolithography process is as follows: substrate preparation (cleaning and dehydration followed by an adhesion promoter for spin-coatable resist (e.g., hexamethyldisilazane (HMDS)), photoresist spin coating, pre-bake, exposure and development, followed by a wet etching process to transfer the binary image to a substrate (e.g., a glass or glass-ceramic substrate). The final step is to strip the resist after the resist pattern has been transferred to the underlying layers. In some cases, post-bake and post-exposure bake steps are required to ensure resist adhesion during the wet etching process.

[0195] After the anti-glare surface is manufactured by any of the above methods, the textured anti-glare surface can be advantageously coated with the high shallow hardness optical film structure 120 design of the present disclosure to produce a transparent product 100 that combines an optimal combination of low specular reflectivity, low reflected image visibility and high abrasion resistance in various usage conditions.

[0196] The transparent article 100 disclosed herein (e.g., Figures 1A to 1G As shown) can be incorporated into equipment articles (for example, equipment articles with a display (or display equipment articles) (for example, consumer electronics, including mobile phones, tablet computers, computers, navigation systems, wearable devices (for example, watches), and the like), augmented reality displays, heads-up displays, eyeglass displays, architectural equipment articles, transportation equipment articles (for example, vehicles, trains, aircraft, marine craft, etc.), appliance equipment articles, or any device that can benefit from transparency, scratch resistance, wear resistance, damage resistance, or a combination thereof). Figure 2A and Figure 2B In combination with any article disclosed herein (e.g., Figures 1A to 1G Specifically, Figure 2A and Figure 2BA consumer electronic device 200 is shown, comprising: a housing 202 having a front surface 204, a rear surface 206, and a side surface 208; electronic components (not shown) at least partially located inside the housing or completely located inside the housing and including at least a controller, a memory, and a display 210 at or adjacent to the front surface of the housing; and a cover substrate 212 at or above the front surface of the housing and located above the display. In some embodiments, the cover substrate 212 can include any transparent article 100 disclosed herein.

[0197] Example

[0198] The following examples describe various features and advantages provided by the present disclosure and are not intended to limit the present disclosure and the appended claims.

[0199] In these examples (Examples 1-28E) and comparative examples (i.e., Comparative Examples 1-5), transparent articles were formed according to the methods of the present disclosure and as described in each of Tables 1-35. More specifically, unless otherwise stated, the optical film structures of these examples were formed using a metal mode reactive sputtering process in a rotary drum coater, wherein the sputtering power was independently controlled in the metal deposition and inductively coupled plasma (ICP) (gas reaction) zones. The reactive gas (e.g., N2 gas and O2 gas) was isolated from the metal target in the ICP (gas reaction) zone. In addition, the metal sputtering zone only employed an inert gas flow (i.e., Ar gas).

[0200] The light transmission and reflection properties of the experimental samples prepared according to these examples were measured using an Agilent Cary 5000 UV-Vis-NIR spectrophotometer.The hardness values ​​for the transparent articles reported in the following examples were obtained using the Berkovich Hardness Test Method outlined previously in this disclosure.

[0201] More specifically, the inventive examples (Examples 1-3 and 10) combined with the strengthened glass-ceramic substrates exhibit, among other mechanical and optical properties, very high shallow hardness and low reflectivity in the visible, IR, and near-IR spectra, and are exemplary of transparent articles 100 of the present disclosure (see Figures 1A to 1D In addition, inventive examples (Examples 4-9 and 11-14) that include glass or glass-ceramic substrates exhibit or are expected to exhibit high shallow hardness and low reflectivity in the visible, IR, and near-IR spectra, among other mechanical and optical properties.

[0202] Similarly, the inventive examples combined with strengthened glass or glass-ceramic substrates (Examples 17-28) exhibit very high shallow hardness, low reflectivity, minimized optical film structure thickness, and various retained properties (e.g., retained strength, hardness, and minimal warping).

[0203] Comparative Example 1

[0204] A comparative transparent article including a strengthened glass ceramic substrate was prepared for this example, and its structure is shown in Table 1 below. The glass ceramic substrate is an ion-exchanged LAS glass ceramic substrate having a thickness of 600 μm and a refractive index of 1.533. In addition, the glass ceramic substrate has the following composition: 74.5% SiO2; 7.53% Al2O3; 2.1% P2O5; 11.3% Li2O; 0.06% Na2O; 0.12% K2O; 4.31% ZrO2; 0.06% Fe2O3; and 0.02% SnO2 (based on weight %) of the oxide. In addition, the glass ceramic substrate was ceramicized according to the following schedule: (a) heating from room temperature to 580°C at 5°C / min; (b) holding at 580°C for 2.75 hours; (c) heating to 755°C at 2.5°C / min; (d) holding at 755°C for 0.75 hours; and (e) cooling to room temperature at a furnace rate. After ceramicization, the glass ceramic substrate was ion exchange strengthened at 500°C for 6 hours in a molten salt bath of 60% KNO3 / 40% NaNO3+0.12% LiNO3 (wt%). In addition, the layers of the optical film structure were deposited according to the vapor deposition conditions set forth in U.S. Patent Publication No. 2020 / 0158916, the main part of which is incorporated herein by reference.

[0205] Reference Figure 3A , provides a graph of first surface reflectance versus wavelength for this comparative example measured at a near normal incidence angle of 8°. It should be noted that this comparative example exhibits high maximum and minimum reflectance oscillations in the 1000 to 1700 nm wavelength band of greater than 7%. Figure 3A It is also apparent that this comparative example exhibits high reflectivity in the near infrared spectrum (eg, over 8% at 1100 nm, about 10% at 1300 nm, and over 11% at 1500 nm).

[0206] Reference Figure 3B , provides a graph of the single-sided reflected color for this comparative example measured at incident angles of 0° to 90° using various optical film structure thickness scaling factors.

[0207] Table 1: Comparative Example 1, transparent product design with reinforced glass ceramic substrate

[0208]

[0209]

[0210] Total thickness(nm): 2374.2

[0211] AR layer (external structure) thickness (nm): 113.0 Low RI AR thickness (nm): 82.7

[0212] Comparative Example 2

[0213] A comparative transparent article including a strengthened glass substrate was prepared for this example, and its structure is shown in Table 2 below. The glass substrate is an ion-exchanged aluminosilicate glass substrate having a thickness of 550 μm and a refractive index of 1.51. The substrate has the following composition: 61.81% SiO2; 3.9% B2O3; 19.69% Al2O3; 12.91% Na2O; 0.018% K2O; 1.43% MgO; 0.019% Fe2O3; and 0.223% SnO2 (based on the weight % of the oxide). A molten salt bath was used to strengthen the substrate to achieve a maximum compressive stress (CS) of 850 MPa and a depth of layer (DOL) of 40 μm. In addition, the layers of the optical film structure were deposited according to the vapor deposition conditions described in U.S. Patent Publication No. 2020 / 0158916, the main part of which is incorporated herein by reference.

[0214] Reference Figure 4A , provides a graph of first surface reflectance versus wavelength for this comparative example measured at a near normal incidence angle of 8°. It should be noted that this comparative example exhibits high maximum and minimum reflectance oscillations in the 1000 to 1700 nm wavelength band of greater than 8%. Figure 4A It is also apparent that this comparative example exhibits high reflectivity in the near infrared spectrum (eg, over 7% at 940 nm, over 12% at 1200 nm, over 13% at 1350 nm, and over 11% at 1500 nm).

[0215] Reference Figure 4B , provides a graph of the single-side reflected color for this comparative example measured at incident angles of 0° to 90° using various optical film structure thickness scaling factors. Figure 4B It can be clearly seen that this comparative example exhibits a color shift less than 4 only for a narrow range of optical film structure thickness scaling factors of about 95 to 100%.

[0216] Table 2: Comparative Example 2, transparent product design with tempered glass substrate

[0217]

[0218]

[0219] Total thickness(nm): 2510.8

[0220] AR layer (external structure) thickness (nm): 312.6 Low RI AR thickness (nm): 116.1

[0221] Comparative Example 3

[0222] A comparative transparent article including a strengthened glass substrate was prepared for this example, and its structure is shown in Table 3 below. The glass substrate is an ion-exchanged aluminosilicate glass substrate having a thickness of 550 μm and a refractive index of 1.51. The substrate has the following composition: 61.81% SiO2; 3.9% B2O3; 19.69% Al2O3; 12.91% Na2O; 0.018% K2O; 1.43% MgO; 0.019% Fe2O3; and 0.223% SnO2 (based on the weight % of the oxide). A molten salt bath was used to strengthen the substrate to achieve a maximum compressive stress (CS) of 850 MPa and a depth of layer (DOL) of 40 μm. In addition, the layers of the optical film structure were deposited according to the vapor deposition conditions described in U.S. Patent Publication No. 2020 / 0158916, the main part of which is incorporated herein by reference.

[0223] Reference Figure 5A , provides a graph of first surface reflectance versus wavelength for this comparative example measured at a near normal incidence angle of 8°. It should be noted that this comparative example exhibits high maximum and minimum reflectance oscillations in the 1000 to 1700 nm wavelength band of greater than 7%. Figure 5A It is also apparent that this comparative example exhibits high reflectivity in the near infrared spectrum (eg, over 11% at 1200 nm, over 17% at 1350 nm, and over 21% at 1550 nm).

[0224] Reference Figure 5B , provides a graph of the single-side reflected color for this comparative example measured at incident angles of 0° to 90° using various optical film structure thickness scaling factors. Figure 5B It can be clearly seen that the color shift exhibited by this comparative example is quite consistent for optical film structure thickness scaling factors of about 75 to 100%, wherein the color shift ranges slightly over 4 for almost all scaling factors.

[0225] Table 3: Comparative Example 3, transparent product design with tempered glass substrate

[0226] layer Material Thickness(nm) Refractive index (550nm) Glass substrate 1.51 1 <![CDATA[SiO2]]> 20 1.476 2 <![CDATA[SiO x N y ]]> 8.14 1.943 3 <![CDATA[SiO2]]> 67.12 1.476 4 <![CDATA[SiO x N y ]]> 21.57 1.943 5 <![CDATA[SiO2]]> 50.82 1.476 6 <![CDATA[SiO x N y ]]> 39.32 1.943 7 <![CDATA[SiO2]]> 26.68 1.476 8 <![CDATA[SiO x N y ]]> 56.09 1.943 9 <![CDATA[SiO2]]> 8 1.476 10 <![CDATA[SiO x N y ]]> 1500 1.943 11 <![CDATA[SiO2]]> 14.56 1.476 12 <![CDATA[SiN y ]]> 38.39 2.014 13 <![CDATA[SiO2]]> 46.3 1.476 14 <![CDATA[SiN y ]]> 25.19 2.014 15 <![CDATA[SiO2]]> 81.14 1.476 16 <![CDATA[SiN y ]]> 24.93 2.014 17 <![CDATA[SiO2]]> 44.65 1.476 18 <![CDATA[SiN y ]]> 152.62 2.014 19 <![CDATA[SiO2]]> 102.28 1.476 medium Air 1

[0227] Total thickness(nm): 2327.8

[0228] AR layer (external structure) thickness (nm): 530.1 Low RI AR thickness (nm): 288.9

[0229] Example 1

[0230] For this example, a transparent article including a strengthened glass ceramic substrate was prepared, and its structure is shown in Table 4 below. The glass ceramic substrate is an ion-exchanged LAS glass ceramic substrate having a thickness of 600 μm and a refractive index of 1.533. In addition, the glass ceramic substrate has the following composition: 74.5% SiO2; 7.53% Al2O3; 2.1% P2O5; 11.3% Li2O; 0.06% Na2O; 0.12% K2O; 4.31% ZrO2; 0.06% Fe2O3; and 0.02% SnO2 (based on the weight % of the oxide). In addition, the glass ceramic substrate was ceramicized according to the following schedule: (a) heating from room temperature to 580°C at 5°C / min; (b) holding at 580°C for 2.75 hours; (c) heating to 755°C at 2.5°C / min; (d) holding at 755°C for 0.75 hours; and (e) cooling to room temperature at a furnace rate. After ceramicization, the glass ceramic substrate was ion exchange strengthened at 500°C for 6 hours in a molten salt bath of 60% KNO3 / 40% NaNO3+0.12% LiNO3 (wt%). In addition, the layers of the optical film structure were deposited according to the vapor deposition conditions set forth in U.S. Patent Publication No. 2020 / 0158916, the main part of which is incorporated herein by reference.

[0231] Referring again to the transparent article of this example, the layers of the optical film structure (e.g., layers 17-23 in Table 4) above the scratch resistant layer (e.g., layer 16 in Table 4) are configured to achieve high shallow layer hardness while not negatively affecting the optical properties of the article (including reflectivity in the visible, IR, and near-IR spectra). It is apparent from the optical film structure design in Table 4 that the medium refractive index layer (SiO x N y Layers 18, 20 and 22) are arranged with the high refractive index layer (SiN y The layers 17, 19 and 21) are adjacent to each other to drive the shallow high hardness level in the product. Similarly, it can be clearly seen from Table 4 that the total thickness of the low refractive index layer (e.g., SiO2 layer 23) in the outer structure of the optical film structure above the scratch resistant layer is minimized to a level less than 25nm, which also helps to drive the shallow high hardness level in the product.

[0232] Reference Fig. 6A, provides a graph of first surface reflectivity versus wavelength for this inventive example measured at a near normal incidence angle of 8°. It should be noted that this example exhibits low maximum and minimum reflectivity oscillations in the 1000 to 1700 nm wavelength band of less than 6%. Also from Fig. 6A It can be clearly seen that this example exhibits a maximum reflectivity of less than 12% in the near infrared spectrum from 1000 to 1700 nm.

[0233] Reference Figure 6B , provides a graph of the single-side reflected color for this inventive example measured at incident angles of 0° to 90° using various optical film structure thickness scaling factors. Figure 6B It can be clearly seen that the color shift exhibited by this inventive example is fairly consistent and less than 4 for a wide range of optical film structure thickness scaling factors from about 70 to 100%.

[0234] Table 4: Example 1, transparent article design with strengthened glass ceramic substrate

[0235]

[0236]

[0237] Total thickness(nm): 2903.7

[0238] AR layer (external structure) thickness (nm): 270.0 Low RI AR thickness (nm): 14

[0239] Example 2

[0240] For this example, a transparent article including a strengthened glass ceramic substrate was prepared, and its structure is shown in Table 5 below. The glass ceramic substrate is an ion-exchanged LAS glass ceramic substrate having a thickness of 600 μm and a refractive index of 1.533. The glass ceramic substrate has the following composition: 74.5% SiO2; 7.53% Al2O3; 2.1% P2O5; 11.3% Li2O; 0.06% Na2O; 0.12% K2O; 4.31% ZrO2; 0.06% Fe2O3; and 0.02% SnO2 (based on weight %) of oxides. In addition, the glass ceramic substrate was ceramized according to the following schedule: (a) heating from room temperature to 580°C at 5°C / min; (b) holding at 580°C for 2.75 hours; (c) heating to 755°C at 2.5°C / min; (d) holding at 755°C for 0.75 hours; and (e) cooling to room temperature at a furnace rate. After ceramization, the glass ceramic substrate was ion exchange strengthened at 500°C for 6 hours in a molten salt bath of 60% KNO3 / 40% NaNO3+0.12% LiNO3 (wt%). The layers of the optical film structure were deposited according to the vapor deposition conditions set forth in U.S. Patent Publication No. 2020 / 0158916, the main part of which is incorporated herein by reference.

[0241] Referring again to the transparent article of this example, the layers of the optical film structure (e.g., layers 17-27 in Table 5) above the scratch resistant layer (e.g., layer 16 in Table 5) are configured to achieve high shallow layer hardness while not negatively affecting the optical properties of the article (including reflectivity in the visible, IR, and near-IR spectra). It is apparent from the optical film structure design in Table 5 that the medium refractive index layer (SiO x N y Layers 18, 20, 22, 24 and 26) are arranged with the high refractive index layer (SiN y The optical film structure of the present invention is adjacent to the scratch-resistant layer 17, 19, 21, 23 and 25) to drive the shallow high hardness level in the product. Similarly, it can be clearly seen from Table 5 that the total thickness of the low refractive index layer (e.g., SiO2 layer 27) in the outer structure of the optical film structure above the scratch-resistant layer is minimized to a level of less than 25nm, which also helps to drive the shallow high hardness level in the product.

[0242] Reference Fig. 7A , provides a graph of first surface reflectivity versus wavelength for this inventive example measured at a near normal incidence angle of 8°. It should be noted that this example exhibits low maximum and minimum reflectivity oscillations in the 1000 to 1700 nm wavelength band of less than 2.5%. Also from Fig. 7A It can be clearly seen that this example exhibits a low maximum reflectivity of less than 6% in the near infrared spectrum from 1000 to 1700 nm.

[0243] Reference Figure 7B , provides a graph of the single-side reflected color for this inventive example measured at incident angles of 0° to 90° using various optical film structure thickness scaling factors. Figure 7B It can be clearly seen that the color shift exhibited by this inventive example is fairly consistent and less than 4 for the full range of optical film structure thickness scaling factors of about 50 to 100% shown in this graph.

[0244] Table 5: Example 2, transparent article design with strengthened glass-ceramic substrate

[0245]

[0246]

[0247] Total thickness(nm): 3096.6

[0248] AR layer (external structure) thickness (nm): 462.9 Low RI AR thickness (nm): 14

[0249] Example 3

[0250] For this example, a transparent article including a strengthened glass ceramic substrate was prepared, and its structure is shown in Table 6 below. The glass ceramic substrate is an ion-exchanged LAS glass ceramic substrate having a thickness of 600 μm and a refractive index of 1.528. In addition, the glass ceramic substrate has the following composition: 74.5% SiO2; 7.53% Al2O3; 2.1% P2O5; 11.3% Li2O; 0.06% Na2O; 0.12% K2O; 4.31% ZrO2; 0.06% Fe2O3; and 0.02% SnO2 (based on the weight % of the oxide). The glass ceramic substrate was ceramized according to the following schedule: (a) heating from room temperature to 580°C at 5°C / min; (b) holding at 580°C for 2.75 hours; (c) heating to 755°C at 2.5°C / min; (d) holding at 755°C for 0.75 hours; and (e) cooling to room temperature at a furnace rate. After ceramization, the glass ceramic substrate was ion exchange strengthened at 500°C for 6 hours in a molten salt bath of 60% KNO3 / 40% NaNO3+0.12% LiNO3 (wt%). The layers of the optical film structure were deposited according to the vapor deposition conditions set forth in U.S. Patent Publication No. 2020 / 0158916, the main part of which is incorporated herein by reference.

[0251] Referring again to the transparent article of this example, the layers of the optical film structure (e.g., layers 17-23 in Table 6) above the scratch resistant layer (e.g., layer 16 in Table 6) are configured to achieve high shallow layer hardness while not negatively affecting the optical properties of the article (including reflectivity in the visible, IR, and near-IR spectra). It is apparent from the optical film structure design of Table 6 that the medium refractive index layer (SiO x N y Layers 18, 20 and 22) are arranged with the high refractive index layer (SiN y Layers 17, 19 and 21) are adjacent to each other to drive the shallow high hardness level in the article. Similarly, it can be seen from Table 6 that the total thickness of the low refractive index layer (e.g., SiO2 layer 24) in the outer structure of the optical film structure above the scratch resistant layer is minimized to a level of less than 25nm, which also helps drive the shallow high hardness level in the article. In addition, it can be seen from Table 6 that the outer structure of this example includes a repeated medium refractive index layer (e.g., layer 23) adjacent to another medium refractive index layer (e.g., layer 22), which can also have a positive impact on the hardness level of the article at the shallow indentation depth.

[0252] Reference Fig. 8A , provides a graph of first surface reflectivity versus wavelength for this inventive example measured at a near normal incidence angle of 8°. It should be noted that this example exhibits low maximum and minimum reflectivity oscillations in the 1000 to 1700 nm wavelength band of less than 2%. Also from Fig. 8A It can be clearly seen that this example exhibits a low maximum reflectivity of less than 5.5% in the near infrared spectrum from 1000 to 1700 nm.

[0253] Reference Figure 8B , provides a graph of the single-side reflected color for this inventive example measured at incident angles of 0° to 90° using various optical film structure thickness scaling factors. Figure 8B It can be clearly seen that the color shift exhibited by this inventive example is fairly consistent and less than 4 for the full range of optical film structure thickness scaling factors from about 40 to 100% shown in this graph.

[0254] Table 6: Example 3, transparent article design with strengthened glass-ceramic substrate

[0255]

[0256]

[0257] Total thickness(nm): 2949.4 AR layer (external structure) thickness (nm): 388.2 Low RI AR thickness (nm): 14

[0258] Mechanical properties of examples 1-3

[0259] Now refer to Fig. 9A , provides a box plot of the average product failure stress measured in the ring-to-ring test for the transparent products of Examples 1-3 and Comparative Example 2 and the control glass-ceramic substrate without the optical film structure. Fig. 9A It can be clearly seen that the inventive examples exhibit an average failure stress level of at least 800 MPa, which is comparable to the bare glass-ceramic substrate without an optical film structure (in Fig. 9A In contrast, the comparative example (Comparative Example 2) exhibited an average fracture stress level of less than 600 MPa, which is much lower than the average fracture stress level of the inventive examples (Examples 1-3).

[0260] Now refer to Fig. 9B and Fig. 9C , provides a graph of the hardness and elastic modulus versus displacement measured in the Berkovich hardness test of the optical film structures of the transparent articles of Examples 1-3. Fig. 9B It can be clearly seen that each of the inventive examples (Examples 1-3) exhibits a hardness of about 15 GPa or more at a shallow indentation depth of 100 to 125 nm. Fig. 9C It can be clearly seen that each of the inventive examples (Examples 1-3) exhibits a maximum elastic modulus in the range of 160-200 GPa, and an elastic modulus of 120-160 GPa at 15% of the total thickness of the optical film structure (about 450 nm for these examples).

[0261] Example 4

[0262] For this example, a transparent article including a strengthened glass ceramic substrate was prepared, and its structure is shown in Table 7 below. The glass ceramic substrate is an ion-exchanged LAS glass ceramic substrate having a thickness of 600 μm and a refractive index of 1.533. The glass ceramic substrate has the following composition: 74.5% SiO2; 7.53% Al2O3; 2.1% P2O5; 11.3% Li2O; 0.06% Na2O; 0.12% K2O; 4.31% ZrO2; 0.06% Fe2O3; and 0.02% SnO2 (based on weight %) of oxides. The glass ceramic substrate was ceramized according to the following schedule: (a) heating from room temperature to 580°C at 5°C / min; (b) holding at 580°C for 2.75 hours; (c) heating to 755°C at 2.5°C / min; (d) holding at 755°C for 0.75 hours; and (e) cooling to room temperature at a furnace rate. After ceramization, the glass ceramic substrate was ion exchange strengthened at 500°C for 6 hours in a molten salt bath of 60% KNO3 / 40% NaNO3+0.12% LiNO3 (wt%). In addition, the layers of the optical film structure were deposited according to the vapor deposition conditions set forth in U.S. Patent Publication No. 2020 / 0158916, the main part of which is incorporated herein by reference.

[0263] Reference Fig. 10A , provides a graph of first surface reflectivity versus wavelength for this inventive example measured at a near normal incidence angle of 8°. It should be noted that this example exhibits low maximum and minimum reflectivity oscillations of less than 2% in the 1000 to 1700 nm wavelength band.

[0264] Reference Fig. 10B , provides a graph of the single-side reflected color for this inventive example measured at incident angles of 0° to 90° using various optical film structure thickness scaling factors. Fig. 10B It can be clearly seen that the color shift exhibited by this inventive example is fairly consistent and less than 4 for the full range of optical film structure thickness scaling factors from about 35 to 100% shown in this graph.

[0265] Table 7: Example 4, transparent article design with strengthened glass ceramic substrate

[0266] layer Material Thickness(nm) Refractive index (550nm) Glass Ceramics substrate 1.533 1 <![CDATA[SiO2]]> 25 1.476 2 <![CDATA[SiO x N y ]]> 14.37 1.744 3 <![CDATA[SiO2]]> 66 1.476 4 <![CDATA[SiO x N y ]]> 26.64 1.744 5 <![CDATA[SiO2]]> 58.9 1.476 6 <![CDATA[SiO x N y ]]> 40.48 1.744 7 <![CDATA[SiO2]]> 40.9 1.476 8 <![CDATA[SiO x N y ]]> 56.21 1.744 9 <![CDATA[SiO2]]> 22.2 1.476 10 <![CDATA[SiO x N y ]]> 69.21 1.744 11 <![CDATA[SiO2]]> 8 1.476 12 <![CDATA[SiO x N y ]]> 1960 1.744 13 <![CDATA[SiO2]]> 18 1.476 medium Air 1

[0267] Total thickness(nm): 2405.9 AR layer thickness for low RI (nm): 18.0

[0268] Example 5

[0269] For this example, a transparent article including a strengthened glass ceramic substrate was prepared, and its structure is shown in Table 8 below. The glass ceramic substrate is an ion-exchanged LAS glass ceramic substrate having a thickness of 600 μm and a refractive index of 1.533. The glass ceramic substrate has the following composition: 74.5% SiO2; 7.53% Al2O3; 2.1% P2O5; 11.3% Li2O; 0.06% Na2O; 0.12% K2O; 4.31% ZrO2; 0.06% Fe2O3; and 0.02% SnO2 (based on weight %) of oxides. The glass ceramic substrate was ceramized according to the following schedule: (a) heating from room temperature to 580°C at 5°C / min; (b) holding at 580°C for 2.75 hours; (c) heating to 755°C at 2.5°C / min; (d) holding at 755°C for 0.75 hours; and (e) cooling to room temperature at a furnace rate. After ceramization, the glass ceramic substrate was ion exchange strengthened at 500°C for 6 hours in a molten salt bath of 60% KNO3 / 40% NaNO3+0.12% LiNO3 (wt%). In addition, the layers of the optical film structure were deposited according to the vapor deposition conditions set forth in U.S. Patent Publication No. 2020 / 0158916, the main part of which is incorporated herein by reference.

[0270] Reference Fig.11A , provides a graph of first surface reflectivity versus wavelength for this inventive example measured at a near normal incidence angle of 8°. It should be noted that this example exhibits low maximum and minimum reflectivity oscillations in the 1000 to 1700 nm wavelength band of less than 2.5%.

[0271] Reference Fig. 11B , provides a graph of the single-side reflected color for this inventive example measured at incident angles of 0° to 90° using various optical film structure thickness scaling factors. Fig. 11B It can be clearly seen that the color shift exhibited by this inventive example is fairly consistent and less than 4 for the full range of optical film structure thickness scaling factors from about 45 to 100% shown in this graph.

[0272] Table 8: Example 5, transparent article design with strengthened glass ceramic substrate

[0273]

[0274]

[0275] Total thickness(nm): 3174.7

[0276] AR layer (external structure) thickness (nm): 796.4 Low RI AR thickness (nm): 95

[0277] Example 6

[0278] For this example, a transparent article including a strengthened glass substrate was prepared, and its structure is shown in Table 9 below. In this example, the substrate used is Glass 3 (commercially available from Corning, Inc.). Examples of glass 3 compositions are described in U.S. Patent Nos. 7,666,511, 4,483,700, and 5,674,790, the main contents of which are incorporated herein by reference. The layers of the optical film structure are deposited according to the vapor deposition conditions set forth in U.S. Patent Publication No. 2020 / 0158916, the main portion of which is incorporated herein by reference.

[0279] Reference Fig. 12A , provides a graph of first surface reflectance versus wavelength for this inventive example measured at a near normal incidence angle of 8°. It should be noted that this example exhibits low maximum and minimum reflectance oscillations of less than 3% in the 1000 to 1700 nm wavelength band.

[0280] Reference Fig. 12B , provides a graph of the single-side reflected color for this inventive example measured at incident angles of 0° to 90° using various optical film structure thickness scaling factors. Fig. 12B It can be clearly seen that the color shift exhibited by this inventive example is fairly consistent and less than 4 for the full range of optical film structure thickness scaling factors from about 45 to 100% shown in this graph.

[0281] Table 9: Example 6, transparent article design with strengthened glass substrate

[0282]

[0283] Total thickness(nm): 2698.4

[0284] AR layer (external structure) thickness (nm): 251.0 Low RI AR thickness (nm): 190.0

[0285] Example 7

[0286] For this example, a transparent article including a strengthened glass ceramic substrate was prepared, and its structure is shown in Table 10 below. The glass ceramic substrate is an ion-exchanged LAS glass ceramic substrate having a thickness of 600 μm and a refractive index of 1.533. The glass ceramic substrate has the following composition: 74.5% SiO2; 7.53% Al2O3; 2.1% P2O5; 11.3% Li2O; 0.06% Na2O; 0.12% K2O; 4.31% ZrO2; 0.06% Fe2O3; and 0.02% SnO2 (based on weight %) of oxides. The glass ceramic substrate was ceramized according to the following schedule: (a) heating from room temperature to 580°C at 5°C / min; (b) holding at 580°C for 2.75 hours; (c) heating to 755°C at 2.5°C / min; (d) holding at 755°C for 0.75 hours; and (e) cooling to room temperature at a furnace rate. After ceramization, the glass ceramic substrate was ion exchange strengthened at 500°C for 6 hours in a molten salt bath of 60% KNO3 / 40% NaNO3+0.12% LiNO3 (wt%). In addition, the layers of the optical film structure were deposited according to the vapor deposition conditions set forth in U.S. Patent Publication No. 2020 / 0158916, the main part of which is incorporated herein by reference.

[0287] Reference Fig.13A , provides a graph of first surface reflectivity versus wavelength for this inventive example measured at a near normal incidence angle of 8°. It should be noted that this example exhibits low maximum and minimum reflectivity oscillations of less than 4% in the 1000 to 1700 nm wavelength band.

[0288] Reference Fig. 13B , provides a graph of the single-side reflected color for this inventive example measured at incident angles of 0° to 90° using various optical film structure thickness scaling factors. Fig. 13B It can be clearly seen that the color shift exhibited by this inventive example is fairly consistent and less than 4 for the full range of optical film structure thickness scaling factors from about 65 to 100% shown in this graph.

[0289] Table 10: Example 7, transparent article design with strengthened glass ceramic substrate

[0290]

[0291]

[0292] Total thickness(nm): 2544.0

[0293] AR layer (external structure) thickness (nm): 165.7 Low RI AR thickness (nm): 141.6

[0294] Example 8

[0295] For this example, a transparent article including a strengthened glass ceramic substrate was prepared, and its structure is shown in Table 11 below. The glass ceramic substrate is an ion-exchanged LAS glass ceramic substrate having a thickness of 600 μm and a refractive index of 1.533. The glass ceramic substrate has the following composition: 74.5% SiO2; 7.53% Al2O3; 2.1% P2O5; 11.3% Li2O; 0.06% Na2O; 0.12% K2O; 4.31% ZrO2; 0.06% Fe2O3; and 0.02% SnO2 (based on weight %) of the oxide. The glass ceramic substrate was ceramized according to the following schedule: (a) heating from room temperature to 580°C at 5°C / min; (b) holding at 580°C for 2.75 hours; (c) heating to 755°C at 2.5°C / min; (d) holding at 755°C for 0.75 hours; and (e) cooling to room temperature at a furnace rate. After ceramization, the glass ceramic substrate was ion exchange strengthened at 500°C for 6 hours in a molten salt bath of 60% KNO3 / 40% NaNO3+0.12% LiNO3 (wt%). In addition, the layers of the optical film structure were deposited according to the vapor deposition conditions set forth in U.S. Patent Publication No. 2020 / 0158916, the main part of which is incorporated herein by reference.

[0296] Reference Fig.14A , provides a graph of first surface reflectivity versus wavelength for this inventive example measured at a near normal incidence angle of 8°. It should be noted that this example exhibits low maximum and minimum reflectivity oscillations in the 1000 to 1700 nm wavelength band of less than about 3%.

[0297] Reference Fig. 14B , provides a graph of the single-side reflected color for this inventive example measured at incident angles of 0° to 90° using various optical film structure thickness scaling factors. Fig. 14B It can be clearly seen that the color shift exhibited by this inventive example is fairly consistent and less than 4 for the full range of optical film structure thickness scaling factors of about 70 to 100% shown in this graph.

[0298] Table 11: Example 8, transparent article design with strengthened glass ceramic substrate

[0299] layer Material Thickness(nm) Refractive index (550nm) Glass Ceramics substrate 1.533 1 <![CDATA[SiO2]]> 25 1.476 2 <![CDATA[SiO x N y ]]> 13.7 1.829 3 <![CDATA[SiO2]]> 66 1.476 4 <![CDATA[SiO x N y ]]> 25.4 1.829 5 <![CDATA[SiO2]]> 58.9 1.476 6 <![CDATA[SiO x N y ]]> 38.6 1.829 7 <![CDATA[SiO2]]> 40.9 1.476 8 <![CDATA[SiO x N y ]]> 53.6 1.829 9 <![CDATA[SiO2]]> 22.2 1.476 10 <![CDATA[SiO x N y ]]> 66 1.829 11 <![CDATA[SiO2]]> 8 1.476 12 <![CDATA[SiO x N y ]]> 1960 1.829 13 <![CDATA[SiN y ]]> 8.25 2.042 14 <![CDATA[SiO x N y ]]> 98.33 1.744 15 <![CDATA[SiO2]]> 99.92 1.476 medium Air 1

[0300] Total thickness(nm): 2584.8

[0301] AR layer (external structure) thickness (nm): 206.5 Low RI AR thickness (nm): 99.9

[0302] Example 9

[0303] For this example, a transparent article including a strengthened glass ceramic substrate was prepared, and its structure is shown in Table 12 below. The glass ceramic substrate is an ion-exchanged LAS glass ceramic substrate having a thickness of 600 μm and a refractive index of 1.533. The glass ceramic substrate has the following composition: 74.5% SiO2; 7.53% Al2O3; 2.1% P2O5; 11.3% Li2O; 0.06% Na2O; 0.12% K2O; 4.31% ZrO2; 0.06% Fe2O3; and 0.02% SnO2 (based on weight %) of the oxide. The glass ceramic substrate was ceramized according to the following schedule: (a) heating from room temperature to 580°C at 5°C / min; (b) holding at 580°C for 2.75 hours; (c) heating to 755°C at 2.5°C / min; (d) holding at 755°C for 0.75 hours; and (e) cooling to room temperature at a furnace rate. After ceramization, the glass ceramic substrate was ion exchange strengthened at 500°C for 6 hours in a molten salt bath of 60% KNO3 / 40% NaNO3+0.12% LiNO3 (wt%). In addition, the layers of the optical film structure were deposited according to the vapor deposition conditions set forth in U.S. Patent Publication No. 2020 / 0158916, the main part of which is incorporated herein by reference.

[0304] Reference Fig.15A , provides a graph of first surface reflectance versus wavelength for this inventive example measured at a near normal incidence angle of 8°. This example exhibits a low maximum reflectance in the 1000 to 1700 nm wavelength band of less than 10.5%.

[0305] Reference Fig. 15B , provides a graph of the single-side reflected color for this inventive example measured at incident angles of 0° to 90° using various optical film structure thickness scaling factors. Fig. 15B It can be clearly seen that the color shift exhibited by this inventive example is fairly consistent and less than 4 for the full range of optical film structure thickness scaling factors from about 65 to 100% shown in this graph.

[0306] Table 12: Example 9, transparent article design with strengthened glass ceramic substrate

[0307]

[0308]

[0309] Total thickness(nm): 2699.9

[0310] AR layer (external structure) thickness (nm): 321.6 Low RI AR thickness (nm): 93.0

[0311] Example 10

[0312] For this example, a transparent article including a strengthened glass ceramic substrate was prepared, and its structure is shown in Table 13 below. The glass ceramic substrate is an ion-exchanged LAS glass ceramic substrate having a thickness of 600 μm and a refractive index of 1.533. The glass ceramic substrate has the following composition: 74.5% SiO2; 7.53% Al2O3; 2.1% P2O5; 11.3% Li2O; 0.06% Na2O; 0.12% K2O; 4.31% ZrO2; 0.06% Fe2O3; and 0.02% SnO2 (based on weight %) of the oxide. In addition, the glass ceramic substrate was ceramized according to the following schedule: (a) heating from room temperature to 580°C at 5°C / min; (b) holding at 580°C for 2.75 hours; (c) heating to 755°C at 2.5°C / min; (d) holding at 755°C for 0.75 hours; and (e) cooling to room temperature at a furnace rate. After ceramization, the glass ceramic substrate was ion exchange strengthened at 500°C for 6 hours in a molten salt bath of 60% KNO3 / 40% NaNO3+0.12% LiNO3 (wt%). The layers of the optical film structure were deposited according to the vapor deposition conditions set forth in U.S. Patent Publication No. 2020 / 0158916, the main part of which is incorporated herein by reference.

[0313] Referring again to the transparent article of this example, the layers of the optical film structure (e.g., layers 13-17 in Table 13) above the scratch resistant layer (e.g., layer 12 in Table 13) are configured to achieve high shallow layer hardness while not negatively affecting the optical properties of the article (including reflectivity in the visible, IR, and near-IR spectra). It is apparent from the optical film structure design of Table 13 that the medium refractive index layer (SiO x N y Layers 14 and 16) are arranged to be aligned with the high refractive index layer (SiN y Similarly, it can be clearly seen from Table 13 that the total thickness of the low refractive index layer (e.g., SiO2 layer 17) in the outer structure of the optical film structure above the scratch resistant layer is minimized to a level less than 75nm, which also helps to drive the shallow high hardness level in the product.

[0314] Reference Fig.16A, provides a graph of first surface reflectance versus wavelength for this example measured at a near normal incidence angle of 8°. This example exhibits a maximum reflectance of less than 11.5% in the near IR spectrum from 1000 to 1700 nm.

[0315] Reference Fig. 16B , provides a graph of the single-side reflected color for this inventive example measured at incident angles of 0° to 90° using various optical film structure thickness scaling factors. Fig. 16B It can be clearly seen that the color shift exhibited by this inventive example is fairly consistent and less than 4 for the full range of optical film structure thickness scaling factors of about 70 to 100% shown in this graph.

[0316] Table 13: Example 10, transparent article design with strengthened glass ceramic substrate

[0317] layer Material Thickness(nm) Refractive index (550nm) Glass Ceramics substrate 1.533 1 <![CDATA[SiO2]]> 25 1.476 2 <![CDATA[SiO x N y ]]> 13.7 1.829 3 <![CDATA[SiO2]]> 66 1.476 4 <![CDATA[SiO x N y ]]> 25.4 1.829 5 <![CDATA[SiO2]]> 58.9 1.476 6 <![CDATA[SiO x N y ]]> 38.6 1.829 7 <![CDATA[SiO2]]> 40.9 1.476 8 <![CDATA[SiO x N y ]]> 53.6 1.829 9 <![CDATA[SiO2]]> 22.2 1.476 10 <![CDATA[SiO x N y ]]> 66 1.829 11 <![CDATA[SiO2]]> 8 1.476 12 <![CDATA[SiO x N y ]]> 1960 1.829 13 <![CDATA[SiN y ]]> 20.8 2.042 14 <![CDATA[SiO x N y ]]> 23.4 1.744 15 <![CDATA[SiN y ]]> 141.5 2.042 16 <![CDATA[SiO x N y ]]> 59.9 1.744 17 <![CDATA[SiO2]]> 60 1.476 medium Air 1

[0318] Total thickness(nm): 2684.0

[0319] AR layer (external structure) thickness (nm): 305.7 Low RI AR thickness (nm): 60.0

[0320] Example 11

[0321] For this example, a transparent article including a strengthened glass ceramic substrate was prepared, and its structure is shown in Table 14 below. The glass ceramic substrate is an ion-exchanged LAS glass ceramic substrate having a thickness of 600 μm and a refractive index of 1.533. The glass ceramic substrate has the following composition: 74.5% SiO2; 7.53% Al2O3; 2.1% P2O5; 11.3% Li2O; 0.06% Na2O; 0.12% K2O; 4.31% ZrO2; 0.06% Fe2O3; and 0.02% SnO2 (based on weight %) of the oxide. The glass ceramic substrate was ceramized according to the following schedule: (a) heating from room temperature to 580°C at 5°C / min; (b) holding at 580°C for 2.75 hours; (c) heating to 755°C at 2.5°C / min; (d) holding at 755°C for 0.75 hours; and (e) cooling to room temperature at a furnace rate. After ceramization, the glass ceramic substrate was ion exchange strengthened at 500°C for 6 hours in a molten salt bath of 60% KNO3 / 40% NaNO3+0.12% LiNO3 (wt%). In addition, the layers of the optical film structure were deposited according to the vapor deposition conditions set forth in U.S. Patent Publication No. 2020 / 0158916, the main part of which is incorporated herein by reference.

[0322] Reference Fig.17A , provides a graph of first surface reflectance versus wavelength for this inventive example measured at a near normal incidence angle of 8°. This example exhibits a low maximum reflectance in the range of 1000 to 1700 nm of less than 10%.

[0323] Reference Fig. 17B , provides a graph of the single-side reflected color for this inventive example measured at incident angles of 0° to 90° using various optical film structure thickness scaling factors. Fig. 17B It can be clearly seen that the color shift exhibited by this inventive example is fairly consistent and less than 4 for the full range of optical film structure thickness scaling factors of about 80 to 100% shown in this graph.

[0324] Table 14: Example 11, transparent article design with strengthened glass ceramic substrate

[0325]

[0326]

[0327] Total thickness(nm): 2726.1

[0328] AR layer (external structure) thickness (nm): 287.8 Low RI AR thickness (nm): 104.0

[0329] Example 12

[0330] For this example, a transparent article including a strengthened glass ceramic substrate was prepared, and its structure is shown in Table 15 below. The glass ceramic substrate is an ion-exchanged LAS glass ceramic substrate having a thickness of 600 μm and a refractive index of 1.533. The glass ceramic substrate has the following composition: 74.5% SiO2; 7.53% Al2O3; 2.1% P2O5; 11.3% Li2O; 0.06% Na2O; 0.12% K2O; 4.31% ZrO2; 0.06% Fe2O3; and 0.02% SnO2 (based on weight %) of the oxide. The glass ceramic substrate was ceramized according to the following schedule: (a) heating from room temperature to 580°C at 5°C / min; (b) holding at 580°C for 2.75 hours; (c) heating to 755°C at 2.5°C / min; (d) holding at 755°C for 0.75 hours; and (e) cooling to room temperature at a furnace rate. After ceramization, the glass ceramic substrate was ion exchange strengthened at 500°C for 6 hours in a molten salt bath of 60% KNO3 / 40% NaNO3+0.12% LiNO3 (wt%). In addition, the layers of the optical film structure were deposited according to the vapor deposition conditions set forth in U.S. Patent Publication No. 2020 / 0158916, the main part of which is incorporated herein by reference.

[0331] Reference Fig.18A , provides a graph of first surface reflectance versus wavelength for this inventive example measured at a near normal incidence angle of 6°. It should be noted that this example exhibits a low reflectance in the 1000 to 1700 nm wavelength band of less than 15%.

[0332] Reference Fig.18B , provides a graph of the single-sided reflected color for this inventive example measured at incident angles of 0° to 90° without utilizing an optical film structure thickness scaling factor (ie, a thickness scaling factor of 100%).

[0333] Table 15: Example 12, transparent article design with strengthened glass ceramic substrate

[0334] layer Material Thickness(nm) Refractive index (550nm) Glass Ceramics substrate 1.533 1 <![CDATA[SiO2]]> 25.0 1.476 2 <![CDATA[SiO x N y ]]> 14.0 1.829 3 <![CDATA[SiO2]]> 51.2 1.476 4 <![CDATA[SiO x N y ]]> 30.7 1.829 5 <![CDATA[SiO2]]> 30.1 1.476 6 <![CDATA[SiO x N y ]]> 49.2 1.829 7 <![CDATA[SiO2]]> 8.9 1.476 8 <![CDATA[SiO x N y ]]> 2002 1.829 9 <![CDATA[SiO2]]> 15.2 1.476 10 <![CDATA[SiN y ]]> 35.2 2.058 11 <![CDATA[SiO2]]> 23.1 1.476 12 <![CDATA[SiN y ]]> 143.0 2.058 13 <![CDATA[SiO2]]> 96.7 1.476 medium Air 1

[0335] Total thickness(nm): 2523.8

[0336] AR layer (external structure) thickness (nm): 313.2 Low RI AR thickness (nm): 135.1

[0337] Example 13

[0338] For this example, a transparent article including a strengthened glass ceramic substrate was prepared, and its structure is shown in Table 16 below. The glass ceramic substrate is an ion-exchanged LAS glass ceramic substrate having a thickness of 600 μm and a refractive index of 1.533. The glass ceramic substrate has the following composition: 74.5% SiO2; 7.53% Al2O3; 2.1% P2O5; 11.3% Li2O; 0.06% Na2O; 0.12% K2O; 4.31% ZrO2; 0.06% Fe2O3; and 0.02% SnO2 (based on weight %) of the oxide. The glass ceramic substrate was ceramized according to the following schedule: (a) heating from room temperature to 580°C at 5°C / min; (b) holding at 580°C for 2.75 hours; (c) heating to 755°C at 2.5°C / min; (d) holding at 755°C for 0.75 hours; and (e) cooling to room temperature at a furnace rate. After ceramization, the glass ceramic substrate was ion exchange strengthened at 500°C for 6 hours in a molten salt bath of 60% KNO3 / 40% NaNO3+0.12% LiNO3 (wt%). In addition, the layers of the optical film structure were deposited according to the vapor deposition conditions set forth in U.S. Patent Publication No. 2020 / 0158916, the main part of which is incorporated herein by reference.

[0339] Referring again to the transparent article of this example, the layers of the optical film structure (e.g., layers 9-14 in Table 16) above the scratch resistant layer (e.g., layer 8 in Table 16) are configured to achieve high shallow layer hardness without negatively affecting the optical properties of the article (including reflectivity in the visible, IR, and near-IR spectra). It is apparent from the optical film structure design of Table 16 that the medium refractive index layer (SiO x N y Layers 9, 11 and 13) are arranged with the high refractive index layer (SiN y The layers 10 and 12) are adjacent to each other to drive the shallow high hardness level in the product. Similarly, it can be clearly seen from Table 13 that the total thickness of the low refractive index layer (e.g., SiO2 layer 14) in the outer structure of the optical film structure above the scratch resistant layer is minimized to a level less than 75nm, which also helps to drive the shallow high hardness level in the product.

[0340] Reference Fig.19A , provides a graph of first surface reflectance versus wavelength for this inventive example measured at a near normal incidence angle of 6°. It should be noted that this example exhibits a maximum reflectance in the 1000 to 1700 nm wavelength band of less than about 15%.

[0341] Reference Fig.19B, provides a graph of the single-sided reflected color for this inventive example measured at incident angles of 0° to 90° without utilizing an optical film structure thickness scaling factor (ie, a thickness scaling factor of 100%).

[0342] Table 16: Example 13, transparent article design with strengthened glass ceramic substrate

[0343]

[0344]

[0345] Total thickness(nm): 2492.9

[0346] AR layer (external structure) thickness (nm): 283.9 Low RI AR thickness (nm): 60.0

[0347] Example 14

[0348] For this example, a transparent article including a strengthened glass substrate was prepared, and its structure is shown in Table 17 below. In this example, the substrate used is Glass 3 (commercially available from Corning, Inc.). Examples of glass 3 compositions are described in U.S. Patent Nos. 7,666,511, 4,483,700, and 5,674,790, the major portions of which are incorporated herein by reference. The layers of the optical film structure are deposited according to the vapor deposition conditions set forth in U.S. Patent Publication No. 2020 / 0158916, the major portions of which are incorporated herein by reference. In addition, the layers of the optical film structure are deposited according to the vapor deposition conditions set forth in U.S. Patent Publication No. 2020 / 0158916, the major portions of which are incorporated herein by reference.

[0349] Reference Fig. 20A , provides a graph of first surface reflectance versus wavelength for this inventive example measured at a near normal incidence angle of 8°. It should be noted that this example exhibits a maximum reflectance in the 1000 to 1700 nm wavelength band of less than about 10%.

[0350] Reference Fig. 20B , provides a graph of the single-side reflected color for this inventive example measured at incident angles of 0° to 90° using various optical film structure thickness scaling factors. Fig. 20B It can be clearly seen that the color shift exhibited by this inventive example is fairly consistent and less than 4 for the full range of optical film structure thickness scaling factors of about 50 to 100% shown in this graph.

[0351] Table 17: Example 14, transparent article design with strengthened glass substrate

[0352]

[0353]

[0354]

[0355] Total thickness(nm): 2544.0

[0356] AR layer (external structure) thickness (nm): 1147.6 Low RI AR thickness (nm): 118.1

[0357] Summary of Comparative Example 1-3 and Example 1-14

[0358] Now refer to Fig.21 , a table summarizing the optical and mechanical properties of comparative examples and inventive examples (Comparative Examples 1-3 and Examples 1-14) of the present disclosure is provided. In Table 21, various reflectivity properties are provided (e.g., first surface average reflectivity ("First Surface Average %R (Visible Photopic, Y, 6 degree AOI)"), first surface average reflectivity in the near IR spectrum from 1000 to 1700 nm ("%R (1000-1700nm)"), etc.). The refractive index of the scratch resistant layer of each of the designs is also provided (designated as "Hard Layer Refractive Index"). In addition, various dimensional attributes are provided for the outer structure of the optical film structure above the scratch resistant layer ("AR layer thickness: (nm)"), the percentage of silicon nitride in the outer structure ("%SiN in AR layer"), etc. x ”), refractive index of low RI layers in the outer structure (“Low n in AR stack (non-top)”), total thickness of low RI layers in the outer structure (“Total low RI* (e.g., SiO2) in AR layers: (nm)”), and thickness of the capping layer (“Top SiO2 thickness”)). Regarding color uniformity, the table also provides a range of scaling factors associated with color shifts less than 4 (“Thickness scaling range with 0-90AOI color shift <4”). Finally, various Berkovich hardness values ​​are provided for specific indentation depths of 100nm (“H100(GPa)-Expt.”), 125nm (“H125(GPa)-Expt.”), and 500nm (“H500(GPa)-Expt.”), as well as the maximum hardness value over the entire indentation depth range (“Hmax(GPa)-Expt.”).

[0359] from Fig.21It can be clearly seen that the inventive examples of the present disclosure (e.g., Examples 1-3 and 10) exhibit high shallow hardness of about 15 GPa or more at an indentation depth of 100 to 125 nm, while the comparative examples do not exhibit these levels of hardness at these shallow indentation depths. Fig.21 It can also be seen that compared with the comparative examples, the inventive examples (e.g., Examples 1-3 and 10) also exhibit low reflectivity levels in the visible light (e.g., photopic reflectivity), IR (e.g., 940nm), and near IR (e.g., 1000 to 1700nm) spectra.

[0360] from Fig.21 It can also be seen from the preceding paragraphs that each of the transparent articles uses a glass-ceramic substrate. However, it is believed that the mechanical and optical properties of the inventive examples (including high shallow hardness and low reflectivity in the visible, IR and near-IR spectra) will also be exhibited by transparent articles having an optical film structure consistent with the principles of the present disclosure and using other types of substrates (including ceramic substrates, glass substrates, sapphire substrates, strengthened glass substrates and strengthened glass-ceramic substrates). For example, a shallow high hardness level is observed on a transparent article using a glass substrate, which is comparable to the hardness level of some of the aforementioned inventive examples (including Examples 1-3 and 10). In addition, from an optical point of view, the inner structure (e.g., inner structure 130b) of the optical film structure (e.g., optical film structure 120) of these transparent articles can be configured to have layer materials and thicknesses according to impedance matching standards to accommodate the difference in refractive index of the glass-ceramic substrate and the refractive index of other specific substrate types (e.g., ceramic substrates, glass substrates, sapphire substrates, strengthened glass substrates and strengthened glass-ceramic substrates) to ensure that it has comparable optical performance (including low reflectivity in the visible, IR and near-IR spectra).

[0361] Example 15

[0362] In this example, four transparent articles having an optical film structure configured according to the glass-ceramic substrate and the optical film structure (see below) of Table 18 are the subject of stress modeling. More specifically, these articles are modeled and the average ROR failure strength is evaluated considering the residual compressive stress and elastic modulus level of their optical film structure. In addition, these four articles use the optical film structure of Table 18, which is further configured to have SiO x N y The high RI layer causes the optical film structure to exhibit elastic modulus levels of 140 GPa (Example 15C1), 150 GPa (Example 15C2), 160 GPa (Example 15C3) and 170 GPa (Example 15C4), respectively.

[0363] The following assumptions were made when modeling in this example. For the transparent article of the present disclosure having a rigid and hard optical film structure and a glass-ceramic substrate, the applied strain required to propagate a pre-existing defect in the optical film structure is much lower than the strain itself required to propagate a pre-existing defect in the substrate, primarily because the brittle optical film structure is more rigid than the glass-ceramic substrate. Therefore, assuming that the optical film structure fails first, once the crack driving force exceeds the fracture resistance of the glass-ceramic substrate, the crack will penetrate the substrate, leading to eventual catastrophic failure of the system. Then, numerical modeling based on fracture mechanics (via finite element analysis) is performed, and a series of cracks are inserted into the sample, and when the crack tip stress intensity factor (K I ) is equal to the fracture toughness (K IC ), the strain level is determined. The average retained strength is then calculated based on an assumed defect distribution in the substrate with cracks ranging in size from 0.1 to 2.5 μm.

[0364] Table 18: Example 15, transparent article design with strengthened glass ceramic substrate

[0365]

[0366] Now refer to Fig. 22 , a graph of the average article failure stress (MPa) measured in the ROR test and the optical film structure residual stress (MPa) modeled for transparent articles of the optical film structure of this example with different elastic modulus values ​​(Examples 15C1-15C4) is provided. It can be seen from the graph that maintaining an optical film structure residual stress of at least 700 MPa and controlling the elastic modulus of the optical film structure to 170 GPa or less can ensure a failure stress of the optical film structure of at least 750 MPa. In addition, if the elastic modulus of the optical film structure is maintained at about 140 GPa to about 170 GPa, increasing the residual compressive stress in the optical film structure tends to increase the average failure stress from 750 MPa to a level far above 850 MPa.

[0367] Example 16

[0368] For this example, a transparent article including a strengthened glass ceramic substrate was prepared, and its structure is shown in Table 20 below. The glass ceramic substrate is an ion-exchanged LAS glass ceramic substrate having a thickness of 600 μm and a refractive index of 1.533. In addition, the glass ceramic substrate has the following composition: 74.5% SiO2; 7.53% Al2O3; 2.1% P2O5; 11.3% Li2O; 0.06% Na2O; 0.12% K2O; 4.31% ZrO2; 0.06% Fe2O3; and 0.02% SnO2 (based on weight %) of the oxide. In addition, the glass ceramic substrate was ceramicized according to the following schedule: (a) heating from room temperature to 580°C at 5°C / min; (b) holding at 580°C for 2.75 hours; (c) heating to 755°C at 2.5°C / min; (d) holding at 755°C for 0.75 hours; and (e) cooling to room temperature at a furnace rate. After ceramicization, the glass ceramic substrate was ion exchange strengthened at 500°C for 6 hours in a molten salt bath of 60% KNO3 / 40% NaNO3+0.12% LiNO3 (wt%). In addition, the layers of the optical film structure were deposited according to the vapor deposition conditions set forth in U.S. Patent Publication No. 2020 / 0158916, the main part of which is incorporated herein by reference.

[0369] Referring again to the transparent article of this example (designated Example 16), the layers of the optical film structure (e.g., layers 17-23 in Table 20) above the scratch resistant layer (e.g., layer 16 in Table 20) are configured to achieve high shallow layer hardness while not negatively affecting the optical properties of the article (including reflectivity in the visible, IR, and near-IR spectra). It is apparent from the optical film structure design of Table 20 that the medium refractive index layer (SiO x N y Layers 18, 20 and 22) are arranged with the high refractive index layer (SiN y The layers 17, 19 and 21) are adjacent to each other to drive the shallow high hardness level in the product. Similarly, it can be clearly seen from Table 20 that the total thickness of the low refractive index layer (e.g., SiO2 layer 23) in the outer structure of the optical film structure above the scratch resistant layer is minimized to a level of less than 25nm, which also helps to drive the shallow high hardness level in the product.

[0370] Some mechanical pointers of Example 16 include measured nanoindentation hardness at 100nm depth = 19.0GPa, hardness at 125nm depth = 19.4GPa, hardness at 500nm depth = 17.0GPa, and a maximum modulus of 190GPa. The modulus at a depth equal to 15% of the thickness of the optical film structure (for Example 16, the depth is about 440nm) is equal to 130GPa.

[0371] The ring-to-ring strength of Example 16 was tested to an average of 960 MPa when residual compressive stress in the optical film structure was manufactured to 950-1000 MPa. In addition, the four-point bend strength of this example was measured, and during this test, when the optical film structure was placed on a tensile surface or a compressive surface, the average four-point bend test strength was measured to be greater than 700 MPa. Example 16 (two bars on the right) of the optical film structure in compression and tension was compared to a control sample with only an easy-to-clean coating (designated as Comparative Example 16), and this four-point bend test data for Example 16 is shown in Fig.23A (no effect on the mechanics of this test) (the two bars on the left represent the control samples in compression and tension on the ETC side). There is no statistical difference between the control and the Example 16 samples with the optical film structure, indicating that the Example 16 optical film structure has complete strength retention due to the designed modulus and compressive stress in the film structure, and the optimized properties combined with the glass-ceramic substrate. This is in contrast to the typical average 4-point bend test strength of less than 400 MPa for the Comparative Example 3 optical film structure on the chemically strengthened glass substrate when the surface of the optical film structure is in tension (not shown in the figure).

[0372] Table 20: Example 16, Transparent Article Design with Strengthened Glass Ceramic Substrate

[0373] layer Material Thickness(nm) Refractive index (550nm) Glass Ceramics substrate 1.533 1 <![CDATA[SiO2]]> 25.0 1.476 2 <![CDATA[SiO x N y ]]> 16.2 1.744 3 <![CDATA[SiO2]]> 67.9 1.476 4 <![CDATA[SiO x N y ]]> 25.3 1.744 5 <![CDATA[SiO2]]> 70.9 1.476 6 <![CDATA[SiO x N y ]]> 33.4 1.744 7 <![CDATA[SiO2]]> 61.7 1.476 8 <![CDATA[SiO x N y ]]> 44.1 1.744 9 <![CDATA[SiO2]]> 47.4 1.476 10 <![CDATA[SiO x N y ]]> 56.7 1.744 11 <![CDATA[SiO2]]> 32.0 1.476 12 <![CDATA[SiO x N y ]]> 68.9 1.744 13 <![CDATA[SiO2]]> 18.3 1.476 14 <![CDATA[SiO x N y ]]> 76.6 1.744 15 <![CDATA[SiO2]]> 8.0 1.476 16 <![CDATA[SiO x N y ]]> 2000.0 1.744 17 <![CDATA[SiN x ]]> 15.3 2.058 18 <![CDATA[SiO x N y ]]> 37.7 1.744 19 <![CDATA[SiN x ]]> 57.3 2.058 20 <![CDATA[SiO x N y ]]> 8.0 1.744 21 <![CDATA[SiN x ]]> 66.2 2.058 22 <![CDATA[SiO x N y ]]> 76.2 1.744 23 <![CDATA[SiO2]]> 14.0 1.476 medium Air 1

[0374] Total thickness: 2926.8 AR layer (external structure) thickness (nm): 274.6 Low RI AR thickness (nm): 14

[0375] Key optical indicators for Example 16 include first surface photopic average reflectance at 0-10 degree incident angle = 4.38%, %R(940nm) = 4.98%, and %Ravg(1000-1700nm) = 10.4%.

[0376] Reference Fig. 23B , provides a graph of first surface reflectance versus wavelength for this inventive example modeled at a near normal incidence angle of 8°. It should be noted that Example 16 exhibits low maximum and minimum reflectance oscillations in the 1000 to 1700 nm wavelength band of less than 7%. Also from Fig. 23B It can be clearly seen that this example exhibits a maximum reflectivity of less than 13% in the near infrared spectrum from 1000 to 1700 nm.

[0377] Reference Fig.23C , provides a graph of the single-side reflected color for this inventive example measured at incident angles of 0° to 90° using various optical film structure thickness scaling factors. Fig.23CIt can be clearly seen that the color shift exhibited by this inventive example is fairly consistent and less than 4 for a wide range of optical film structure thickness scaling factors from about 70 to 100%.

[0378] Berkovich Hardness Test Modeling Example

[0379] In this example, the modeled hardness values ​​of Example 1 and Comparative Example 1 were compared as a function of indentation depth to evaluate the hardness response of the articles of the present disclosure in the Berkovich hardness test. Typically, experimental errors associated with variations in the sharpness of the diamond nanoindenter tip are considered, which increases the uncertainty of the measured hardness values ​​at indentation depths below about 100 nm. In this example, a detailed modeling analysis was performed to evaluate the effects of the indenter tip radius and the finite element mesh size parameters. These modeling results were then compared to experimental measurement data (see Fig.24 , as described below). The model was validated by comparison with bulk high-purity fused silica, which has known hardness values ​​at all depths. This analysis, as well as the agreement between modeling and experiment shown below (see Fig.24 ) provide a rigorous basis upon which to determine hardness values ​​at indentation depths of 20 nm and 40 nm as distinguishing points for articles of the present disclosure (e.g., Examples 17-27 above) that exhibit high shallow hardness with relatively thin optical film structures. The indenter tip radius can still be varied experimentally, but these new analyses lead us to believe that article and optical thin film structure hardness at a depth of 20 nm can be defined through modeling, and that these hardness values ​​can also be measured experimentally with a high quality diamond indenter under the correct test conditions.

[0380] Now refer to Fig.24 , provides a graph of hardness (GPa) versus indentation depth (0 to 50 nm) measured in a Berkovich hardness test of an optical film structure of a transparent article (Example 1) of the present disclosure and a comparative article (Comparative Example 1). In addition, as Fig.24As shown, the modeled finite element (FEA) hardness and experimental hardness (including the change in the indenter tip radius in the FEA model) were evaluated for these products (Example 1 and Comparative Example 1). The FEA modeling of hardness was completed using the commonly used commercial finite element software Abaqus v2019. An axisymmetric model was used to reduce the calculation time, and a conical indenter tip with a half angle of 70.3° was assumed, which produced the same contact area to depth ratio as the Berkovich tip. The model includes the properties of the individual layers in the optical film structure and the substrate. Assuming that the material obeys the von Mises yield rule, it is assumed that the material behaves in a completely elastic-plastic manner. The material properties selected for each individual layer are calibrated to the known hardness and modulus curves measured for a single-layer optical film structure. The output of the FEA modeling is a load-displacement curve, which is then used to calculate the hardness versus depth curve, such as Fig.24 As shown. In order to extract the function of hardness and nanoindentation depth, continuous stiffness measurement (CSM) nanoindentation must be simulated. To this end, the tip of the nanoindenter vibrates with a small amplitude during the loading phase. For this simulation, the displacement history of the tip is specified by the "amplitude" curve defined by the user in ABAQUS to apply very small (about 1nm or less) harmonic removal. The maximum time increment is limited in a way that the historical output can have a high sampling rate to capture all these 1nm "removal" parts during the entire loading phase. Then, as understood by those skilled in the art, the hardness response is calculated using the Oliver-Pharr method.

[0381] Refer again Fig.24 , the original model was constructed to obtain the hardness response over a wider indentation range, typically in the range of 500nm to 1000nm, and although a good correlation with experiment was found within these depth ranges, an improved model was needed to capture the hardness at shallower depths. After a rigorous investigation of the FEA mesh quality, the model was improved so that the size of the FEA mesh elements near the surface was only a few nanometers, small enough to capture the stress field under the indenter early in the indentation process. Another change made was to model the indentation over a depth range of only 150nm, rather than over the range of 500 to 1000nm, while maintaining the same number of sampling points to extract hardness values ​​as a function of depth, but the sampling rate is now higher. This move enables more accurate capture of the hardness response at shallower depths, such as 20nm and 40nm, providing further confidence in the experimental measurement data of these examples and others in the present disclosure.

[0382] Comparative Example 4

[0383] A comparative transparent article including a strengthened glass substrate was prepared for this example, and its structure is shown in Table 21 below. The glass substrate is an ion-exchanged aluminosilicate glass substrate having a thickness of 550 μm and a refractive index of 1.51. The substrate has the following composition: 61.81% SiO2; 3.9% B2O3; 19.69% Al2O3; 12.91% Na2O; 0.018% K2O; 1.43% MgO; 0.019% Fe2O3; and 0.223% SnO2 (based on the weight % of the oxide). A molten salt bath was used to strengthen the substrate to achieve a maximum compressive stress (CS) of 850 MPa and a depth of layer (DOL) of 40 μm. In addition, the layers of the optical film structure were deposited according to the vapor deposition conditions set forth in U.S. Patent Publication No. 2020 / 0158916, the main part of which is incorporated herein by reference.

[0384] Reference Fig.25A , provides a graph of first surface reflectance versus wavelength for this comparative example measured at a near normal incidence angle of 8°. It should be noted that this comparative example exhibits an increased reflectance of 3.5% or more in wavelengths of 750nm and greater.

[0385] Reference Fig.25B , provides a graph of the single-sided reflectance color for this comparative example measured at incident angles from 0° to 90°.

[0386] Table 21: Comparative Example 4, transparent product design with tempered glass substrate

[0387] layer Material Thickness(nm) Refractive index (550nm) Glass substrate 1.51 1 <![CDATA[SiO2]]> 25 1.478 2 <![CDATA[SiN x ]]> 16.5 2.067 3 <![CDATA[SiO2]]> 24.7 1.478 4 <![CDATA[SiN x ]]> 104.6 2.067 5 <![CDATA[SiO2]]> 82 1.478 medium Air 1

[0388] Total thickness: 252.8

[0389] AR layer (external structure) thickness (nm): 82

[0390] Low RI AR thickness (nm): 82

[0391] Example 17-20

[0392] In these examples, the optical film structures described in Tables 22-25 below (e.g., Figure 1E A transparent product including a strengthened glass substrate is prepared by using a substrate of Glass 3 (commercially available from Corning, Inc.). Examples of glass 3 compositions are described in U.S. Patent Nos. 7,666,511, 4,483,700, and 5,674,790, the main contents of which are incorporated herein by reference. The layers of the optical film structure are deposited according to the vapor deposition conditions set forth in U.S. Patent Publication No. 2020 / 0158916, the main portion of which is incorporated herein by reference.

[0393] It should be noted that each of these examples (Examples 17-20) employed a relatively thick scratch resistant layer comprising a high RI material (SiN) having a thickness >120 nm, >150 nm, or >200 nm. x ). In addition, each of these exemplary optical film structures uses layers with four different refractive indices, SiN x (n=2.057), SiO x N y (n=1.744),SiO x N y (n=1.589) and SiO2 (n=1.476), while allowing for minimization of the amount of low RI material (SiO2) and minimization of the thickness of the outermost capping layer comprising SiO2. In combination, the aforementioned optical film structure design and design strategy advantageously improves hardness while maintaining a low average photopic reflectance and minimizing the overall thickness of the optical film structure.

[0394] Now refer to Fig.26A , Fig.27A , Fig.28A and Fig.29A , respectively provide graphs of the first surface reflectance and wavelength measured at a near normal incidence angle of 8° for the articles of this example (Examples 17-20). It is apparent from these graphs that each of these examples exhibits an average photopic first surface reflectance of less than or equal to 1.5%. In addition, it is apparent from these graphs that each of these examples exhibits an average first surface reflectance of less than 8% from 920 to 960 nm. In addition, referring to Fig.26B , Fig.27B , Fig.28B and Fig.29B , provides a graph of the single-side reflected color of the transparent articles of this example (Examples 17-20) measured at incident angles from 0° to 90°.

[0395] In addition, now refer to Fig.29C, a graph of the hardness (GPa) and indentation depth measured in the Berkovich hardness test of the optical film structure of one of the transparent articles of this example (Example 20) is provided. It can be clearly seen from the graph that the maximum hardness of this example is 14.5 GPa, and the hardness of the indentation depth is: 9.7 GPa (20nm), 11.0 GPa (40nm), 13.9 GPa (100nm), 14.2nm (125nm).

[0396] Table 22: Example 17, transparent article design with strengthened glass substrate

[0397] layer Material Thickness(nm) Refractive index (550nm) Glass substrate 1.51 1 <![CDATA[SiO2]]> 25 1.476 2 <![CDATA[SiO x N y ]]> 81.1 1.744 3 <![CDATA[SiN x ]]> 65.7 2.057 4 <![CDATA[SiO x N y ]]> 8.0 1.744 5 <![CDATA[SiN x ]]> 158.9 2.057 6 <![CDATA[SiO x N y ]]> 31.84 1.589 7 <![CDATA[SiO2]]> 65 1.476 medium Air 1

[0398] Total thickness: 435.5

[0399] AR layer (external structure) thickness (nm): 96.84 AR thickness for low RI (nm): 65

[0400] Table 23: Example 18, transparent article design with strengthened glass substrate

[0401]

[0402]

[0403] Total thickness: 433.4 AR layer thickness (nm): 96.2 AR thickness for low RI (nm): 50

[0404] Table 24: Example 19, transparent article design with strengthened glass substrate

[0405] layer Material Thickness(nm) Refractive index (550nm) Glass substrate 1.51 1 <![CDATA[SiO2]]> 25 1.476 2 <![CDATA[SiO x N y ]]> 81.6 1.744 3 <![CDATA[SiN x ]]> 65.2 2.057 4 <![CDATA[SiO x N y ]]> 8.0 1.744 5 <![CDATA[SiN x ]]> 156.2 2.057 6 <![CDATA[SiO x N y ]]> 53.2 1.589 7 <![CDATA[SiO2]]> 40 1.476 medium Air 1

[0406] Total thickness: 429.2 AR layer (external structure) thickness (nm): 93.2 AR thickness for low RI (nm): 40

[0407] Table 25: Example 20, transparent article design with strengthened glass substrate

[0408]

[0409]

[0410] Total thickness: 410.8

[0411] AR layer (external structure) thickness (nm): 99.5 AR thickness for low RI (nm): 15

[0412] Examples 21 and 22

[0413] In these examples, the optical film structures described in Tables 26 and 27 below (e.g., Figure 1F A transparent product including a strengthened glass substrate is prepared by using a substrate of Glass 3 (commercially available from Corning, Inc.). Examples of glass 3 compositions are described in U.S. Patent Nos. 7,666,511, 4,483,700, and 5,674,790, the main contents of which are incorporated herein by reference. The layers of the optical film structure are deposited according to the vapor deposition conditions set forth in U.S. Patent Publication No. 2020 / 0158916, the main portion of which is incorporated herein by reference.

[0414] It should be noted that each of these examples (Examples 21 and 22) employed a relatively thick scratch resistant layer comprising a high RI material (SiN x ). In addition, each of these exemplary optical film structures uses layers with three different refractive indices, SiN x (n=2.057), SiO x N y (n=1.744) and SiO2 (n=1.476), while allowing for minimization of the amount of low RI material (SiO2) and minimization of the thickness of the outermost capping layer comprising SiO2. In combination, the aforementioned optical film structure design and design strategy advantageously improve hardness while maintaining a low average photopic reflectance and minimizing the overall thickness of the optical film structure.

[0415] Now refer to Fig. 30A and Fig.31A , respectively, provide graphs of the first surface reflectance versus wavelength measured at a near normal incidence angle of 8° for the articles of this example (Examples 21 and 22). As can be seen from these graphs, each of these examples exhibits an average photopic first surface reflectance of less than or equal to 4.5%. In addition, as can be seen from these graphs, each of these examples exhibits an average first surface reflectance of less than 12.5% ​​from 920 to 960 nm. In addition, now referring to Fig. 30B and Fig.31B , provides a graph of the single-side reflected color of the transparent articles of this example (Examples 21 and 22) measured at incident angles of 0° to 90°.

[0416] Table 26: Example 21, transparent article design with strengthened glass substrate

[0417]

[0418]

[0419] Total thickness: 432.5

[0420] AR layer (external structure) thickness (nm): 73.6 AR thickness for low RI (nm): 4

[0421] Table 27: Example 22, transparent article design with strengthened glass substrate

[0422] layer Material Thickness(nm) Refractive index (550nm) Glass substrate 1.51 1 <![CDATA[SiO2]]> 25 1.476 2 <![CDATA[SiO x N y ]]> 75.5 1.744 3 <![CDATA[SiN x ]]> 231.8 2.057 4 <![CDATA[SiO x N y ]]> 54.7 1.744 5 <![CDATA[SiO2]]> 14 1.476 medium Air 1

[0423] Total thickness: 401.0

[0424] AR layer (external structure) thickness (nm): 68.7 Low RI AR thickness (nm): 14

[0425] Example 23-27

[0426] In these examples, the optical film structures described in Tables 28-32 (Examples 23-27) below (e.g., Figure 1G A transparent article including a strengthened glass ceramic substrate is prepared by using a reinforced glass ceramic substrate (as exemplified by a transparent article of ). The glass ceramic substrate is an ion-exchanged LAS glass ceramic substrate having a thickness of 600 μm and a refractive index of 1.533. The glass ceramic substrate has the following composition: 74.5% SiO2; 7.53% Al2O3; 2.1% P2O5; 11.3% Li2O; 0.06% Na2O; 0.12% K2O; 4.31% ZrO2; 0.06% Fe2O3; and 0.02% SnO2 (based on the weight % of the oxide). The glass ceramic substrate was ceramized according to the following schedule: (a) heating from room temperature to 580°C at 5°C / min; (b) holding at 580°C for 2.75 hours; (c) heating to 755°C at 2.5°C / min; (d) holding at 755°C for 0.75 hours; and (e) cooling to room temperature at a furnace rate. After ceramization, the glass ceramic substrate was ion exchange strengthened at 500°C for 6 hours in a molten salt bath of 60% KNO3 / 40% NaNO3+0.12% LiNO3 (wt%). In addition, the layers of the optical film structure were deposited according to the vapor deposition conditions set forth in U.S. Patent Publication No. 2020 / 0158916, the main part of which is incorporated herein by reference.

[0427] It should be noted that each of these examples (Examples 23-27) employed a relatively thick scratch resistant layer comprising a medium RI material (SiO x N y ). In addition, each of these exemplary optical film structures employs (a) a relatively thick high RI layer (SiN x ) (e.g., layers 12, 12, 14, 21, and 19 of Examples 23-27, respectively), and (b) including a medium RI material (SiO x N y ) (e.g., layers 8, 8, 8, 16, and 16 of Examples 23-27, respectively) (whose thickness can vary between 0.2 and 5 μm), together contribute to increasing the hardness of the article while maintaining a low average photopic reflectance. For example, an optical film structure design having a 500 nm thick scratch-resistant layer (layer 8) similar to the design in Table 28 below (Example 23) exhibits similar optical properties, but the thickness of the optical film structure in a thinner overall package is about 1209 nm. In another example, an optical film structure design having a 500 nm thick scratch-resistant layer (layer 16) similar to the design in Table 31 (Example 26) exhibits similar optical properties, but the thickness of the optical film structure in a thinner overall package is about 1423 nm.

[0428] Furthermore, the use of a medium RI material in the scratch resistant layer (i.e., the thickest layer in the optical film structure) of these examples (Examples 23-27) can be advantageously used to improve the retained flexural strength of the transparent article while also reducing optical absorption, thereby enabling the use of thicker scratch resistant layers without causing an unacceptable reduction in optical transmission due to absorption. Furthermore, each of these example optical film structures employs layers having four different refractive indices, SiN x (n=2.057), SiO x N y (n=1.744),SiO x N y (n=1.589, 1.733, or 1.707) and SiO2 (n=1.476), while allowing for minimization of the amount of low RI material (SiO2) and minimization of the thickness of the outermost capping layer comprising SiO2. In combination, the aforementioned optical film structure design and design strategy advantageously improve hardness while maintaining a low average photopic reflectance and minimizing the overall thickness of the optical film structure.

[0429] Now refer to FIG. 32A to FIG. 36A, respectively, provide graphs of the first surface reflectance and wavelength measured at a near normal incidence angle of 8° for the articles of this example (Examples 23-27). It is apparent from these graphs that each of these examples exhibits an average photopic first surface reflectance of less than or equal to 4.5% (Examples 23-27) or less than 1.6% (Examples 23-25). In addition, it is apparent from these graphs that each of these examples exhibits an average first surface reflectance of less than 5.5% from 920 to 960 nm. In addition, referring to FIG. 32B to FIG. 36B , provides a graph of the single-side reflected color of the transparent articles of this example (Examples 23-27) measured at incident angles from 0° to 90°.

[0430] Table 28: Example 23, transparent article design with strengthened glass ceramic substrate

[0431] layer Material Thickness(nm) Refractive index (550nm) Glass Ceramics substrate 1.533 1 <![CDATA[SiO2]]> 25 1.476 2 <![CDATA[SiO x N y ]]> 14.0 1.829 3 <![CDATA[SiO2]]> 51.2 1.476 4 <![CDATA[SiO x N y ]]> 30.7 1.829 5 <![CDATA[SiO2]]> 30.1 1.476 6 <![CDATA[SiO x N y ]]> 49.2 1.829 7 <![CDATA[SiO2]]> 8.9 1.476 8 <![CDATA[SiO x N y ]]> 2000 1.829 9 <![CDATA[SiO x N y ]]> 163.2 1.744 10 <![CDATA[SiN x ]]> 33.5 2.058 11 <![CDATA[SiO x N y ]]> 14.9 1.744 12 <![CDATA[SiN x ]]> 198.0 2.058 13 <![CDATA[SiO x N y ]]> 76.5 1.589 14 <![CDATA[SiO2]]> 14 1.476 medium Air 1

[0432] Total thickness: 2709.0 AR layer thickness(nm): 500.0 Low RI AR thickness (nm): 14

[0433] Table 29: Example 24, transparent article design with strengthened glass ceramic substrate

[0434] layer Material Thickness(nm) Refractive index (550nm) Glass Ceramics substrate 1.533 1 <![CDATA[SiO2]]> 25 1.476 2 <![CDATA[SiO x N y ]]> 14.0 1.829 3 <![CDATA[SiO2]]> 51.2 1.476 4 <![CDATA[SiO x N y ]]> 30.7 1.829 5 <![CDATA[SiO2]]> 30.1 1.476 6 <![CDATA[SiO x N y ]]> 49.2 1.829 7 <![CDATA[SiO2]]> 8.9 1.476 8 <![CDATA[SiO x N y ]]> 2000 1.829 9 <![CDATA[SiO x N y ]]> 186.9 1.744 10 <![CDATA[SiN x ]]> 28.3 2.058 11 <![CDATA[SiO x N y ]]> 30.6 1.744 12 <![CDATA[SiN x ]]> 164.2 2.058 13 <![CDATA[SiO x N y ]]> 79.0 1.589 14 <![CDATA[SiO2]]> 14 1.476 medium Air 1

[0435] Total thickness: 2711.9 AR layer thickness (nm): 502.9 Low RI AR thickness (nm): 14

[0436] Table 30: Example 25, transparent article design with strengthened glass-ceramic substrate

[0437] layer Material Thickness(nm) Refractive index (550nm) Glass Ceramics substrate 1.533 1 <![CDATA[SiO2]]> 25 1.476 2 <![CDATA[SiO x N y ]]> 9.2 1.829 3 <![CDATA[SiO2]]> 54.9 1.476 4 <![CDATA[SiO x N y ]]> 30.1 1.829 5 <![CDATA[SiO2]]> 32.9 1.476 6 <![CDATA[SiO x N y ]]> 61.7 1.829 7 <![CDATA[SiO2]]> 8.7 1.476 8 <![CDATA[SiO x N y ]]> 2000 1.829 9 <![CDATA[SiO x N y ]]> 203.9 1.744 10 <![CDATA[SiN x ]]> 14.5 2.058 11 <![CDATA[SiO x N y ]]> 63.2 1.744 12 <![CDATA[SiN x ]]> 30.9 2.058 13 <![CDATA[SiO x N y ]]> 17.5 1.744 14 <![CDATA[SiN x ]]> 102.0 2.058 15 <![CDATA[SiO x N y ]]> 77.2 1.589 16 <![CDATA[SiO2]]> 14 1.476 medium Air 1

[0438] Total thickness: 2745.5 AR layer thickness (nm): 523.1 Low RI AR thickness (nm): 14

[0439] Table 31: Example 26, transparent article design with strengthened glass ceramic substrate

[0440] layer Material Thickness(nm) Refractive index (550nm) Glass Ceramics substrate 1.533 1 <![CDATA[SiO2]]> 25 1.476 2 <![CDATA[SiO x N y ]]> 16.2 1.744 3 <![CDATA[SiO2]]> 67.9 1.476 4 <![CDATA[SiO x N y ]]> 25.3 1.744 5 <![CDATA[SiO2]]> 70.9 1.476 6 <![CDATA[SiO x N y ]]> 33.4 1.744 7 <![CDATA[SiO2]]> 61.7 1.476 8 <![CDATA[SiO x N y ]]> 44 1.744 9 <![CDATA[SiO2]]> 47.4 1.476 10 <![CDATA[SiO x N y ]]> 56.7 1.744 11 <![CDATA[SiO2]]> 32.0 1.476 12 <![CDATA[SiO x N y ]]> 68.9 1.744 13 <![CDATA[SiO2]]> 18.3 1.476 14 <![CDATA[SiO x N y ]]> 76.6 1.744 15 <![CDATA[SiO2]]> 8.0 1.476 16 <![CDATA[SiO x N y ]]> 2000 1.744 17 <![CDATA[SiN x ]]> 15.5 2.058 18 <![CDATA[SiO x N y ]]> 37.4 1.744 19 <![CDATA[SiN x ]]> 59.3 2.058 20 <![CDATA[SiO x N y ]]> 8.0 1.744 21 <![CDATA[SiN x ]]> 65.0 2.058 22 <![CDATA[SiO x N y ]]> 81.6 1.733 23 <![CDATA[SiO2]]> 4 1.476 medium Air 1

[0441] Total thickness: 2923.0 AR layer thickness (nm): 270.8 AR thickness for low RI (nm): 4

[0442] Table 32: Example 27, transparent article design with strengthened glass-ceramic substrate

[0443] layer Material Thickness(nm) Refractive index (550nm) Glass Ceramics substrate 1.533 1 <![CDATA[SiO2]]> 25 1.476 2 <![CDATA[SiO x N y ]]> 16.2 1.744 3 <![CDATA[SiO2]]> 67.9 1.476 4 <![CDATA[SiO x N y ]]> 25.3 1.744 5 <![CDATA[SiO2]]> 70.9 1.476 6 <![CDATA[SiO x N y ]]> 33.4 1.744 7 <![CDATA[SiO2]]> 61.7 1.476 8 <![CDATA[SiO x N y ]]> 44 1.744 9 <![CDATA[SiO2]]> 47.4 1.476 10 <![CDATA[SiO x N y ]]> 56.7 1.744 11 <![CDATA[SiO2]]> 32.0 1.476 12 <![CDATA[SiO x N y ]]> 68.9 1.744 13 <![CDATA[SiO2]]> 18.3 1.476 14 <![CDATA[SiO x N y ]]> 76.6 1.744 15 <![CDATA[SiO2]]> 8.0 1.476 16 <![CDATA[SiO x N y ]]> 2000 1.744 17 <![CDATA[SiN x ]]> 16.0 2.058 18 <![CDATA[SiO x N y ]]> 36.6 1.744 19 <![CDATA[SiN x ]]> 63.8 2.058 20 <![CDATA[SiO x N y ]]> 8.0 1.744 21 <![CDATA[SiN x ]]> 62.4 2.058 22 <![CDATA[SiO x N y ]]> 68.0 1.707 23 <![CDATA[SiN x ]]> 8 2.058 24 <![CDATA[SiO2]]> 4 1.476 medium Air 1

[0444] Total thickness: 2918.9 AR layer thickness (nm): 266.6 AR thickness for low RI (nm): 4

[0445] Summary of Mechanical and Optical Properties of Comparative Examples 1 and 4 and Examples 1 and 17-27

[0446] In the foregoing examples, transparent articles and optical structure designs are described in detail that exhibit high shallow layer hardness while maintaining desired optical properties (e.g., low average photopic reflectance) (i.e., Examples 17-27). As previously described, strategies for increasing near-surface hardness while controlling the optical properties of these transparent articles include reducing the amount of low refractive index material (e.g., SiO2) with n<1.55 in a multilayer thin film stack (e.g., an optical film structure), minimizing the thickness of the outermost low refractive index layer (e.g., a capping layer), and using one or more medium refractive index materials (e.g., SiO2) in the layer stack. x N y ) and high refractive index materials (e.g. SiN x ).

[0447] As described in detail in Table 33 below, the key optical and mechanical property indicators of these transparent products and optical film structure designs (i.e., Examples 1, 17-27) are captured. For comparison, Table 33 also provides optical and mechanical property data for two comparative products (Comparative Example 1 and Comparative Example 4). All data provided in Table 33 are from modeling, but as previously described (see Fig.24 and corresponding description), the model adopted in the present disclosure has been verified using experimental data.

[0448] Table 33: Mechanical and optical properties of Examples 1 and 17-27 and Comparative Examples 1 and 4

[0449]

[0450]

[0451] Finally, the concept of quality factor is introduced, which combines the shallow hardness (e.g., the hardness at a depth of 125 nanometers, or other depth values ​​specified herein) and the change in average visible reflectivity of a transparent article with a specified amount of material removed. The change in reflectivity with material removal may be related to the visibility of shallow surface scratches or wear marks, so a smaller change in reflectivity with material removal is preferred. Given the optical film structure design and data in the present disclosure, known transfer matrix simulation methods can be used to model the change in reflectivity with shallow depth of material removal. For example, Comparative Example 1 has a hardness at a depth of 125 nm of approximately 15.7 GPa and a change in average % reflectivity (400-700 nm wavelength average) of 48% (only 18 nm of material is removed from the top of the optical film structure). This gives an exemplary quality factor (FOm) of H(125) / delta%R(18 nm)=15.7 / 0.48=32.7. In contrast, Example 1 has an exemplary FOM of H(125) / delta%R(18nm)=19.7 / 0.059=333. Therefore, using this suggested FOM, it is desirable and transparent articles of the present disclosure may exhibit a FOM of H(125) / delta%R(18nm)=greater than 50, greater than 100, greater than 200, or even greater than 300.

[0452] Example 28 (Examples 28A-28E)

[0453] In this example, a transparent article (nominally Example 16, as detailed above) including a strengthened glass-ceramic substrate (thickness of about 0.6 mm) was evaluated to assess the surprising effect of reducing the thickness of the scratch-resistant layer 150 to reduce warpage and maintain the strength and hardness of the article. More specifically, transparent articles having designs as detailed in Table 34 below were evaluated, with different scratch-resistant layer thicknesses (i.e., Examples 28A-28E having scratch-resistant layer thicknesses of 0.1, 0.5, 1, 1.5, and 2 μm, respectively).

[0454] This example uses the standard transparent product design (Example 28A) of Table 34 to demonstrate the advantages of tuning the thickness of the scratch-resistant layer. As can be clearly seen from Table 34, the optical film structure includes an outer structure (i.e., anti-reflection (AR) stack), a scratch-resistant layer (2 μm), and an inner structure (i.e., impedance matching (IM) stack), wherein the total thickness of the optical film structure is as high as 2.9 μm. Based on the measurement of the average optical film structure stress, the optical film structure design, and the stress measurement in the single-layer structure, the residual stress in the scratch-resistant layer is estimated to be about -1121 MPa.

[0455] Table 34: Examples 28A-E, Transparent Article Designs with Strengthened Glass-Ceramic Substrates

[0456]

[0457]

[0458] Total thickness: 1026.8 to 2926.8 AR layer (external structure) thickness (nm): 274.6 Low RI AR thickness (nm): 14

[0459] Hardness Response vs. Scratch Resistant Layer Thickness (Examples 28A-28E)

[0460] Now refer to Fig.40A , provides a diagram of hardness (GPa) versus indentation depth modeled to indicate the results of Berkovich hardness testing of optical film structures of transparent articles of this example (Examples 28A-28E) with different levels of scratch-resistant layer thickness. In this example, the samples (Examples 28A-28E) were modeled assuming that the processing conditions for sputtering the scratch-resistant layer and other layers remained unchanged. Fig.40A As shown, FEA simulations were used to evaluate the effect of thinner scratch-resistant layers on nanoindentation hardness (e.g., Berkovich hardness test) (e.g., as described in Price, JJ et al., "Nanoindentation Hardness and Practical Scratch Resistance in Mechanically Tunable Anti-Reflection Coatings," Coatings, 2021, 11(2), the main portion of which is incorporated herein by reference). As shown, transparent articles with scratch-resistant layers having thicknesses of 0.1, 0.5, 1, 1.5, and 2 microns were evaluated, respectively Examples 28A-28E. Fig.40A As shown, the hardness response in the initial stage of nanoindentation does not change much with the thickness of the scratch-resistant layer, and the curve seems to diverge with increasing indentation depth. In addition, even if the scratch-resistant layer thickness is reduced to as small as 0.1 μm (Example 28A), the hardness remains above 12 GPa in the entire indentation depth range of 100 nm to 1000 nm.

[0461] Now refer to Fig.40B , provides a diagram of hardness (GPa) versus scratch-resistant layer thickness modeled to indicate the results of Berkovich hardness testing of the optical film structures of the transparent articles of this example (Examples 28A-28E). The hardness value at 125nm (H125) is generally considered to be very important because it may represent the scratch resistance provided in customer-specific scratch testing. Therefore, Fig.40BH125 values ​​are shown as well as H250 and H500 as a function of the thickness of the scratch-resistant layer. The data labels show the hardness drop compared to the original design (Example 28E) with a 2μm scratch-resistant layer. As shown, H125 remains fairly stable as the scratch-resistant layer thickness decreases from 2μm to 500nm (Example 28C) and the change remains within 1%. H125 decreases by about 3% only when the thickness of the scratch-resistant layer is reduced to as low as 100nm (Example 28A). Similarly, the reduction in H250 is only apparent when the scratch-resistant layer thickness is less than 1000nm thick. For any value of thickness <1500nm (e.g., Examples 28A-28C), H500 is significantly reduced. "Significantly" in this article means a change of more than a few% compared to the original design (Example 28E).

[0462] in accordance with Fig.40A and Fig.40B The evaluation results shown, if H125 is the most important hardness parameter, then a scratch resistant layer of 500nm should be thick enough, and scratch resistant layers >500nm provide diminishing returns. If scratch resistance at a deeper depth (e.g., 250nm) is desired, then a scratch resistant layer of 1000nm may be sufficient. Furthermore, if H500 is considered important, then 1500nm is already thick enough for the scratch resistant layer.

[0463] Retention Strength vs. Scratch-Resistant Layer Thickness (Examples 28A-28E and Comparative Example 5)

[0464] In this aspect, the retention strength is evaluated as a function of the thickness of the scratch-resistant layer of the samples of this example (Examples 28A-28E). In addition, a control sample without an optical film structure was evaluated (Comparative Example 5), in which all other components were the same as the samples of this example. It is obvious from the results of this aspect that multiple factors affect the retention strength: (a) a reduction in the thickness of the optical film structure reduces the overall number of defects (optical film structure + substrate defect size) and increases the strength; (b) a reduction in the thickness of the optical film structure (especially a reduction in the thickness of the high stress layer) may reduce the average optical film structure stress, reduce the "crack closure" effect, and ultimately reduce the strength; (c) a reduction in the thickness of the high modulus layer (e.g., the scratch-resistant layer) in the optical film structure relative to the thickness of other layers (e.g., a low RI layer (e.g., SiO2)) reduces the average modulus of the optical film structure, while reducing the stress intensity factor and increasing the strength.

[0465] Reference Fig.41A and Fig.41B, provides a schematic diagram modeled to indicate the retained strength (MPa) of the ring-to-ring (ROR) test of transparent articles of this example (Examples 28A-28E) with different levels of scratch-resistant layer thickness and a control sample without an optical film structure (Comparative Example 5) and two substrate defect size ranges (ranging from 0 to 20 μm and 60 to 68 μm, respectively). More specifically, the curves shift in two main ways as the thickness of the scratch-resistant layer changes. More specifically, for thinner scratch-resistant layers, (a) the surface strength increases; and (b) the strength at depth increases.

[0466] For (a) of the increase in surface strength, assuming that the average surface strength under unworn conditions measured in the ROR test is determined by defects in the range of 0.5μm to 2.5μm, the average surface strength increases slightly from 731MPa to 740MPa. It was found that the increase in strength of defects of 0.1μm was more obvious (786MPa to 840MP, or about 7%). Most importantly, it was found that the unworn retained strength was not adversely affected. For (b) of the increase in strength at depth, it was found that the damage resistance of the provided glass substrate under drop conditions decreased with the thickness of the optical film structure. The magnitude of the reduction in strength after the drop depends on the inspection depth. For example, it was found that the average inspection depth after the strengthened glass ceramic substrate was dropped was 63μm (0.6mm glass attached to a 200g polymer disc, and the plane was dropped onto 3M's 80-grit garnet sandpaper). Assuming that the inspection depth of the strengthened glass-ceramic substrate with the optical film structure also remains the same, it is found that the strength at 63 μm after the drop is slightly reduced (i.e., for a hard layer of 500 nm thickness, it is reduced from the original 257 MPa to 245 MPa (i.e., a 5% reduction)). However, the optical film structure is also expected to provide a certain damage resistance, which may alleviate this strength drop.

[0467] Now refer to Fig.41C , provides a schematic diagram of the retained strength (MPa) and the thickness of the scratch-resistant layer modeled to indicate the surface retained strength and the strength at a depth of 63 μm in the ROR test of the transparent articles of this example (Examples 28A-28E). Fig.41C The data are also summarized in Table 35 below. Fig.41C It can be clearly seen from Table 35 that the average optical film structure stress decreases with the reduction of the scratch resistant layer thickness, which means that crack closure may not be as effective; however, it is clear that the simultaneous increase in average modulus and the reduction in total defect depth (optical film structure thickness + substrate defect size) compensate for the decrease in optical film structure stress.

[0468] Table 35: Summary of Retention Strength and Other Properties of Examples 28A-28E

[0469]

[0470] Warpage and Scratch Resistant Layer Thickness (Examples 28A-28E)

[0471] In this aspect, the warpage was evaluated as a function of the scratch resistant layer thickness of the samples of this example (Examples 28A-28E). It is apparent from the results of this aspect that a reduction in the scratch resistant layer thickness can significantly reduce substrate warpage after deposition of the optical film structure and reduce the time and cost required to process the substrate (asymmetric polishing) prior to applying the optical film structure. As summarized in Table 36 below, the warpage is primarily driven by the compressive stress in the optical film structure and the thickness of the optical film structure. Because the average stress in the optical film structure itself and the optical film structure "force" (i.e., F = σh c ), the optical film structure stress multiplied by the optical film structure thickness) is also reduced, so reducing the thickness of the scratch resistant layer has a dual effect on warpage. It is obvious from Table 36 that if the scratch resistant layer thickness is reduced from 2000nm (Example 28E) to 500nm (Example 28B), the maximum deflection of the D63 portion (maximum diagonal length of 73mm) is reduced from about 1mm (original) to about 435μm.

[0472] Table 36: Summary of Maximum Deflection and Residual Stress for Examples 28A-28E

[0473]

[0474] Now refer to Fig.42A , provides a schematic diagram of the net deflection (μm) and single-side material removal of the transparent articles of this example (Examples 28A-28E) with different scratch-resistant layer thickness levels. In addition, Fig.42B is a schematic diagram of the single-sided material removal required before deposition of a zero-warpage optical film structure as a function of the scratch-resistant layer thickness of the transparent article of this example. More specifically, Fig.42A Showing the net deflection as a function of one-sided material removal, and Fig.42B The single-sided material removal required before applying the optical film structure to achieve net zero warpage for various thicknesses of the scratch-resistant layer (for all of the D63 section, Examples 28A-28E) is shown. From these figures, it can be seen that if a 2 μm thick scratch-resistant layer is used (Example 28E), a single-sided material removal of nearly 12 μm is required (on the A side of the substrate), while only 4 μm of removal is required for a 500 nm thick scratch-resistant layer (Example 28B), a 3-fold reduction.

[0475] Aspect 1: According to the first aspect of the present disclosure, a transparent article is provided, comprising: a substrate comprising a first major surface and a second major surface, the major surfaces being opposite to each other; and an optical film structure defining an outer surface, the optical film structure being disposed on the first major surface. The optical film structure comprises a scratch-resistant layer and a plurality of alternating high refractive index (RI) and low RI layers. In addition, the optical film structure comprises an outer structure and an inner structure, the scratch-resistant layer being disposed between the outer structure and the inner structure. In addition, one or both of the following: (i) the outer structure comprises at least one medium RI layer, the at least one medium RI layer being in contact with one or both of the following: (a) the scratch-resistant layer, and (b) one of the high RI layers; and (ii) the sum of the physical thicknesses of all the low RI layers in the outer structure is less than about 200 nm. In addition, at least one medium RI layer comprises a refractive index of 1.55 to 1.80, each of the high RI layers comprises a refractive index greater than 1.80, and each of the low RI layers comprises a refractive index less than 1.55.

[0476] Aspect 2: According to the second aspect of the present disclosure, the first aspect is provided, wherein the outer structure includes at least one medium RI layer, and the at least one medium RI layer is in contact with one or both of the following: (a) the scratch-resistant layer, and (b) one of the high RI layers.

[0477] Aspect 3: According to the third aspect of the present disclosure, the first aspect or the second aspect is provided, wherein the sum of the physical thicknesses of all low RI layers in the outer structure is less than about 75 nm.

[0478] Aspect 4: According to the fourth aspect of the present disclosure, the third aspect is provided, wherein the transparent article exhibits an average first surface photopic reflectance of less than 7% and a first surface reflectance at a wavelength of 940 nm of less than 8%, each measured at a near normal incidence angle.

[0479] Aspect 5: According to the fifth aspect of the present disclosure, the first aspect is provided, wherein the sum of the physical thicknesses of all low RI layers in the outer structure is less than about 200 nm, and wherein the transparent article further exhibits an average first surface photopic reflectance of less than 3% and a first surface reflectance at a wavelength of 940 nm of less than 5%, each measured at a near normal incidence angle.

[0480] Aspect 6: According to the sixth aspect of the present disclosure, a first aspect is provided, wherein the outer structure includes at least one medium RI layer, and the at least one medium RI layer is in contact with one or both of the following: (a) the scratch-resistant layer, and (b) one of the high RI layers, and wherein the substrate further includes a glass-ceramic substrate having an elastic modulus greater than 85 GPa and a fracture toughness greater than 0.8 MPa·√m.

[0481] Aspect 7: According to the seventh aspect of the present disclosure, a first aspect is provided, wherein the optical film structure has a physical thickness of about 200 nm to 5000 nm, wherein the article exhibits an average first surface photopic reflectance of less than 6%, and wherein the article further exhibits one or more of the following: (a) a hardness greater than 11 GPa at an indentation depth of about 20 nm or 40 nm measured at the outer surface of the optical film structure by a Berkovich hardness test; (b) a hardness greater than 15 GPa at an indentation depth of 100 nm; and (c) a hardness greater than 16 GPa at an indentation depth of 125 nm.

[0482] Aspect 8: According to the eighth aspect of the present disclosure, a first aspect is provided, wherein the optical film structure has a physical thickness of about 200 nm to 800 nm, wherein the article exhibits an average first surface photopic reflectance of less than 6%, and wherein the article further exhibits one or more of the following: (a) a hardness greater than 9 GPa at an indentation depth of 20 nm measured at the outer surface of the optical film structure by a Berkovich hardness test; (b) a hardness greater than 10 GPa at an indentation depth of 40 nm; (c) a hardness greater than 12 GPa at an indentation depth of 100 nm; (d) a hardness greater than 12 GPa at an indentation depth of 125 nm.

[0483] Aspect 9: According to the ninth aspect of the present disclosure, a first aspect is provided, wherein the scratch-resistant layer has a physical thickness of about 100 nm to less than 2000 nm, and wherein the outer structure further includes at least one medium RI layer, and the at least one medium RI layer is in contact with one or both of the following: (a) the scratch-resistant layer, and (b) one of the high RI layers.

[0484] Aspect 10: According to the tenth aspect of the present disclosure, any one of the first to ninth aspects is provided, further comprising a textured surface region defined by the first major surface of the substrate, wherein the textured surface region comprises a plurality of structural features and an average texture height (R) of 50 nm to 800 nm. text ).

[0485] Aspect 11: According to the eleventh aspect of the present disclosure, any one of the first to ninth aspects is provided, further comprising a diffraction surface area defined by the first major surface of the substrate, wherein the diffraction surface area comprises a plurality of structural features with a plurality of different heights having a bimodal or multimodal distribution.

[0486] Aspect 12: According to the twelfth aspect of the present disclosure, a transparent article is provided, comprising: a substrate comprising a first major surface and a second major surface, the major surfaces being opposite to each other; and an optical film structure defining an outer surface, the optical film structure being disposed on the first major surface. The optical film structure comprises a scratch-resistant layer and a plurality of alternating high refractive index (RI) and low RI layers. In addition, the optical film structure comprises an outer structure and an inner structure, the scratch-resistant layer being disposed between the outer structure and the inner structure. The outer structure comprises at least one medium RI layer, the at least one medium RI layer being in contact with one or both of the following: (a) the scratch-resistant layer, and (b) one of the high RI layers. In addition, the medium RI layer comprises a refractive index of 1.55 to 1.80, each of the high RI layers comprises a refractive index greater than 1.80, and each of the low RI layers comprises a refractive index less than 1.55.

[0487] Aspect 13: According to the thirteenth aspect of the present disclosure, the twelfth aspect is provided, wherein the article exhibits a hardness greater than 15 GPa measured by the Berkovich Hardness Test at an indentation depth of about 125 nm from the outer surface of the optical film structure.

[0488] Aspect 14: According to the fourteenth aspect of the present disclosure, the twelfth aspect is provided, wherein the article exhibits a hardness greater than 16 GPa measured by the Berkovich Hardness Test at an indentation depth of about 125 nm from the outer surface of the optical film structure.

[0489] Aspect 15: According to the fifteenth aspect of the present disclosure, any one of aspects 12 to 14 is provided, wherein the article exhibits an average first surface photopic reflectance of less than 5%, a first surface reflectance at a wavelength of 940 nm of less than 6%, and an average first surface reflectance at a wavelength of 1000 nm to 1700 nm of less than 10%, each measured at a near normal incidence angle.

[0490] Aspect 16: According to the sixteenth aspect of the present disclosure, any one of the twelfth to fifteenth aspects is provided, wherein each high RI layer and the scratch resistant layer comprises Si3N4, SiN y and SiO x N y One or more of, and each low RI layer comprises SiO2, SiO x and SiO x N y One or more of .

[0491] Aspect 17: According to the seventeenth aspect of the present disclosure, any one of the twelfth to sixteenth aspects is provided, wherein the scratch-resistant layer and each medium RI layer comprises SiO x N y .

[0492] Aspect 18: According to the eighteenth aspect of the present disclosure, any one of aspects 12 to 17 is provided, wherein the optical film structure exhibits a residual compressive stress greater than or equal to 700 MPa and an elastic modulus greater than or equal to 140 GPa.

[0493] Aspect 19: According to the nineteenth aspect of the present disclosure, any one of aspects 12 to 18 is provided, wherein the substrate is a glass ceramic material comprising an elastic modulus greater than 85 GPa and a fracture toughness greater than 0.8 MPa·√m.

[0494] Aspect 20: According to the twentieth aspect of the present disclosure, any one of aspects 12 to 19 is provided, wherein the optical film structure exhibits a residual compressive stress of 700 MPa to 1100 MPa and an elastic modulus of 140 GPa to 200 GPa.

[0495] Aspect 21: According to the twenty-first aspect of the present disclosure, any one of aspects 12 to 20 is provided, wherein the optical film structure exhibits an elastic modulus of 140 GPa to 180 GPa.

[0496] Aspect 22: According to the twenty-second aspect of the present disclosure, any one of aspects 12 to 21 is provided, wherein the substrate has a residual surface compressive stress of 200 MPa to 1200 MPa and a depth of compression (DOC) of 5 μm to 150 μm.

[0497] Aspect 23: According to the twenty-third aspect of the present disclosure, any one of aspects 12 to 22 is provided, wherein the substrate further exhibits a maximum central tension (CT) value of about 80 MPa to 200 MPa, and wherein the substrate further has a thickness of about 1.5 mm or less.

[0498] Aspect 24: According to the twenty-fourth aspect of the present disclosure, any one of aspects 12 to 23 is provided, wherein the substrate has a residual surface compressive stress of 200 MPa to 400 MPa.

[0499] Aspect 25: According to the twenty-fifth aspect of the present disclosure, a transparent article is provided, comprising: a substrate comprising a first major surface and a second major surface, the major surfaces being opposite to each other; and an optical film structure defining an outer surface, the optical film structure being disposed on the first major surface. The optical film structure comprises a scratch-resistant layer and a plurality of alternating high refractive index (RI) and low RI layers. In addition, the optical film structure comprises an outer structure and an inner structure, the scratch-resistant layer being disposed between the outer structure and the inner structure. In addition, the sum of the physical thicknesses of all low RI layers in the outer structure is less than about 75 nm.

[0500] Aspect 26: According to the twenty-sixth aspect of the present disclosure, the twenty-fifth aspect is provided, wherein the article exhibits a hardness greater than 15 GPa measured by the Berkovich Hardness Test at an indentation depth of about 125 nm from the outer surface of the optical film structure.

[0501] Aspect 27: According to the twenty-seventh aspect of the present disclosure, the twenty-fifth aspect is provided, wherein the article exhibits a hardness greater than 17 GPa measured by the Berkovich Hardness Test at an indentation depth of about 125 nm from the outer surface of the optical film structure.

[0502] Aspect 28: According to the twenty-eighth aspect of the present disclosure, any one of aspects 25 to 27 is provided, wherein the article exhibits an average first surface photopic reflectance of less than 5%, a first surface reflectance at a wavelength of 940 nm of less than 6%, and an average first surface reflectance at a wavelength of 1000 nm to 1700 nm of less than 10%, each measured at a near normal incidence angle.

[0503] Aspect 29: According to the twenty-ninth aspect of the present disclosure, any one of aspects 25 to 28 is provided, wherein each high RI layer and the scratch-resistant layer comprises Si3N4, SiN y and SiO x N y One or more of, and each low RI layer comprises SiO2, SiO x and SiO x N y One or more of .

[0504] Aspect 30: According to the thirtieth aspect of the present disclosure, any one of aspects twenty-fifth to twenty-ninth is provided, wherein the sum of the physical thicknesses of all low RI layers in the outer structure is less than about 65 nm.

[0505] Aspect 31: According to the thirty-first aspect of the present disclosure, any one of aspects 25 to 30 is provided, wherein the optical film structure exhibits a residual compressive stress greater than or equal to 700 MPa and an elastic modulus greater than or equal to 140 GPa.

[0506] Aspect 32: According to the thirty-second aspect of the present disclosure, any one of aspects 25 to 31 is provided, wherein the substrate is a glass ceramic material comprising an elastic modulus greater than 85 GPa and a fracture toughness greater than 0.8 MPa·√m.

[0507] Aspect 33: According to the thirty-third aspect of the present disclosure, any one of aspects 25 to 32 is provided, wherein the optical film structure exhibits a residual compressive stress of 700 MPa to 1100 MPa and an elastic modulus of 140 GPa to 200 GPa.

[0508] Aspect 34: According to the thirty-fourth aspect of the present disclosure, any one of aspects 25 to 33 is provided, wherein the optical film structure exhibits an elastic modulus of 140 GPa to 180 GPa.

[0509] Aspect 35: According to the thirty-fifth aspect of the present disclosure, any one of aspects 25 to 34 is provided, wherein the substrate has a residual surface compressive stress of 200 MPa to 1200 MPa and a depth of compression (DOC) of 5 μm to 150 μm.

[0510] Aspect 36: According to the thirty-sixth aspect of the present disclosure, any one of aspects 25 to 35 is provided, wherein the substrate further exhibits a maximum central tension (CT) value of about 80 MPa to 200 MPa, and wherein the substrate further has a thickness of about 1.5 mm or less.

[0511] Aspect 37: According to the thirty-seventh aspect of the present disclosure, any one of aspects 25 to 36 is provided, wherein the substrate has a residual surface compressive stress of 200 MPa to 400 MPa.

[0512] Aspect 38: According to the thirty-eighth aspect of the present disclosure, a transparent article is provided, comprising: a substrate comprising a first major surface and a second major surface, the major surfaces being opposite to each other; and an optical film structure defining an outer surface, the optical film structure being disposed on the first major surface. The optical film structure comprises a scratch-resistant layer and a plurality of alternating high refractive index (RI) and low RI layers. In addition, the optical film structure comprises an outer structure and an inner structure, the scratch-resistant layer being disposed between the outer structure and the inner structure. The outer structure comprises at least one medium RI layer in contact with one of the high RI layers and the scratch-resistant layer. In addition, the medium RI layer comprises a refractive index of 1.55 to 1.80, each of the high RI layers comprises a refractive index greater than 1.80, and each of the low RI layers comprises a refractive index less than 1.55. In addition, the sum of the physical thicknesses of all low RI layers in the outer structure is less than about 75 nm.

[0513] Aspect 39: According to the thirty-ninth aspect of the present disclosure, the thirty-eighth aspect is provided, wherein the article exhibits a hardness greater than 15 GPa measured by the Berkovich Hardness Test at an indentation depth of about 125 nm from the outer surface of the optical film structure.

[0514] Aspect 40: According to the fortieth aspect of the present disclosure, the thirty-eighth aspect is provided, wherein the article exhibits a hardness greater than 17 GPa measured by the Berkovich Hardness Test at an indentation depth of about 125 nm from the outer surface of the optical film structure.

[0515] Aspect 41: According to the forty-first aspect of the present disclosure, any one of aspects 38 to 40 is provided, wherein the article exhibits an average first surface photopic reflectance of less than 5%, a first surface reflectance at a wavelength of 940 nm of less than 6%, and an average first surface reflectance at a wavelength of 1000 nm to 1700 nm of less than 10%, each measured at a near normal incidence angle.

[0516] Aspect 42: According to the forty-second aspect of the present disclosure, any one of aspects 38 to 41 is provided, wherein the article exhibits an average first surface photopic reflectance of about 4% or less, a first surface reflectance at a wavelength of 940 nm of about 4.3% or less, and an average first surface reflectance at a wavelength of 1000 nm to 1700 nm of less than 8%, each measured at a near normal incidence angle.

[0517] Aspect 43: According to the forty-third aspect of the present disclosure, any one of the thirty-eighth to forty-second aspects is provided, wherein each high RI layer and the scratch-resistant layer comprises Si3N4, SiN y and SiO x N y One or more of, and each low RI layer comprises SiO2, SiO x and SiO x N y One or more of .

[0518] Aspect 44: According to the forty-fourth aspect of the present disclosure, any one of the thirty-eighth to forty-third aspects is provided, wherein the scratch-resistant layer and each medium RI layer comprises SiO x N y , further wherein the sum of the physical thicknesses of all low RI layers in the outer structure is less than about 65 nm.

[0519] Aspect 45: According to the forty-fifth aspect of the present disclosure, any one of aspects 38 to 44 is provided, wherein the optical film structure exhibits a residual compressive stress greater than or equal to 700 MPa and an elastic modulus greater than or equal to 140 GPa.

[0520] Aspect 46: According to the forty-sixth aspect of the present disclosure, any one of aspects 38 to 45 is provided, wherein the substrate is a glass ceramic material comprising an elastic modulus greater than 85 GPa and a fracture toughness greater than 0.8 MPa·√m.

[0521] Aspect 47: According to the forty-seventh aspect of the present disclosure, any one of aspects 38 to 46 is provided, wherein the optical film structure exhibits a residual compressive stress of 700 MPa to 1100 MPa and an elastic modulus of 140 GPa to 200 GPa.

[0522] Aspect 48: According to the forty-eighth aspect of the present disclosure, any one of aspects 38 to 47 is provided, wherein the optical film structure exhibits an elastic modulus of 140 GPa to 180 GPa.

[0523] Aspect 49: According to the forty-ninth aspect of the present disclosure, any one of aspects 38 to 48 is provided, wherein the substrate has a residual surface compressive stress of 200 MPa to 1200 MPa and a depth of compression (DOC) of 5 μm to 150 μm.

[0524] Aspect 50: According to the fiftieth aspect of the present disclosure, any one of aspects 38 to 49 is provided, wherein the substrate further exhibits a maximum central tension (CT) value of about 80 MPa to 200 MPa, and wherein the substrate further has a thickness of about 1.5 mm or less.

[0525] Aspect 51: According to the fifty-first aspect of the present disclosure, any one of the thirty-eighth to the fiftieth aspects is provided, wherein the substrate has a residual surface compressive stress of 200 MPa to 400 MPa.

[0526] Aspect 52: According to the fifty-second aspect of the present disclosure, a transparent article is provided, comprising: a substrate comprising a first major surface and a second major surface, the major surfaces being opposite to each other; and an optical film structure defining an outer surface, the optical film structure being disposed on the first major surface. The optical film structure comprises a scratch-resistant layer and a plurality of alternating high refractive index (RI) and low RI layers. In addition, the optical film structure comprises an outer structure and an inner structure, the scratch-resistant layer being disposed between the outer structure and the inner structure. In addition, the sum of the physical thicknesses of all low RI layers in the outer structure is less than about 75 nm. In addition, the article exhibits an average first surface photopic reflectance of less than 7% and a first surface reflectance at a wavelength of 940 nm of less than 8%, each measured at a near normal incidence angle.

[0527] Aspect 53: According to the fifty-third aspect of the present disclosure, the fifty-second aspect is provided, wherein the sum of the physical thicknesses of all low RI layers in the outer structure is less than about 50 nm.

[0528] Aspect 54: According to the fifty-fourth aspect of the present disclosure, the fifty-second aspect or the fifty-third aspect is provided, wherein the article exhibits a first surface reflectivity of about 7% or less at a wavelength of 1000 nm to 1700 nm measured at a near normal incidence angle.

[0529] Aspect 55: According to the fifty-fifth aspect of the present disclosure, any one of aspects fifty-second to fifty-fourth is provided, wherein the article exhibits a hardness greater than 15 GPa measured by the Berkovich Hardness Test at an indentation depth of about 125 nm from the outer surface of the optical film structure.

[0530] Aspect 56: According to the fifty-sixth aspect of the present disclosure, any one of aspects 52 to 55 is provided, wherein each of the high RI layer and the scratch-resistant layer comprises SiO x N y , and each low RI layer contains SiO2, SiO x and SiO x N y One or more of .

[0531] Aspect 57: According to the fifty-seventh aspect of the present disclosure, any one of aspects 52 to 56 is provided, wherein the optical film structure exhibits a residual compressive stress greater than or equal to 700 MPa and an elastic modulus greater than or equal to 140 GPa.

[0532] Aspect 58: According to the fifty-eighth aspect of the present disclosure, any one of aspects 52 to 57 is provided, wherein the substrate is a glass ceramic material comprising an elastic modulus greater than 85 GPa and a fracture toughness greater than 0.8 MPa·√m.

[0533] Aspect 59: According to the fifty-ninth aspect of the present disclosure, any one of aspects 52 to 58 is provided, wherein the optical film structure exhibits a residual compressive stress of 700 MPa to 1100 MPa and an elastic modulus of 140 GPa to 200 GPa.

[0534] Aspect 60: According to the sixtieth aspect of the present disclosure, any one of aspects 52 to 59 is provided, wherein the optical film structure exhibits an elastic modulus of 140 GPa to 180 GPa.

[0535] Aspect 61: According to the sixty-first aspect of the present disclosure, any one of the fifty-second to sixtieth aspects is provided, wherein the substrate has a residual surface compressive stress of 200 MPa to 1200 MPa and a depth of compression (DOC) of 5 μm to 150 μm.

[0536] Aspect 62: According to the sixty-second aspect of the present disclosure, any one of aspects 52 to 61 is provided, wherein the substrate further exhibits a maximum central tension (CT) value of about 80 MPa to 200 MPa, and wherein the substrate further has a thickness of about 1.5 mm or less.

[0537] Aspect 63: According to the sixty-third aspect of the present disclosure, any one of aspects 52 to 62 is provided, wherein the substrate has a residual surface compressive stress of 200 MPa to 400 MPa.

[0538] Aspect 64: According to the sixty-fourth aspect of the present disclosure, any one of aspects 52 to 63 is provided, wherein the internal structure includes one of the following: (a) multiple alternating high refractive index (RI) layers and low RI layers; (b) a refractive index gradient; and (c) a composition gradient.

[0539] Aspect 65: According to the sixty-fifth aspect of the present disclosure, there is provided a transparent article comprising: a substrate comprising a first major surface and a second major surface, the major surfaces being opposite to each other; and an optical film structure defining an outer surface, the optical film structure being disposed on the first major surface. The optical film structure comprises a scratch-resistant layer and a plurality of alternating high refractive index (RI) and low RI layers. In addition, the optical film structure comprises an outer structure and an inner structure, the scratch-resistant layer being disposed between the outer structure and the inner structure. In addition, the sum of the physical thicknesses of all low RI layers in the outer structure is less than about 200 nm. In addition, the article exhibits an average first surface photopic reflectance of less than 3% and a first surface reflectance at a wavelength of 940 nm of less than 5%, each measured at a near normal incidence angle.

[0540] Aspect 66: According to the sixty-sixth aspect of the present disclosure, the sixty-fifth aspect is provided, wherein the...

Claims

1. A transparent product, comprising: a substrate including a first major surface and a second major surface, the major surfaces being opposite to each other; as well as an optical film structure defining an outer surface, the optical film structure being disposed on the first major surface, The optical film structure comprises a scratch-resistant layer and a plurality of alternating high refractive index (RI) and low RI layers, The optical film structure further comprises an outer structure and an inner structure, and the scratch-resistant layer is disposed between the outer structure and the inner structure. One or both of the following conditions exist: (i) the outer structure comprises at least one medium RI layer, the at least one medium RI layer being in contact with one or both of: (a) the scratch resistant layer, and (b) one of the high RI layers; and (ii) the sum of the physical thicknesses of all of the low RI layers in the outer structure is less than about 200 nm, and Further wherein the at least one medium RI layer comprises a refractive index of 1.55 to 1.80, each of the high RI layers comprises a refractive index greater than 1.80, and each of the low RI layers comprises a refractive index less than 1.

55.

2. The transparent article of claim 1, wherein the outer structure comprises at least one medium RI layer, the at least one medium RI layer being in contact with one or both of: (a) the scratch resistant layer, and (b) one of the high RI layers.

3. The transparent article of claim 1 or claim 2, wherein the sum of the physical thicknesses of all of the low RI layers in the outer structure is less than about 75 nm.

4. The transparent article of claim 3, wherein the transparent article exhibits an average first surface photopic reflectance of less than 7% and a first surface reflectance at a wavelength of 940 nm of less than 8%, each measured at a near normal incidence angle.

5. The transparent article of claim 1, wherein the sum of the physical thicknesses of all of the low RI layers in the outer structure is less than about 200 nm, and further wherein the transparent article exhibits an average first surface photopic reflectance of less than 3% and a first surface reflectance at a wavelength of 940 nm of less than 5%, each measured at near normal incidence.

6. A transparent article as described in claim 1, wherein the outer structure includes at least one medium RI layer, and the at least one medium RI layer is in contact with one or both of the following: (a) the scratch-resistant layer, and (b) one of the high RI layers, and further wherein the substrate includes a glass-ceramic substrate having an elastic modulus greater than 85 GPa and a fracture toughness greater than 0.8 MPa·√m.

7. The transparent article of claim 1, wherein the optical film structure has a physical thickness of about 200 nm to 5000 nm, wherein the article exhibits an average first surface photopic reflectance of less than 6%, and further wherein the article exhibits one or more of the following: (a) a hardness greater than 11 GPa at an indentation depth of about 20 nm or 40 nm as measured by the Berkovich Hardness Test at the outer surface of the optical film structure; (b) a hardness greater than 15 GPa at an indentation depth of 100 nm; and (c) a hardness greater than 16 GPa at an indentation depth of 125 nm.

8. The transparent article of claim 1, wherein the optical film structure has a physical thickness of about 200 nm to 800 nm, wherein the article exhibits an average first surface photopic reflectance of less than 6%, and further wherein the article exhibits one or more of the following: (a) a hardness greater than 9 GPa at an indentation depth of 20 nm, as measured by the Berkovich Hardness Test at the outer surface of the optical film structure; (b) a hardness greater than 10 GPa at an indentation depth of 40 nm; (c) a hardness greater than 12 GPa at an indentation depth of 100 nm; (d) a hardness greater than 12 GPa at an indentation depth of 125 nm.

9. The transparent article of claim 1, wherein the scratch resistant layer has a physical thickness of about 100 nm to less than 2000 nm, and further wherein the outer structure includes at least one medium RI layer, the at least one medium RI layer being in contact with one or both of: (a) the scratch resistant layer, and (b) one of the high RI layers.

10. The transparent article of any one of claims 1-9, further comprising a textured surface region defined by the first major surface of the substrate, wherein the textured surface region comprises a plurality of structural features and an average texture height (R) of 50 nm to 800 nm. text ).

11. The transparent article of any one of claims 1 to 9, further comprising a diffractive surface region defined by the first major surface of the substrate, wherein the diffractive surface region comprises a plurality of structural features having a plurality of different heights with a bimodal or multimodal distribution.

12. A transparent product, comprising: a substrate including a first major surface and a second major surface, the major surfaces being opposite to each other; as well as an optical film structure defining an outer surface, the optical film structure being disposed on the first major surface, The optical film structure comprises a scratch-resistant layer and a plurality of alternating high refractive index (RI) and low RI layers, The optical film structure further comprises an outer structure and an inner structure, and the scratch-resistant layer is disposed between the outer structure and the inner structure. wherein the outer structure comprises at least one medium RI layer in contact with one or both of: (a) the scratch resistant layer, and (b) one of the high RI layers, and Further wherein the medium RI layer comprises a refractive index of 1.55 to 1.80, each of the high RI layers comprises a refractive index greater than 1.80, and each of the low RI layers comprises a refractive index less than 1.

55.

13. The transparent article of claim 12, wherein the article exhibits a hardness greater than 15 GPa as measured by the Berkovich Hardness Test at an indentation depth of about 125 nm from the outer surface of the optical film structure.

14. The transparent article of claim 12, wherein the article exhibits a hardness greater than 16 GPa as measured by the Berkovich Hardness Test at an indentation depth of about 125 nm from the outer surface of the optical film structure.

15. The transparent article of any one of claims 12-14, wherein the article exhibits an average first surface photopic reflectance of less than 5%, a first surface reflectance at a wavelength of 940 nm of less than 6%, and an average first surface reflectance at a wavelength of 1000 nm to 1700 nm of less than 10%, each measured at a near normal incidence angle.

16. The transparent article of any one of claims 12 to 15, wherein each high RI layer and the scratch resistant layer comprises Si3N4, SiN y and SiO x N y One or more of, and each low RI layer comprises SiO2, SiO x and SiO x N y One or more of .

17. The transparent article of any one of claims 12 to 16, wherein the scratch resistant layer and each medium RI layer comprises SiO x N y .

18. The transparent article of any one of claims 12-17, wherein the optical film structure exhibits a residual compressive stress greater than or equal to 700 MPa and an elastic modulus greater than or equal to 140 GPa.

19. The transparent article of any one of claims 12-18, wherein the substrate is a glass-ceramic material comprising an elastic modulus greater than 85 GPa and a fracture toughness greater than 0.8 MPa·√m.

20. The transparent article of any one of claims 12-19, wherein the optical film structure exhibits a residual compressive stress of 700 MPa to 1100 MPa and an elastic modulus of 140 GPa to 200 GPa.

21. The transparent article of any one of claims 12-20, wherein the optical film structure exhibits an elastic modulus of 140 GPa to 180 GPa.

22. The transparent article of any one of claims 12-21, wherein the substrate has a residual surface compressive stress of 200 MPa to 1200 MPa and a depth of compression (DOC) of 5 μm to 150 μm.

23. The transparent article of any one of claims 12-22, wherein the substrate further exhibits a maximum central tension (CT) value of about 80 MPa to 200 MPa, and further wherein the substrate has a thickness of about 1.5 mm or less.

24. The transparent article of any one of claims 12-23, wherein the substrate has a residual surface compressive stress of 200 MPa to 400 MPa.

25. A transparent product, comprising: a substrate including a first major surface and a second major surface, the major surfaces being opposite to each other; as well as an optical film structure defining an outer surface, the optical film structure being disposed on the first major surface, The optical film structure comprises a scratch-resistant layer and a plurality of alternating high refractive index (RI) and low RI layers, The optical film structure further comprises an outer structure and an inner structure, the scratch-resistant layer is disposed between the outer structure and the inner structure, and Further wherein the sum of the physical thicknesses of all of the low RI layers in the outer structure is less than about 75 nm.

26. The transparent article of claim 25, wherein the article exhibits a hardness greater than 15 GPa as measured by the Berkovich Hardness Test at an indentation depth of about 125 nm from the outer surface of the optical film structure.

27. The transparent article of claim 25, wherein the article exhibits a hardness greater than 17 GPa as measured by the Berkovich Hardness Test at an indentation depth of about 125 nm from the outer surface of the optical film structure.

28. The transparent article of any one of claims 25-27, wherein the article exhibits an average first surface photopic reflectance of less than 5%, a first surface reflectance at a wavelength of 940 nm of less than 6%, and an average first surface reflectance at a wavelength of 1000 nm to 1700 nm of less than 10%, each measured at a near normal incidence angle.

29. The transparent article of any one of claims 25-28, wherein each high RI layer and the scratch resistant layer comprises Si3N4, SiN y and SiO x N y One or more of, and each low RI layer comprises SiO2, SiO x and SiO x N y One or more of .

30. The transparent article of any one of claims 25-29, wherein the sum of the physical thicknesses of all of the low RI layers in the outer structure is less than about 65 nm.

31. The transparent article of any one of claims 25-30, wherein the optical film structure exhibits a residual compressive stress greater than or equal to 700 MPa and an elastic modulus greater than or equal to 140 GPa.

32. The transparent article of any one of claims 25-31, wherein the substrate is a glass-ceramic material comprising an elastic modulus greater than 85 GPa and a fracture toughness greater than 0.8 MPa·√m.

33. The transparent article of any one of claims 25-32, wherein the optical film structure exhibits a residual compressive stress of 700 MPa to 1100 MPa and an elastic modulus of 140 GPa to 200 GPa.

34. The transparent article of any one of claims 25-33, wherein the optical film structure exhibits an elastic modulus of 140 GPa to 180 GPa.

35. The transparent article of any one of claims 25-34, wherein the substrate has a residual surface compressive stress of 200 MPa to 1200 MPa and a depth of compression (DOC) of 5 μm to 150 μm.

36. The transparent article of any one of claims 25-35, wherein the substrate further exhibits a maximum central tension (CT) value of about 80 MPa to 200 MPa, and further wherein the substrate has a thickness of about 1.5 mm or less.

37. The transparent article of any one of claims 25-36, wherein the substrate has a residual surface compressive stress of 200 MPa to 400 MPa.

38. A transparent product, comprising: a substrate including a first major surface and a second major surface, the major surfaces being opposite to each other; as well as an optical film structure defining an outer surface, the optical film structure being disposed on the first major surface, The optical film structure comprises a scratch-resistant layer and a plurality of alternating high refractive index (RI) and low RI layers, The optical film structure further comprises an outer structure and an inner structure, and the scratch-resistant layer is disposed between the outer structure and the inner structure. wherein the outer structure comprises at least one medium RI layer in contact with one of the high RI layers and the scratch resistant layer, wherein the medium RI layer comprises a refractive index of 1.55 to 1.80, each of the high RI layers comprises a refractive index greater than 1.80, and each of the low RI layers comprises a refractive index less than 1.55, and Further wherein the sum of the physical thicknesses of all of the low RI layers in the outer structure is less than about 75 nm.

39. The transparent article of claim 38, wherein the article exhibits a hardness greater than 15 GPa as measured by the Berkovich Hardness Test at an indentation depth of about 125 nm from the outer surface of the optical film structure.

40. The transparent article of claim 38, wherein the article exhibits a hardness greater than 17 GPa as measured by the Berkovich Hardness Test at an indentation depth of about 125 nm from the outer surface of the optical film structure.

41. The transparent article of any one of claims 38-40, wherein the article exhibits an average first surface photopic reflectance of less than 5%, a first surface reflectance at a wavelength of 940 nm of less than 6%, and an average first surface reflectance at a wavelength of 1000 nm to 1700 nm of less than 10%, each measured at a near normal incidence angle.

42. The transparent article of any one of claims 38-41, wherein the article exhibits an average first surface photopic reflectance of about 4% or less, a first surface reflectance at a wavelength of 940 nm of about 4.3% or less, and an average first surface reflectance at a wavelength of 1000 nm to 1700 nm of less than 8%, each measured at a near normal incidence angle.

43. The transparent article of any one of claims 38 to 42, wherein each high RI layer and the scratch resistant layer comprises Si3N4, SiN y and SiO x N y One or more of, and each low RI layer comprises SiO2, SiO x and SiO x N y One or more of .

44. The transparent article of any one of claims 38-43, wherein the scratch resistant layer and each medium RI layer comprises SiO x N y , and further wherein the sum of the physical thicknesses of all of the low RI layers in the outer structure is less than about 65 nm.

45. The transparent article of any one of claims 38-44, wherein the optical film structure exhibits a residual compressive stress greater than or equal to 700 MPa and an elastic modulus greater than or equal to 140 GPa.

46. ​​The transparent article of any one of claims 38-45, wherein the substrate is a glass-ceramic material comprising an elastic modulus greater than 85 GPa and a fracture toughness greater than 0.8 MPa·√m.

47. The transparent article of any one of claims 38-46, wherein the optical film structure exhibits a residual compressive stress of 700 MPa to 1100 MPa and an elastic modulus of 140 GPa to 200 GPa.

48. The transparent article of any one of claims 38-47, wherein the optical film structure exhibits an elastic modulus of 140 GPa to 180 GPa.

49. The transparent article of any one of claims 38-48, wherein the substrate has a residual surface compressive stress of 200 MPa to 1200 MPa and a depth of compression (DOC) of 5 μm to 150 μm.

50. The transparent article of any one of claims 38-49, wherein the substrate further exhibits a maximum central tension (CT) value of about 80 MPa to 200 MPa, and further wherein the substrate has a thickness of about 1.5 mm or less.

51. The transparent article of any one of claims 38-50, wherein the substrate has a residual surface compressive stress of 200 MPa to 400 MPa.

52. A transparent product, comprising: a substrate including a first major surface and a second major surface, the major surfaces being opposite to each other; as well as an optical film structure defining an outer surface, the optical film structure being disposed on the first major surface, The optical film structure comprises a scratch-resistant layer and a plurality of alternating high refractive index (RI) and low RI layers, The optical film structure further comprises an outer structure and an inner structure, and the scratch-resistant layer is disposed between the outer structure and the inner structure. wherein the sum of the physical thicknesses of all of said low RI layers in said outer structure is less than about 75 nm, and Further wherein the transparent article exhibits an average first surface photopic reflectance of less than 7% and a first surface reflectance at a wavelength of 940 nm of less than 8%, each measured at a near normal incidence angle.

53. The transparent article of claim 52, wherein the sum of the physical thicknesses of all of the low RI layers in the outer structure is less than about 50 nm.

54. The transparent article of claim 52 or claim 53, wherein the article exhibits a first surface reflectivity at wavelengths of 1000 nm to 1700 nm of about 7% or less measured at near normal incidence.

55. The transparent article of any one of claims 52-54, wherein the article exhibits a hardness greater than 15 GPa as measured by the Berkovich Hardness Test at an indentation depth of about 125 nm from the outer surface of the optical film structure.

56. The transparent article of any one of claims 52-55, wherein each high RI layer and the scratch resistant layer comprises SiO x N y , and each low RI layer contains SiO2, SiO x and SiO x N y One or more of .

57. The transparent article of any one of claims 52-56, wherein the optical film structure exhibits a residual compressive stress greater than or equal to 700 MPa and an elastic modulus greater than or equal to 140 GPa.

58. The transparent article of any one of claims 52-57, wherein the substrate is a glass-ceramic material comprising an elastic modulus greater than 85 GPa and a fracture toughness greater than 0.8 MPa·√m.

59. The transparent article of any one of claims 52-58, wherein the optical film structure exhibits a residual compressive stress of 700 MPa to 1100 MPa and an elastic modulus of 140 GPa to 200 GPa.

60. The transparent article of any one of claims 52-59, wherein the optical film structure exhibits an elastic modulus of 140 GPa to 180 GPa.

61. The transparent article of any one of claims 52-60, wherein the substrate has a residual surface compressive stress of 200 MPa to 1200 MPa and a depth of compression (DOC) of 5 μm to 150 μm.

62. The transparent article of any one of claims 52-61, wherein the substrate further exhibits a maximum central tension (CT) value of about 80 MPa to 200 MPa, and further wherein the substrate has a thickness of about 1.5 mm or less.

63. The transparent article of any one of claims 52-62, wherein the substrate has a residual surface compressive stress of 200 MPa to 400 MPa.

64. The transparent article of any one of claims 52-63, wherein the inner structure comprises one of: (a) a plurality of alternating high refractive index (RI) layers and low RI layers; (b) a refractive index gradient; and (c) a composition gradient.

65. A transparent product, comprising: a substrate including a first major surface and a second major surface, the major surfaces being opposite to each other; as well as an optical film structure defining an outer surface, the optical film structure being disposed on the first major surface, The optical film structure comprises a scratch-resistant layer and a plurality of alternating high refractive index (RI) and low RI layers, The optical film structure further comprises an outer structure and an inner structure, and the scratch-resistant layer is disposed between the outer structure and the inner structure. wherein the sum of the physical thicknesses of all of said low RI layers in said outer structure is less than about 200 nm, and Further wherein the article exhibits an average first surface photopic reflectance of less than 3% and a first surface reflectance at a wavelength of 940 nm of less than 5%, each measured at near normal incidence.

66. The transparent article of claim 65, wherein the sum of the physical thicknesses of all of the low RI layers in the outer structure is less than about 150 nm.

67. The transparent article of claim 65, wherein the sum of the physical thicknesses of all of the low RI layers in the outer structure is less than about 100 nm.

68. The transparent article of any one of claims 65-67, wherein the article exhibits a first surface average reflectivity at wavelengths of 1000 nm to 1700 nm of about 8% or less measured at near normal incidence.

69. The transparent article of any one of claims 65-68, wherein the article exhibits a first surface average reflectivity at wavelengths of 1000 nm to 1700 nm of about 4% or less measured at near normal incidence.

70. The transparent article of any one of claims 65-69, wherein the article exhibits an average first surface photopic reflectance of less than 2.2%.

71. The transparent article of any one of claims 65-70, wherein the article exhibits a hardness greater than 12 GPa as measured by the Berkovich Hardness Test at an indentation depth of about 125 nm from the outer surface of the optical film structure.

72. The transparent article of any one of claims 65-71, wherein the outer structure comprises at least one medium RI layer in contact with one of the high RI layers and the scratch resistant layer, wherein the medium RI layer comprises a refractive index of 1.55 to 1.80, each of the high RI layers comprises a refractive index greater than 1.80, and each of the low RI layers comprises a refractive index less than 1.55, and further wherein the scratch resistant layer and each medium RI layer comprise SiO x N y .

73. The transparent article of any one of claims 65-72, wherein the optical film structure exhibits a residual compressive stress greater than or equal to 700 MPa and an elastic modulus greater than or equal to 140 GPa.

74. The transparent article of any one of claims 65-73, wherein the substrate is a glass-ceramic material comprising an elastic modulus greater than 85 GPa and a fracture toughness greater than 0.8 MPa·√m.

75. The transparent article of any one of claims 65-74, wherein the optical film structure exhibits a residual compressive stress of 700 MPa to 1100 MPa and an elastic modulus of 140 GPa to 200 GPa.

76. The transparent article of any one of claims 65-75, wherein the optical film structure exhibits an elastic modulus of 140 GPa to 180 GPa.

77. The transparent article of any one of claims 65-76, wherein the substrate has a residual surface compressive stress of 200 MPa to 1200 MPa and a depth of compression (DOC) of 5 μm to 150 μm.

78. The transparent article of any one of claims 65-77, wherein the substrate further exhibits a maximum central tension (CT) value of about 80 MPa to 200 MPa, and further wherein the substrate has a thickness of about 1.5 mm or less.

79. The transparent article of any one of claims 65-78, wherein the substrate has a residual surface compressive stress of 200 MPa to 400 MPa.

80. The transparent article of any one of claims 65-79, wherein the inner structure comprises one of: (a) a plurality of alternating high refractive index (RI) layers and low RI layers; (b) a refractive index gradient; and (c) a composition gradient.

81. A display device comprising the transparent article according to any one of claims 1 to 11, wherein the transparent article is used as a protective cover for the display device.

82. A display device comprising the transparent article according to any one of claims 12 to 24, wherein the transparent article is used as a protective cover for the display device.

83. A display device comprising the transparent article according to any one of claims 25 to 37, wherein the transparent article is used as a protective cover for the display device.

84. A display device comprising the transparent article according to any one of claims 38 to 51, wherein the transparent article is used as a protective cover for the display device.

85. A display device comprising the transparent article according to any one of claims 52 to 64, wherein the transparent article is used as a protective cover for the display device.

86. A display device comprising the transparent article according to any one of claims 65 to 80, wherein the transparent article is used as a protective cover for the display device.

87. A transparent product, comprising: A glass ceramic substrate comprising a first major surface and a second major surface, the major surfaces being opposite to each other; as well as an optical film structure defining an outer surface, the optical film structure being disposed on the first major surface, The optical film structure comprises a scratch-resistant layer and a plurality of alternating high refractive index (RI) and low RI layers, The optical film structure further comprises an outer structure and an inner structure, and the scratch-resistant layer is disposed between the outer structure and the inner structure. wherein the outer structure comprises at least one medium RI layer in contact with one of the high RI layers and the scratch resistant layer, wherein the medium RI layer comprises a refractive index of 1.55 to 1.80, each of the high RI layers comprises a refractive index greater than 1.80, and each of the low RI layers comprises a refractive index less than 1.55, and Further wherein the glass ceramic substrate comprises an elastic modulus greater than 85 GPa and a fracture toughness greater than 0.8 MPa·√m.

88. The transparent article of claim 87, wherein the optical film structure exhibits a residual compressive stress greater than or equal to 700 MPa and an elastic modulus greater than or equal to 140 GPa.

89. The transparent article of claim 87, wherein the optical film structure exhibits a residual compressive stress of 700 MPa to 1100 MPa and an elastic modulus of 140 GPa to 200 GPa.

90. The transparent article of any one of claims 87-89, wherein the optical film structure exhibits an elastic modulus of 140 GPa to 180 GPa.

91. The transparent article of any one of claims 87-90, wherein the glass ceramic substrate has a residual surface compressive stress of 200 MPa to 1200 MPa and a depth of compression (DOC) of 5 μm to 150 μm.

92. The transparent article of any one of claims 87-91, wherein the glass-ceramic substrate further exhibits a maximum central tension (CT) value of about 80 MPa to 200 MPa, and further wherein the glass-ceramic substrate has a thickness of about 1.5 mm or less.

93. The transparent article of any one of claims 87-92, wherein the glass-ceramic substrate has a residual surface compressive stress of 200 MPa to 400 MPa.

94. The transparent article of claim 88, wherein the article exhibits an average stress at failure of 700 MPa or greater in a ring-to-ring test with the outer surface of the optical film structure under tension.

95. The transparent article of claim 88, wherein the article exhibits an average stress at failure of 500 MPa or greater in a four point bend test with the outer surface of the optical film structure under tension.

96. A display device comprising the transparent article according to any one of claims 87-95, wherein the transparent article is used as a protective cover for the display device.

97. A transparent product, comprising: a substrate including a first major surface and a second major surface, the major surfaces being opposite to each other; as well as an optical film structure defining an outer surface, the optical film structure being disposed on the first major surface, The optical film structure comprises a scratch-resistant layer and a plurality of alternating high refractive index (RI) and low RI layers, The optical film structure further comprises an outer structure and an inner structure, and the scratch-resistant layer is disposed between the outer structure and the inner structure. wherein the outer structure comprises at least one medium RI layer in contact with one or both of: (a) the scratch resistant layer, and (b) one of the high RI layers, Wherein the at least one medium RI layer comprises a refractive index of 1.55 to 1.80, each of the high RI layers comprises a refractive index greater than 1.80, and each of the low RI layers comprises a refractive index less than 1.

55. wherein the optical film structure has a physical thickness of about 200 nm to 5000 nm, wherein the article exhibits a first surface average photopic reflectance of less than 6%, and Further wherein the article exhibits one or more of the following: (i) a hardness greater than 11 GPa at an indentation depth of approximately 20 nm or 40 nm as measured by the Berkovich Hardness Test at the outer surface of the optical film structure; (ii) a hardness greater than 15 GPa at an indentation depth of 100 nm; and (iii) a hardness greater than 16 GPa at an indentation depth of 125 nm.

98. The transparent article of claim 97, wherein the substrate is a glass-ceramic material comprising an elastic modulus greater than 85 GPa and a fracture toughness greater than 0.8 MPa·√m.

99. The transparent article of claim 97 or claim 98, wherein the optical film structure exhibits a residual compressive stress of 700 MPa to 1100 MPa and an elastic modulus of 140 GPa to 200 GPa.

100. The transparent article of any one of claims 97-99, wherein the optical film structure exhibits an elastic modulus of 140 GPa to 180 GPa.

101. The transparent article of any one of claims 97-100, wherein the substrate has a residual surface compressive stress of 200 MPa to 1200 MPa and a depth of compression (DOC) of 5 μm to 150 μm.

102. The transparent article of any one of claims 97-101, wherein the substrate further exhibits a maximum central tension (CT) value of about 80 MPa to 200 MPa, and further wherein the substrate has a thickness of about 1.5 mm or less.

103. The transparent article of any one of claims 97-102, wherein the substrate has a residual surface compressive stress of 200 MPa to 400 MPa.

104. The transparent article of any one of claims 97-103, wherein the internal structure comprises one of: (a) a plurality of alternating high refractive index (RI) layers and low RI layers; (b) a refractive index gradient; and (c) a composition gradient.

105. The transparent article of any one of claims 97-104, wherein the optical film structure has a physical thickness of about 800 nm to 4000 nm.

106. A display device comprising the transparent article as claimed in any one of claims 97 to 105, wherein the transparent article is used as a protective cover for the display device.

107. A transparent product, comprising: a substrate including a first major surface and a second major surface, the major surfaces being opposite to each other; as well as an optical film structure defining an outer surface, the optical film structure being disposed on the first major surface, The optical film structure comprises a scratch-resistant layer and a plurality of alternating high refractive index (RI) and low RI layers, The optical film structure further comprises an outer structure and an inner structure, and the scratch-resistant layer is disposed between the outer structure and the inner structure. wherein the outer structure comprises at least one medium RI layer in contact with one or both of: (a) the scratch resistant layer, and (b) one of the high RI layers, Wherein the at least one medium RI layer comprises a refractive index of 1.55 to 1.80, each of the high RI layers comprises a refractive index greater than 1.80, and each of the low RI layers comprises a refractive index less than 1.

55. wherein the optical film structure has a physical thickness of about 200 nm to 800 nm, wherein the article exhibits a first surface average photopic reflectance of less than 6%, and Further wherein the article exhibits one or more of the following: (i) a hardness greater than 9 GPa at an indentation depth of 20 nm, as measured by the Berkovich hardness test at the outer surface of the optical film structure; (ii) a hardness greater than 10 GPa at an indentation depth of 40 nm; (iii) a hardness greater than 12 GPa at an indentation depth of 100 nm; (iv) a hardness greater than 12 GPa at an indentation depth of 125 nm.

108. The transparent article of claim 107, wherein the substrate is a glass-ceramic material comprising an elastic modulus greater than 85 GPa and a fracture toughness greater than 0.8 MPa·√m.

109. The transparent article of claim 107 or claim 108, wherein the optical film structure exhibits a residual compressive stress of 700 MPa to 1100 MPa and an elastic modulus of 140 GPa to 200 GPa.

110. The transparent article of any one of claims 107-109, wherein the optical film structure exhibits an elastic modulus of 140 GPa to 180 GPa.

111. The transparent article of any one of claims 107-110, wherein the substrate has a residual surface compressive stress of 200 MPa to 1200 MPa and a depth of compression (DOC) of 5 μm to 150 μm.

112. The transparent article of any one of claims 107-111, wherein the substrate further exhibits a maximum central tension (CT) value of about 80 MPa to 200 MPa, and further wherein the substrate has a thickness of about 1.5 mm or less.

113. The transparent article of any one of claims 107-112, wherein the substrate has a residual surface compressive stress of 200 MPa to 400 MPa.

114. The transparent article of any one of claims 107-113, wherein the inner structure comprises one of: (a) a plurality of alternating high refractive index (RI) layers and low RI layers; (b) a refractive index gradient; and (c) a composition gradient.

115. The transparent article of any one of claims 107-114, wherein the optical film structure has a physical thickness of about 200 nm to 600 nm.

116. A display device comprising the transparent article as claimed in any one of claims 107 to 115, wherein the transparent article is used as a protective cover for the display device.

117. A transparent product, comprising: a substrate including a first major surface and a second major surface, the major surfaces being opposite to each other; as well as an optical film structure defining an outer surface, the optical film structure being disposed on the first major surface, The optical film structure comprises a scratch-resistant layer and a plurality of alternating high refractive index (RI) and low RI layers, The optical film structure further comprises an outer structure and an inner structure, and the scratch-resistant layer is disposed between the outer structure and the inner structure. wherein the outer structure comprises at least one medium RI layer in contact with one or both of: (a) the scratch resistant layer, and (b) one of the high RI layers, wherein the at least one medium RI layer comprises a refractive index of 1.55 to 1.80, each of the high RI layers comprises a refractive index greater than 1.80, and each of the low RI layers comprises a refractive index less than 1.55, and Further wherein the scratch resistant layer has a physical thickness of about 100 nm to less than 2000 nm.

118. The transparent article of claim 117, wherein the substrate is a glass-ceramic material comprising an elastic modulus greater than 85 GPa and a fracture toughness greater than 0.8 MPa·√m.

119. The transparent article of claim 117 or claim 118, wherein the optical film structure exhibits a residual compressive stress of 700 MPa to 1100 MPa and an elastic modulus of 140 GPa to 200 GPa.

120. The transparent article of any one of claims 117-119, wherein the optical film structure exhibits an elastic modulus of 140 GPa to 180 GPa.

121. The transparent article of any one of claims 117-120, wherein the substrate has a residual surface compressive stress of 200 MPa to 1200 MPa and a depth of compression (DOC) of 5 μm to 150 μm.

122. The transparent article of any one of claims 117-121, wherein the substrate further exhibits a maximum central tension (CT) value of about 80 MPa to 200 MPa, and further wherein the substrate has a thickness of about 1.5 mm or less.

123. The transparent article of any one of claims 117-122, wherein the substrate has a residual surface compressive stress of 200 MPa to 400 MPa.

124. A display device comprising the transparent article as described in any one of claims 117-123, wherein the transparent article is used as a protective cover for the display device.

125. The transparent article of any one of claims 97-106, further comprising a textured surface region defined by the first major surface of the substrate, wherein the textured surface region comprises a plurality of structural features and an average texture height (R) of 50 nm to 800 nm. text ).

126. The transparent article of any one of claims 107-116, further comprising a textured surface region defined by the first major surface of the substrate, wherein the textured surface region comprises a plurality of structural features and an average texture height (R) of 50 nm to 800 nm. text ).

127. The transparent article of any one of claims 117-124, further comprising a textured surface region defined by the first major surface of the substrate, wherein the textured surface region comprises a plurality of structural features and an average texture height (R) of 50 nm to 800 nm. text ).

128. A transparent product as described in any one of claims 97-106, further comprising a diffractive surface area defined by the first major surface of the substrate, wherein the diffractive surface area comprises a plurality of structural features having a plurality of different heights with a bimodal or multimodal distribution.

129. The transparent product of any one of claims 107-116, further comprising a diffractive surface region defined by the first major surface of the substrate, wherein the diffractive surface region comprises a plurality of structural features having a plurality of different heights with a bimodal or multimodal distribution.

130. The transparent product of any one of claims 117-124, further comprising a diffractive surface region defined by the first major surface of the substrate, wherein the diffractive surface region comprises a plurality of structural features having a plurality of different heights with a bimodal or multimodal distribution.

Citation Information

Patent Citations

  • Process for making of glass articles with optical and easy-to-clean coatings

    US20140113083A1

  • Optical film structures, inorganic oxide articles with optical film structures, and methods of making the same

    US20200158916A1

  • Chemical strengthening method

    US4483700A

  • Strengthening glass by ion exchange

    US5674790A

  • Down-drawable, chemically strengthened glass for cover plate

    US7666511B2